Rice seedling diagnosis of light and water stress based on green – blue channel feature enhancement - Shaowen Liu; Liwei Wang; Zhigang Zhang; Haoran Xu; Yubo Yang; Rui Gao; Zhongbin Su (Computers and Electronics in Agriculture, 2026)

High-P-T experimental constraints on the genesis of post-collisional porphyry Cu-Au magmas: A case study from the southeastern Tibetan Plateau - Gong Liu; Xian-Wu Bi; Lei-Luo Xu; Wei Du; Lin-Bo Shang; Jing-Jing Zhu; Ming-Liang Huang; Rui Ma (Lithos, 2026)

Endogenous 6-phospho-β-glucosidase overexpression in Lactiplantibacillus plantarum modulates selective enrichment of bioactive and volatile metabolites in black tea extract - Yao-Zeng Zhang; Zhi-Peng Cheng; Pei-Yi Feng; Xin-Xin Liu; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Microbiology, 2026)

Genotype-dependent Food Competition Behaviors in Male Fruit Flies Under Distinct Thermal Conditions - Rui Han; Jun Zhang; Jia-Xin Wang; Yu-Xin Wang; An-Qi Wen; Hao-Wei Wang; Xu Liang; Xiang-Haoran Lin; Lin-Xiang Liu; Ke-Jing Feng (Journal of Insect Behavior, 2026)

Safety and efficacy of recombinant botulinum toxin type A (Eveotox®) in patients with post-stroke upper limb spasticity: Results from a Phase Ib/II clinical trial - Rongrong Lu; Lingjing Jin; Jianzhong Xiong; Lixin Zhang; Yaling Liu; Leilei Xu; Rui Wu; Jianhua Tang; Liandong Zhao; Lihua Dong; Weifeng Luo; Yu Pan; et al. (Toxicon, 2026)

Water quality assessment in multi-salinity groundwater of muddy coastal zones using a function-adaptive weight water quality index - Qiming Sun; Xinyue Chang; Rui Xu; Xin Ji; Jianhe Yang; Hongwei Liu; Maosheng Gao; Guohua Hou; Zhenlin Liu; Xianmin Ke; Jie Dong (Journal of Contaminant Hydrology, 2026)

Dynamic reliability analysis of high earth-rockfill dams under non-stationary and non-Gaussian ground motions using an L-moment-based simplified quintic HPM - Haoyu Yao; Mingyang Xu; Dianjun Zhu; Rui Pang; Bin Xu; Jun Liu (Engineering Structures, 2026)

Pathways and functional enzyme-mediated mechanisms of tetracycline biodegradation by the marine microalgae Phaeodactylum tricornutum - Xiaomin Wu; Jichen Chen; Hua Du; Zhitao Ye; Shaolong Zhang; Rui Bao; Yuanze Xu; James P. Meador; Qiaoxin Zhang; Shuqi Wang; Zhen Wang; Xiaojuan Liu (Bioresource Technology, 2026)

Spatiotemporal variations in LNAPL infiltration in the vadose zone microbial community metabolism and coupled abiotic‒biotic mechanisms - Ziqiu Nie; Rui Zuo; Zhenkun Xue; Jie Yang; Donghui Xu; Jiawei Liu; Ziyi Wu; Shengjie Hu (Water Research, 2026)

A hybrid machine learning and data assimilation framework for penman–monteith evapotranspiration estimation over China - Xiaowen Wu; Xiang Li; Jianli Ding; Shaomin Liu; Tongren Xu; Lisheng Song; Sayed M. Bateni; Ziwei Xu; Dongxing Wu; Xinlei He; Jinjie Wang; Rui Liu; et al. (Remote Sensing of Environment, 2026)

How elevated-road design and adjacent building configuration shape vertical exposure to traffic-related particles in dense urban environments - Ruhui Cao; Yunlu Wang; Rui Xu; Ming Cai; Yonghong Liu; Zhanyong Wang (Landscape and Urban Planning, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

Synergistic co-fermentation of algal sludge and Acorus calamus straw enhances short-chain fatty acid production through improved hydrolysis and microbial community steering - Biao Xu; You Deng; Zhihang Liu; Yanxin Lin; Wanmeng Lin; Ruitao Li; Chengyue Liang; Wudi Zhang; Rui Xu (Journal of Environmental Chemical Engineering, 2026)

Microecological trade-offs in partial nitritation under different ammonia-based food-to-microorganism ratios - Junwei Yang; Danyang Zhu; Enhui Xu; Linglong Shi; Rui Liu; Donghai Yang; Yu Hua; Xiaohu Dai (Journal of Environmental Chemical Engineering, 2026)

Composition-dependent interactions and thermal energy demand in lignocellulosic biomass pyrolysis for sustainable energy recovery - Mingming Liu; Yiyun Zhang; Wenhao Tang; Chenyi Duan; Minmin Gao; Chao Li; Rui Xu; Samuel Mbugua Nyambura; Xiaojun Gao; Xueru Zhu; Hua Li (Journal of Environmental Chemical Engineering, 2026)

CTAB-assisted synthesis of HoY2Ox composite oxide catalyst with highly exposed specific (211) plane for cyclohexene epoxidation - Yingjie Wang; Fang Wang; Yuting Luo; Rui Wang; Xiao Fan; Meng Xu; Junhua Liu (Journal of Environmental Chemical Engineering, 2026)

Phenolic acid-modified Arabic gum as an advanced functional stabilizer to enhance gelation and water retention of emulsion-type myofibrillar protein gels under oxidative stress - Tianhao Zhu; Mingze Xu; Yi Luan; Khubaib Ali; Peipei Yin; Qingling Wang; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Hydrocolloids, 2026)

Fermentation of ginseng juice by Lactiplantibacillus plantarum SP055 and Limosilactobacillus fermentum LB-9: Fermentation characteristics and ginsenoside biotransformation pathways - Jianwei Zang; Wei Liu; Chang Xu; Xia Fan; Yibo Shi; Xiaotong Hao; Yimeng Kou; Chunling Meng; Jiamin Xu; Tao Lin; Xin Rui; Dan Gan; et al. (Food Microbiology, 2026)

Waste akebiae trifoliata-derived WO3 hierarchical tubes efficient detection of ppb-level triethylamine gas at low temperature and application in food freshness detection - Wen-Xiao Li; Jia-Wang Wang; Rui-Long Li; Qiu-Yue Zheng; Bao-Yu Song; Bo-Ya Liu; Li-Xia Zhao; Ying Fu; Ying-Ming Xu (Chemical Engineering Journal, 2026)

Mechanistic insights into the adsorption and separation of nonpolar molecules on delocalization porous carbon: Dispersion interactions enhanced by multiple bonds - Peixin Wang; Jingxu Tian; Da Wei; Yue Sun; Bo Liu; Wenji Pi; Jun Ma; Yunfeng Zhang; Hongyu Chen; Rui Shi; Yang Guo; Xiang Xu; et al. (Chemical Engineering Journal, 2026)

FeCl3-catalyzed acetic acid pretreatment for surface-acetylated cellulose nanofibrils enabling Pickering emulsions and tunable optical composite films - Wei Liu; Xuan Wang; Rui Xu; Tairan Pang; Siyu Chen; Yuhan Liu; Ting Xu; Bo Pang; Haishun Du; Chuanling Si (Carbohydrate Polymers, 2026)

Disintegrated halophilic aerobic granular sludge restoration using zinc oxide nanoparticles: synergistic effects of fungal toxicity inhibition and extracellular polymeric substances production - Ya-Nan Mi; You-Wei Cui; Rui-Chun Yang; Yuan Sui; Zhen-Ying Li; Xu-Zhen Liu; Tong Ren (Bioresource Technology, 2026)

Characterizing on-road NO2 and particulate matter across urban road environments using city-scale mobile monitoring - Ruhui Cao; Dawen Yao; Rui Xu; Lewei Zeng; Yonghong Liu (Atmospheric Environment, 2026)

Characteristics and sources of organic vapors during O3 pollution in a megacity Wuhan in China: from hydrocarbons to highly oxidized molecules - Chong Liu; Xiaoxiao Li; Haoqian Wang; Linjun Li; Ning Ma; Xinchi Ye; Shan Xu; Jian Tan; Jin Peng; Rui Xia; Yi Zheng; Feiyue Mao; et al. (Atmospheric Environment, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

Harnessing a MMP-sensitive fluorescent probe for in-situ and reversible monitoring MMP alteration in dual color based on aggregation/monomer mechanism - Mengmeng Wei; Yuxuan Zhang; Wuyou Qiang; Jiawei Liu; Yi Qian; Jing Xu; Xiaoyan Tang; Jiaojiao Liu; Shenqiang Wang; Tingwang Jiang; Xifeng Yang; Xuekun Hong; et al. (Analytica Chimica Acta, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Transcriptome and metabolome analysis reveals that cuproptosis in bovine cumulus cells triggers the intercellular transmission of senescence and mitochondrial dysfunction to impair oocyte quality - Hong Xu; Tian Tian; Dan Xu; Xiaoxue Du; Rui Su; Jinghong Liang; Ying Liu; Yuqing Zhang; Chang Liu; Shuang Liang; Qingying Li; Deli Ding; et al. (Theriogenology, 2026)

Interfacial electron redistribution stabilizes Cu-centered redox cycling for efficient Fenton-like catalysis - Xiao-Ying Li; Ruo-Lan Xu; Ren Zhu; Ting-Yu Zhang; Wen-Rui Wang; Wu-Jun Liu; Hong Jiang (Journal of Cleaner Production, 2026)

Rockburst prediction as an epistemic problem: A physically consistent and statistically reliable framework under uncertainty - Rui Xu; Kai Zhan; Jinhai Liu; Zhe Li (Journal of Applied Geophysics, 2026)

Physics-validated early warning of high-energy mine tremors: Fusing multi-domain Gutenberg–Richter precursors with dynamic–static stress modelling - Jinhai Liu; Rui Xu; Kai Zhan; Shuo Fan; Zhe Li (Journal of Applied Geophysics, 2026)

Machine learning-based geographical origin discrimination of Smilax china - Boyuan Xu; Haotian Zhong; Yan Wang; Rui Liu; Xiao Huang; Heming Wu; Lei Wang; Aiping Deng; Yong Xiao; Kun Yu (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Origin of natural gas in the Permian Wujiaping shale formation, Southeast Sichuan Basin: Constraints from gas composition and isotopic geochemistry - Rui Yang; Jianting Xu; Wei Peng; Pengwei Wang; Haotian Liu; Li Zhang; Min Li (Fuel, 2026)

Engineered probiotic carriers enregulate coordinated cuproptosis and ferroptosis with immune activation against bladder cancer - Anguo Zhao; Rongkang Li; Rui Liang; Qi Zhuang; Yang Liu; Dashi Deng; Peng Yu; Lei Peng; Hongbo Xu; Jun Zhang; Zhangxin He; Xin Chen; et al. (Chemical Engineering Journal, 2026)

Low-cost and compact spring-type origami triboelectric nanogenerator for human kinetic energy harvesting and intelligent motion interaction - Zhelin Jin; Jie Cao; Rui Lei; Xu Han; Xianpeng Fu; Guoxu Liu; Haisheng Liu; Guanggui Cheng; Jianning Ding (Chemical Engineering Journal, 2026)

Molecular mechanisms of thermochemically-promoted precursor transformation to indole-3-acetic acid from sewage sludge via hydrothermal treatment: Comparative roles of H+/OH− - Rui Liu; Xinyu Bao; Ying Xu; Yue Zhang; Xiaohu Dai (Chemical Engineering Journal, 2026)

Polydopamine-functionalized mineral-based phase-change aerogels for protective safety and personal wearable thermal management - Ling Gong; Yongqian Liu; Rui Wang; Xueying Lu; Xu Li; Zhiming Liu (Chemical Engineering Journal, 2026)

Unveiling the role of Fe doping and Mo leaching in Fe-MoNi4@NiMoOx bifunctional catalysts for water splitting - Rui Ming; Jingjing Du; Lijian Xu; Yong Xu; Zhao Liang; Qiao Liu; Dongjiang Yang; Qiliang Wei; Weiyou Yang; Qing Shi (Chemical Engineering Journal, 2026)

Molten salt-assisted gasification unlocks graphitic nitrogen dominated porous carbons from biomass for high-performance zinc–air batteries - Yiwen Chen; Yangyang Chen; Changrong Zhong; Rui Liu; Gangyong Li; Yucan Zhu; Zhi Li; Minjie Zhou; Rui Tian; Binhong He; Wenyuan Xu (Bioresource Technology, 2026)

Effects of Compound Yeast Culture on the Intestinal Morphology, Intestinal Function, and Microorganisms of Weaned Lambs - Shixiong Liu; Puguo Hao; Hui Chen; Xueqiang Li; Xiaohui Xu; Rui Du; Chen Xue; Lan Yang; Dacheng Liu (Probiotics and Antimicrobial Proteins, 2026)

An integrated InSAR and SPF-constrained workflow for 3D landslide displacement reconstruction - Dezhi Zai; Rui Pang; Bin Xu; Jun Liu (Bulletin of Engineering Geology and the Environment, 2026)

Metagenomics analysis reveals crustose calcifying red algae-associated microbiome metabolic functions and potential mechanisms of inducer production - Zhangqi Zhao; Ying Zhang; Wanting Lu; Shanyin Guan; Rui Chai; Xitong Cen; Gaoyou Yao; Huiru Liu; Hanzhi Xu; Maoxian He; Chang Chen; Xu Gao; et al. (Algal Research, 2026)

A practical guide to investigating biomolecular condensates: a comment from the plant community - Jiaxuan Peng; Jaime Agudo-Canalejo; Monika Chodasiewicz; Daniël Van Damme; Vangelis Daskalakis; Manuel González-Fuente; Rui Gao; Emmanouela Filippidi; Hongwei Guo; Shengbo He; Kai Huang; Shuai Huang; et al. (Science China Life Sciences, 2026)
Biomolecular condensates formed through phase separation have emerged as a central principle of cellular organization, enabling the dynamic regulation of gene expression, signaling, metabolism, and stress responses. While early conceptual advances in condensate biology have largely originated from animal and in vitro systems, plant cells present a unique set of biological and technical challenges, including rigid cell walls, turgor pressure, plastid autofluorescence, complex endomembrane organization, and acute environmental responsiveness. These distinctive features impede the direct transfer of existing methodologies and drive the development of heterogeneous experimental practices. In this community comment, we present a comprehensive methodological framework for studying biomolecular condensates in plants, spanning in silico prediction, in vitro reconstitution, molecular dynamics simulations, live-cell and super-resolution imaging, material property measurements, membrane-associated condensates, and synthetic condensate engineering. We highlight best practices, common pitfalls, and plant-specific considerations, emphasizing the need for orthogonal validation, quantitative interpretation, and physiological relevance. By consolidating current methodologies and articulating shared principles, this review aims to establish a foundation for rigorous, reproducible, and conceptually coherent research in condensate biology of plants and beyond, with emerging implications for crop genetic improvement and synthetic biology applications.

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

Aeolian transport of evaporite minerals in Utopia Planitia: insights from Qaidam Basin spectral analogs - Jianxun Shen; Honglei Lin; Zhaopeng Chen; Xue Guo; Yuqi Wang; Yizhong Zhang; Li Liu; Chengxiang Huang; Enze Wang; Rui Chang; Xuesen Xu; Zhicheng Cui; et al. (Science Bulletin, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Divergent microplastic assemblages across natural and artificial waters in the Wei River Basin - Yiping Guo; Zhe Liu; Houpu Ren; Zixuan Zhang; Shichen Wei; Guojin Qi; Taishuo Zhang; Rui Wang; Xinyu Xu; Peng Liu; Hanzhong Jia (Journal of Water Process Engineering, 2026)

CWN-Net: a precise segmentation model for composite water networks using multi-source and multi-temporal remote sensing imagery - Mingyang Li; Huimin Lei; Fulin Li; Jiwen Huang; Yuzhi Shi; Shangjie Xu; Han Wang; Sinan Wang; Rui Wang; Lili Liu; Suzhen Cheng; Lei Guo; et al. (Journal of Hydrology, 2026)

Tuning the Cu/Zn ratio in copper-zinc phosphate catalysts: Mechanistic insights into activity and stability of anisole acetylation - Yuting Luo; Yingjie Wang; Rui Wang; Xiao Fan; Meng Xu; Junhua Liu; Fang Wang (Fuel, 2026)

Characterization of soy protein isolate-based complexes as novel food-grade stabilizers for oil-in-water (O/W) emulsions and myofibrillar protein emulsion gels - Mingze Xu; Khubaib Ali; Chen Gu; Peipei Yin; Rui Sun; Chang Liu; Qingling Wang; Xinxin Zhao; Mangang Wu (Food Research International, 2026)

Chitosan composite packaging film loaded with luteolin-superoxide dismutase nano-micelles: Enhancing food preservation performance - Pei Wu; Yilin Che; Rui Zhou; Yixin Tang; Lei Guo; Baiqiao Chen; Xinran Yan; Shanli Wu; Chang Liu; Mujie Kan; Jizhou Zhang; Xi Yang; et al. (Food Research International, 2026)

Elucidating the chemical and perceptual basis of lychee-like aroma in grapes through multi-omics and molecular sensory analyses - Jingyang Wang; Chengkui Qiao; Xiucai Fan; Ying Zhang; Rui Xu; Chonghuai Liu; Lei Sun (Food Chemistry, 2026)

Critical roles of CD4-1+ T cells and their secreted IL-21 in vaccine-induced humoral immunity in grass carp - Nan Zhang; Xun Liu; Rui Zhu; Wen-Jing Dong; Yan-Hui Huang; Yong-An Zhang; Xu-Jie Zhang (Fish & Shellfish Immunology, 2026)

Archimedean spiral solar evaporator for synergistic salt-resistant seawater desalination and uranium extraction - Rui Liu; Chenyang Dang; Yuntegn Cao; Shaobo Zhai; Yu Chu; Guiyin Xu; Meifang Zhu (Desalination, 2026)

In situ conversion of KNiF3 perovskite into a fluoride-rich ion/electron-conducting interphase for stable sodium metal anodes - Runzhi Xu; Yiqing Lu; Rui Ding; Yi Li; Weiming Li; Mingjun Xu; Tingyan Gu; Yuqi Liu; Chuyu Tan (Chemical Engineering Journal, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

Diverse plants recruit functional microbes as engines to drive ecosystem multifunctionality in post-fire forests - Hong-Rui Wang; Yu-Yang Liu; Yang Xu; Kai-Li Wang; Rui Deng; Fu-Juan Feng (Plant and Soil, 2026)

Palaeoenvironmental evolution and organic matter enrichment in the Early Silurian Yangtze Foreland Basin: Tectonosequence stratigraphic insights for shale gas exploration - Xinguo Li; Rui Liu; Yuxuan Wang; Junwei Pu; Hui Liu; Lu Xu; Tongtong Luo; Xiucheng Tan; Weiming Chen; Ruiying Chao (Applied Geochemistry, 2026)

The neutron-photon two-way coupling transport calculation based on the 2D/1D method - Shuaizheng Li; Zhouyu Liu; Rui Zhang; Ning Xu; Liangzhi Cao; Hongchun Wu (Annals of Nuclear Energy, 2026)

A photoelectrochemical signal amplification mechanism with Exonuclease III driven stable generation of “Swing Arm” tetrahedral DNA walkers for mediating photogenerated carrier transfer - Jinjie Liu; Dongquan Leng; Yu Du; Tingting Wu; Dehao Jia; Lei Yang; Rui Xu; Qin Wei (Analytica Chimica Acta, 2026)

ATP6AP2 ameliorates inflammation and pyroptosis in heart failure by promoting lysosome-dependent STING degradation - Xuan Zhao; Hui Zhang; Xinyue Ding; Huimin Wu; Min Li; Nengpin Yin; Junqing Gao; Youlong Xu; Rui Wang; Zhen Qi; Lina Xing; Zongjun Liu (Apoptosis, 2026)

Sedimentary DOM composition governs the environmental mobility of palladium in tropical island estuaries - Zhixin Li; Yuyan Liu; Ling Wang; Hongwei Yi; Rui Xu; Jianan Liu; Haofeng Liu; Ye Li; Min Liu (Marine Pollution Bulletin, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Two new protoflavonoids from Polytrichum commune and their cytotoxicity against human gastric cancer cells - Jing-jing Dong; Dan-rui Han; Hao Cheng; Xu-liu Shi; Dong-Lai Ma; Jian-kun Yan; Xu-Hong Duan (Natural Product Research, 2026)

Unraveling antibiotic fate in a highly urbanized estuary: Spatiotemporal patterns, multi-media partitioning, and contaminant prioritization - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Xiao-Ping Huang (Marine Pollution Bulletin, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Pancancer pro-angiogenic atlas unravels tumor-educated pericyte-augmented anti-angiogenic resistance - Yongqiang Zheng; Hui Sun; Zhe Fu; Haojie Chen; Guangyao Cai; Xin Huang; Yi-Qian Pan; Kai Yu; Ping Chen; Zhuoran Liang; Junteng Li; Jiamin Hu; et al. (Science Bulletin, 2026)

A nationwide analysis of hospitalised patients with lower respiratory infections in China: life-stage-specific pathogen spectra, co-detection networks, and sex disparities - Yamin Sun; Min Wang; Tian Qin; Jue Liu; Jiale Yuan; Pei Li; Xinchang Lun; Zhigang Wang; Linghang Wang; Rui Song; Xi Wang; Ronghua Jin; et al. (Science Bulletin, 2026)

Fabrication of Fe-Cu bimetallic particle electrodes from copper slag and biochar for enhanced levofloxacin degradation: Performance, mechanism, and toxicity assessment - Jiao Wei; Linjin Li; Guangfei Qu; Rui Xu; Junyan Li; Yingying Cai; Minghua Chen; Xinxin Liu; Xiaofei Li; Changyi He; Siqing Lu (Process Safety and Environmental Protection, 2026)

Tectonically driven erosion with climatic modulation across the southern Tibetan Plateau: Insights from 10Be erosion rates - Jia-Qi Sun; Jin-Gen Dai; Xu Han; Matthew Fox; Guang-Sheng Ren; Zhi-Cheng Yu; Bo-Rong Liu; Xiang-Rui Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The synergistic effect and underlying mechanism of bimetal and its support in cobalt‑lanthanum doped palygorskite-based catalyst for norfloxacin removal through activating persulfate - Ye Li; Jia-Hang Liu; Bai-Hang Zhao; Xu-Ming Liu; Rui-Xuan Liu (Journal of Water Process Engineering, 2026)

AI-driven monitoring strategy optimization for nutrient-polluted groundwater in a desert site in Northwest China - Yuting Yan; Yu Liu; Baocai Tong; Jinsheng Wang; Rui Zuo; Yuyu Wan; Yuanzheng Zhai; Xu Han (Journal of Hydrology, 2026)

Environmental cadmium drives placental senescence and fetal growth restriction via activating CLPP-dependent mitochondrial stress - Rui Pan; Jin Zhang; Lan-Lan Wu; Cheng-Fang Sun; Xin-Xin Zhang; Yu-Xi Wu; Xu-Ai Yin; Ye-Xin Luo; Si-Ting Liu; Zi-Jian Bao; Wei Chang; Ling-Li Zhao; et al. (Journal of Hazardous Materials, 2026)

Legume-rice rotation improves soil quality index, ecosystem multifunctionality and soybean yield in saline-alkali soils of the Yingbei Plain - Bangyan Zhang; Xiaoli Zhang; Fangdi Chang; Wangsuo Liu; Jinmin Wu; Rui Bu; Tao Zhang; Panting Liu; Jiahao Zhang; Xing Xu; Bin Wang (Journal of Environmental Management, 2026)

The impact of ultra-high pressure processing on crayfish tropomyosin allergenicity and microstructure preservation: Insights into texture and flavors - Rui Liu; Yang Guo; Xuening Yu; Wensi Xu; Xiaoyang Liu; Dayong Zhou (Food Chemistry, 2026)

Ultrasound-driven structural and functional modifications of grape seed protein revealed by power- and duration-dependent experiments - Ying-Yang Liu; Da-Rui Tang; Shi-Ling Wang; Wei-Wei Li; Jun-Wei Xu; Lian-Bing Lin; Yu-Hang Jiang; Qi-Lin Zhang (Food Hydrocolloids, 2026)

Nano-SiO2-doped PVDF piezoelectric ultrafiltration membranes: Synergistic enhancement of antifouling performance via in situ microvibrations and hydrophilic optimization - Haijun Gao; Linjin Li; Guangfei Qu; Rui Xu; Junyan Li; Yingying Cai; Minghua Chen; Xinxin Liu; Xiaofei Li; Changyi He; Jiao Wei (Desalination, 2026)

Lymph node–targeting GM-CSF vesicles produced in situ by ultrasound-activated bacterial factories for enhanced immunotherapy - Yue Yuan; Beibei Zhang; Shaobo Duan; Ruiqing Liu; Juan Zhang; Rui Zhang; Qi Zhou; Linlin Zhang; Xiaoxia Xu; Zesheng Li; Yuanyuan Liu; Xiaoxiao Li; et al. (Chemical Engineering Journal, 2026)

Response of anaerobic ammonium oxidation granular sludge to acute GenX exposure: Performance, microbial responses, and mechanistic insights - Xu-Ming Liu; An-Dong Zhao; Bai-Hang Zhao; Lei-Yue Wu; Rui-Xuan Liu; Peng-Biao Jia (Chemical Engineering Journal, 2026)

Bilayer encapsulation strategy enabled ultra-stretchable electronic skin for human-machine interaction - Miao Kong; Yuxin Chen; Shengwei Gao; Xue Wang; Jiaxin Zhuang; Panqi Huang; Zifan Li; Xu Wang; Zilin Wang; Yuqing Zhang; Ji Cheng; Ruiqi Guo; et al. (Chemical Engineering Journal, 2026)

Spatial and environmental niche differentiation facilitates sympatric macaques' coexistence in montane-canyon landscapes: Implications for conservation - Wei Zhou; Yuan Wang; Deyan Ge; Qisen Yang; Gang Song; Jilong Cheng; Tian Tian; Yu Zhang; Jinbo Xu; Ying Liu; Weibo Wang; Xiaochuan Wang; et al. (Biological Conservation, 2026)

Enhancing the spatio-temporal resolution of urban PM2.5 mapping via large-scale mobile monitoring data and machine learning - Rui Xu; Dawen Yao; Ruhui Cao; Yixin Fu; Ting Gan; Yonghong Liu (Atmospheric Pollution Research, 2026)

Correction to: Puerarin alleviates myocardial ischemia-reperfusion injury by enhancing FUNDC1-mediated mitophagy - Na Feng; Anhua Zhang; Lingling Yao; Jie Tang; Min Lu; Dandan Shi; Zhuoran Zhu; Rui Liu; Jun Chen; Xinwen Min; Handong Yang; Hao Xu; et al. (Molecular and Cellular Biochemistry, 2026)

Heterogeneity of REE distribution revealed by rare-earth phosphate minerals in Chang’e-6 lunar soil - Zhenhao Hu; Rui Li; Jingwen Liu; Yang Li; Tao Chen; Qinglong Yu; Xi Wang; Baochen Yang; Jingyan Xu; Xiongyao Li; Jianzhong Liu; Ziyuan Ouyang (Acta Geochimica, 2026)

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Robust under-canopy navigation path extraction for collaborative harvesting robots using semi-supervised UniMatch V2 segmentation enhanced by edge-contour keypoint clustering - Rui Su; Cheng Liu; Zhentao Zhu; Ling Wang; Xu Mao; Lei Gao; Du Chen (Computers and Electronics in Agriculture, 2026)

Dexmedetomidine regulates fatty acid oxidation through the AMPK/PGC-1α/CPT1A pathway to mitigate renal ischaemia-reperfusion injury - Cong-Li Zhang; Yan Yan; Ke Wang; Jun-Jie Ma; Wen-Jun Xu; Gang Liu; Xing-Chun Zhu; Zhi-Gao Zhu; Hao-Feng Ding; Zi-Rui Ke; Kai Yao; Fang-Tian Fan; et al. (Toxicology and Applied Pharmacology, 2026)

Upcycling alumina industrial solid waste into vanadium disulfide anode materials for lithium-ion batteries - Runxin Zhang; Xuesong Li; Yuhan Wu; Feng Liu; Weishan Li; Pengfei Wang; Laishi Li; Fa-Nian Shi; Rui Xu; Yusheng Wu (Resources, Conservation and Recycling, 2026)

Mutual information and adaptive sparse learning for long term closed loop prediction of ship manoeuvring - Rui Tian; Xiufeng Zhang; Haitong Xu; C. Guedes Soares; Xiuwen Liu (Ocean Engineering, 2026)

Experimental study on the wave mitigation characteristics of a grid-type flexible-membrane breakwater under regular waves - Chuan-Rui Li; Jing-Ping Wu; Ming-Liang Cai; Jun-Ao Kang; Chang-Zhe Chen; Hong Fan; Chen-Xia Liu; Shi-Yu Yang; Zi-Wen Xu (Ocean Engineering, 2026)

System dynamics modeling and characteristic analysis of wave glider with flexible umbilical cable in longitudinal profile - Shaoyu Shi; Weixin Zhou; Yanhui Ai; Rui Xu; Zifeng Shi; Xingran Li; Jingxi Liu (Ocean Engineering, 2026)

Data-driven ship manoeuvring modelling for long-term trajectory prediction using the progressive optimised identification framework - Rui Tian; Xiufeng Zhang; Haitong Xu; C. Guedes Soares; Xiuwen Liu; Zhan Cheng (Ocean Engineering, 2026)

Self-supported cube-like Cu nanoparticles with in-situ growth for efficient CO2 electroreduction to hydrocarbons - Peijun Li; Weicong Xu; Xing Wang; Chao Liu; Anze Ning; Qingwen Chen; WulejiasiI Aerxin; Tao Li; Haowei Huang; Rui Xiao (Journal of Environmental Chemical Engineering, 2026)

Defect-engineered nitrogen-doped carbon from tannic acid for highly efficient peroxydisulfate activation via nonradical pathways - Rui Luo; Tong Yu; Kexin Tai; Xiaoju Wen; Zongtang Liu; Binbin Qian; Qihui Xu; Haijiao Xie; Xiankun Wu (Journal of Environmental Chemical Engineering, 2026)

Copper nanoparticles enhance azo dye decolorization by Shewanella putrefaciens CN32: enhanced effect and underlying mechanisms - Bai-Hang Zhao; Rui-Xuan Liu; Bing-Lin Zhang; Xin-Yu Zhang; Xu-Ming Liu (Journal of Environmental Sciences, 2026)

Structural characterization and functional properties of a mussel peptide-Galactooligosaccharide Maillard conjugate (MPGZn) as a dual-activity zinc chelator and antioxidant for zinc deficiency mitigation - Xuening Yu; Rui Liu; Yuewen Xu; Xiaoyang Liu; Yoshimasa Nakamura; Dayong Zhou (Food Chemistry, 2026)

Comparative study on the changes of triacylglycerol lipolysis products and fatty acid bioaccessibility of four dietary lipids with varying degrees of unsaturation using in vitro digestion model - Yanjun Guo; Zhan Ye; Wei Yang; Rui Xu; Yahui Gao; Yuanfa Liu (Food Bioscience, 2026)

Food-derived inositol derivatives mitigate high-fat diet-induced adiposity by attenuating inflammation and promoting adipocyte browning in mice - Xiaochen Guo; Mengjie Xu; Linlin Liu; Qinghui Lin; Rui Gao; Ruoxuan Xu; Wei Yu; Zhongmei Liang; Pengfei Wu; Zehan Dong; Zhen Xie; Nan Meng; et al. (Food Bioscience, 2026)

Identification of potential virulence sites of IHNV G protein and its impact on pathogenicity and immunogenicity of IHNV in rainbow trout (Oncorhynchus mykiss) - Guangqing Wu; Rui Ao; Yulu Ma; Yanxue Shi; Xueting Guan; Gefeng Xu; Xinjia Lv; Min Liu (Fish & Shellfish Immunology, 2026)

Development of anti-CD4-1/CD8β monoclonal antibodies and spatiotemporal immune profiling of response to live attenuated IHNV in rainbow trout (Oncorhynchus mykiss) - Shuaibo Li; Yulu Ma; Rui Ao; Dandan Zhao; Xueting Guan; Gefeng Xu; Xinjia Lv; Min Liu (Fish & Shellfish Immunology, 2026)

Drivers of reduction in PM2.5 concentrations and related health risks in China from 2013 to 2023 - Fenfen Zhang; Rui Liu; Mei Wan; Yanning Zhang; Yueqi Jiang; Zhaoxin Dong; Qian Song; Lyuyin Huang; Qingru Wu; Litao Wang; Jiayu Xu; Shuxiao Wang (Environmental Pollution, 2026)

Hydrophobization engineering in nitrile hydratase-nicotinamidase cascade system: Promoting multi-tunnel formation for enhanced niacin biosynthesis - Yinbiao Xu; Rui Wang; Chaofan Li; Yu Liu; Xinyue Zhang; Hao Fu; Zongda Chen; Pei Zhou; Yang Sun; Hua Li; Yupeng Liu (Chemical Engineering Journal, 2026)

Development and validation of a Mn/MOF-808 based colorimetric platform for rapid and reliable on-site monitoring of iodide in marine environments - Yi-Ting Chen; Xiao-Jun Dai; Xi- Qing Xu; Pei Liu; Wen-Ge Zhang; Wen-Rui Zhang; Shu-Xuan Li; Peng Wang; Chun-Hui Gong; Yi Yang (Analytica Chimica Acta, 2026)

Enhancing photosynthesis and stress tolerance of the cyanobacterium Nostoc sphaeroides by adaptive laboratory evolution via dry-wet cycles - Zhen Chen; Rui Liu; Yu-Qing Peng; Zhang-Zhuo-Ya Wang; Yong-Qi Yin; Sheng Du; Yu-Jie Jin; Kui Xu; Fei-Fei Li; Wei-Zhi Li; Shan Zhang; Hua-Hua Yue; et al. (Algal Research, 2026)

Post-fire vegetation recovery dynamic monitoring by eliminating vegetation phenology effects from the multi-temporal coherence of Sentinel-1 InSAR - Age Shama; Rui Zhang; Xu He; Junye He; Zhihan Yang; Hongsheng Zhang; Jie Chen; Lei Zhao; Yuchun Zhang; Guoxiang Liu (Agricultural and Forest Meteorology, 2026)

Exposure to per- and polyfluoroalkyl substances and risk of reproductive system cancers: A systematic review and meta-analysis - Xin Liu; Zhihong Lv; Zixiang Huang; Rui Sun; Dingyu Zhu; Pengcheng Xu; Yiquan Xiong; Xiaowei Guo; Yaxuan Ren; Junhua Zhou (Journal of Environmental Health Science and Engineering, 2026)

Muscone Exerts Rapid Antidepressant Effects Through Modulating Glutamatergic Neural Transmission in the Anterior Cingulate Cortex Against Peripheral Inflammation-induced Depression - Xiaoyun Qiu; Xiaojie Zhang; Yuanzhi Yang; Minjuan Sun; Xiaoli Da; Jiaying Liu; Rui Wang; Jingjia Liang; Xuhong Jiang; Gang Tian; Qiyuan Shan; Yu Du; et al. (Neuroscience Bulletin, 2026)

Inhibiting hydrolytic enzyme activity and slowing carbohydrate digestion using lotus seed epicarp phenolic extracts - Congcong Wang; Rui Chen; Lingxiao Gong; Hong Xu; Jie Liu; Huijuan Zhang (Natural Product Research, 2026)

Puerarin alleviates myocardial ischemia-reperfusion injury by enhancing FUNDC1-mediated mitophagy - Na Feng; Anhua Zhang; Lingling Yao; Jie Tang; Min Lu; Dandan Shi; Zhuoran Zhu; Rui Liu; Jun Chen; Xinwen Min; Handong Yang; Hao Xu; et al. (Molecular and Cellular Biochemistry, 2026)

Cooling energy demand for maintaining frozen wall thickness in artificial ground freezing - Xu Li; Rui-ming Li; Xiao-kang Li; Shuang Liu; Zheng Yang (Tunnelling and Underground Space Technology, 2026)

A numerical study of damage evolution and crack propagation in backfill bodies of high-temperature thermal energy storage cavities in mines - Rui Zhan; Bo Zhang; Lang Liu; Chao Huan; Huisheng Qu; Huicong Xu; Jin Zhang; Hongjun Xi (Tunnelling and Underground Space Technology, 2026)

Chang’e-6 lander reveals local hour-scale temporal variations in lunar surface water - Honglei Lin; Heng-Ci Tian; Sheng Gou; Wei Yang; Jinning Li; Li Liu; Kai Fan; Sen Hu; Rui Xu; Zhiping He; Yong Wei; Yangting Lin (Science Bulletin, 2026)

Ship manoeuvring motion modelling based on dual-criterion feature selection and data augmentation - Rui Tian; Xiufeng Zhang; Haitong Xu; C. Guedes Soares; Xiuwen Liu (Ocean Engineering, 2026)

A preliminary assessment of ocean wave parameter retrieval and wave energy estimation using spaceborne BDS-R data - Jinwei Bu; Shuhui Liu; Shunshuang Xu; Hui Yang; Tongsu Xiang; Xin He; Yuhang Jiang; Rui Li (Ocean Engineering, 2026)

Shift in orbital-scale climate response under the coupling of ice sheet and monsoon during the Late Oligocene: Sedimentary records from the East China Sea Shelf Basin - Yingkun Cui; Fujie Jiang; Xianke He; Yichen Liu; Wenji Wang; Rui Zhang; Yinghui Liu; Zhuo Li; Zhenguo Qi; Bo Xu; Hang lv; Jiming Shi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Effective sequestration of phosphate by ultrasmall hydrated Zr(IV) oxide nanoparticles confined inside the PEI-crosslinked chitosan beads - Rui Ma; Xinjie Cui; Youyi Liu; Qianhui Xu; Weiwei Wang; Guangze Nie (Journal of Environmental Sciences, 2026)

Microbial distribution and nitrogen transformation under groundwater table fluctuations: Insights from the vadose zone–saturated aquifer - Shida Zheng; Chengzhi Wang; Xin Liu; Donghui Xu; Shufang Wang; Tianfei Chen; Jinsheng Wang; Guanlan Wu; Rui Zuo (Groundwater for Sustainable Development, 2026)

Pea protein isolate-quercetin covalent complexes: Structure, functionality, and molecular mechanisms underlying emulsion stability - Khubaib Ali; Mingze Xu; Qing Yin; Peipei Yin; Tianhao Zhu; Chang Liu; Rui Sun; Shixue Wu; Yixue Shi; Nadia Niaz; Mangang Wu (Food Chemistry, 2026)

Mechanism and optimization of NaCl removal from soy sauce residue using low pressure superheated steam drying: Role of condensation and moisture migration - Xin Xu; Jian-Bo Liu; Jia-Cheng Guo; Zhi-Hong Xing; Rui-Fang Wang; Qing Xu (Food Chemistry, 2026)

Fabrication and physicochemical characterization of SPI-gallic acid-guar gum ternary complexes: Insights into covalent bonding and structural tunability - Mingze Xu; Chen Gu; Khubaib Ali; Peipei Yin; Chang Liu; Rui Sun; Rui Liu; Qingfeng Ge; Hai Yu; Mangang Wu (Food Chemistry, 2026)

Triterpenoids in the leaves of Schisandra chinensis (Turcz.) Baill. treated AD by inducing mitophagy through activation of MCL-1 - Shi-Qi Xu; Xin Meng; Xu Yang; Gang-Tao Bu; Si-Yi Wang; Meng-Meng Li; Yi-Qiang Zhang; Zhi-Chao Hao; Wei Guan; Qi-Shan Chen; Li-Li Zhang; Rui-Yan Wu; et al. (Food Bioscience, 2026)

Release kinetics and environmental risks of TCPP from polyurethane foam microplastics: Insights from artificial seawater to natural estuarine water - Shan-Shan Yao; Yu-Han Xie; Zhi-Yan Wang; Shan Liu; Rui Hou; Lang Lin; Yu Zhong; Xiao-Ping Huang; Heng-Xiang Li; Xiang-Rong Xu (Environmental Pollution, 2026)

Erratum to “Evidence of shallow subsurface ice at Tianwen-1 landing site” [Earth and Planetary Science Letters 678 (2026)/EPSL 119832] - Xindong Meng; Ling Zhang; Yi Xu; Iraklis Giannakis; Roberto Bugiolacchi; Jiannan Zhao; Xiaoping Zhang; Qiquan Yang; Rui Chen; Renrui Liu; Xiaoting Xu; Huaqing Cao; et al. (Earth and Planetary Science Letters, 2026)

Data-driven discovery of high-performance surface passivators for efficient and stable perovskite solar cells - Feiyi Zhou; Zeyu Wang; Shangshang Zhao; Xu Zhang; Qingyue Guo; Runze Dai; Fanxiang Meng; Huajie Lyu; Jun Wan; Yi Dong; Zhe Jin; Shanqing Yu; et al. (Chemical Engineering Journal, 2026)

Perfusion process-oriented metabolic engineering enhances 1,3-dihydroxyacetone production efficiency in Gluconobacter thailandicus - Yang Sun; Zilong Hu; Yuwei Shan; Rui Wang; Tang Liu; Kuiqi Jin; Qingxuan Miao; Cheng Ye; Jianqi Nie; Daiyin Zuo; Yinbiao Xu; Hua Li; et al. (Chemical Engineering Journal, 2026)

Sinomenine ameliorates experimental autoimmune neuritis by suppressing pro-inflammatory immune components and restoring immune balance - Yan-Mei Gong; Zhen-Lin Liu; Si-Miao Li; Yi-Fan Wei; Guo-Hui Gao; Rui-Qi Xu; Xue-Min Li; Yu-Dong Liu; Rui-Sheng Duan; Ying Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Adverse drug events and toxicological mechanisms of esketamine: a study based on US Food and Drug Administration Adverse Event Reporting System and network toxicology analysis - Lu Wang; Rui Xiong; Hengxu Liu; Shipeng Zhang; Ling Xu; Xiaodan Lai (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Green preparation of graphene oxide-incorporated monoliths for pH-controlled protein enrichment and clinical biomarker detection - Xue Zhang; Fenghua Xu; Rui Wu; Huiying Zhang; Yufei Shi; Zhaosheng Liu; Xin Dong (Analytica Chimica Acta, 2026)

Unveiling the “Glycolysis-Lactate-Lactylation” Axis: A Novel Target in Ischemic Cerebrovascular Disease - Yi Xie; Mengmeng Dai; Rui Liu; Ying Li; Hao Yan; Jiacheng Li; Xuantong Liu; Zhiyuan Yu; Shabei Xu; Wei Wang; Xiang Luo (Neuroscience Bulletin, 2026)
Ischemic cerebrovascular disease involves complex interactions between metabolic reprogramming and epigenetic regulation. Recent studies indicate that enhanced glycolysis and lactate accumulation under hypoxic conditions not only maintain cell viability by supplying energy but also participate in disease regulation through lactylation. Lactylation regulates gene expression, immune polarization, metabolic enzyme activity, and angiogenesis through epigenetic remodeling. In ischemic cerebrovascular disease, lactylation exerts dual roles: on one hand, it can induce neuronal death, exacerbate neuroinflammation, and form a vicious metabolic cycle; on the other hand, it can influence immune cell function and gene expression, thereby exerting neuroprotective effects. Accordingly, targeting lactate metabolism or lactylation-modifying enzymes holds considerable therapeutic potential. Nevertheless, the spatiotemporal regulation, synergistic effects, and broader physiopathological implications of lactylation warrant further in-depth investigation. This review systematically summarizes the role of the “glycolysis-lactate-lactylation” axis in the pathogenesis of ischemic cerebrovascular disease, and discusses its potential as a therapeutic target.

Ultra-highly specific and visual detection of Vibrio pathogens in Porphyra using RPA-coupled CRISPR-LbaCas12a-LFD system - Xu-Xu Luo; Hai-Long Huang; Qi-Qin Liu; Hoi-Yan Kwok; Hai-Tao Ma; Hai-Bo Jiang; Rui Yang (Aquaculture, 2026)

Deformation analysis of a deep excavation with a servo control system adjacent to an existing foundation pit: A case study in Shenzhen - Liqiang Xu; Wangrong Li; Leilei Liu; Fan Wu; Zirui Fan; Rui Chen (Tunnelling and Underground Space Technology, 2026)

Corrigendum to ‘Nitric oxide regulates spindle dynamics to modulate the maturation of goat oocytes’ [Theriogenology 2025 Oct 1, (245), 117517] - Rui Xu; Zhi Zheng; Weizhao Bai; Minghui Liu; Sihai Lu; Sha Peng; Menghao Pan; Baohua Ma (Theriogenology, 2026)

Distinct bio-physical responses to wind stress curl and wind power of tropical cyclones in the Arabian Sea - Haihua Liu; Xiuting Wang; Gaopeng Lu; Liang Sun; Rui Liu; Mengyuan Xu; Qi Liu; Youfang Yan (Regional Studies in Marine Science, 2026)

Mechanistic insights into vanillin's inhibitory effects on Fusarium oxysporum induced postharvest disease - Xinlin Liu; Jiakai He; Yahui Cui; Muhammad Muzammal Aslam; Jian Xu; Rui Li; Wen Li (Postharvest Biology and Technology, 2026)

Six-component load reconstruction for offshore wind turbine blades considering deformation-induced additional moments - Baoxuan Wang; Xu Liang; Lizhong Wang; Fangyuan Sheng; Xiang Wang; Yue Chen; Jianwei Zhang; Shengjie Rui; Rui Liu (Ocean Engineering, 2026)

Magmatic source effects on Zircon Eu anomalies: Refining the Late Cretaceous–Eocene uplift of the Gangdese Arc, Southern Tibet - Guang-Sheng Ren; Jin-Gen Dai; Xiang-Rui Liu; Xu Han; Bo-Rong Liu; Jia-Qi Sun (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

SgPAP27b, a purple acid phosphatase, confers aluminum tolerance in Stylosanthes guianensis through membrane lipid remodeling - Jianyu Zhang; Jinhui Lv; Chun Liu; Ranran Xu; Yu Liu; Rui Huang; Rongshu Dong; Pandao Liu; Zhijian Chen (Journal of Hazardous Materials, 2026)

A Cu-based catalytic molecularly imprinted electrochemical sensor on paper for phthalylsulfacetamide detection in environmental water - Shuyan Miao; Jing Zhou; Zhen Xu; Yuting Wang; Rui Liu; Tian Gan (Journal of Environmental Chemical Engineering, 2026)

Changes of intracellular and extracellular organic matter in Microcystis colonies after ultrasonic stress and during recovery cultivation - Jia Liang; Zhipeng Duan; Lei Liu; Chao Xing; Xiao Tan; Jun Sun; Yangxue Xu; Rui Zhu (Journal of Environmental Management, 2026)

Oriented attachment process induced synthesis of nanoscale lanthanum oxyhydroxide hydrogels for efficient phosphate removal - Caigao Zhou; Yuchen Zhang; Xiaolin Zhang; Yanyang Zhang; Shiyun Xu; Jingfu Liu; Rui Liu (Journal of Environmental Sciences, 2026)

Pea protein isolate‑sodium alginate-based plant-based meat analogue: dual crosslinking and molecular insight mechanisms - Khubaib Ali; Chang Liu; Nadia Niaz; Faizan Ul Haq; Mingze Xu; Rui Sun; Tianhao Zhu; Peipei Yin; Mangang Wu (Food Research International, 2026)

A novel dual-mode sensor based on green-synthesized AuNPs and natural nitrogen-doped CQDs for tobramycin detection: enhanced sensitivity and specificity - Qiang Li; Rui-ling Yin; Xing-yi Yang; Yi-xin Xu; Yan-bing Leng; Xin Liu (Food Research International, 2026)

Green fabrication of lactoferrin–Dendrobium officinale polysaccharide–EGCG ternary nanoparticles for enhanced lutein delivery - Xiaoke Peng; Xiaofan Deng; Jianzhong Xu; Jiayi Guo; Rui Zhao; David Julian McClements; Cuicui Ma; Fuguo Liu (Food Bioscience, 2026)

Measurement, prediction, and interpretation of industrial carbon unlocking efficiency - Shuai Feng; Guiwen Liu; Rui Li; Kaijian Li; Liu Chen; Xu Duan (Environmental Impact Assessment Review, 2026)

Abandonment duration shapes reuse strategies and benefits of abandoned cropland in China - Yixin Liao; Chenrui Luo; Xue Wang; Jialin Liu; Xiaoqi Huang; Xinliang Xu; Rui Qin; Yuanwei Qin; Luo Liu (Environmental Impact Assessment Review, 2026)

An earthworm-inspired hydrogel coating for hydration-assisted aqueous lubrication on diverse polymer substrates - Zhi-Guo Wang; Xi Liao; Yong-Jie Dan; Yu-Wei Liu; Yan-Hua Niu; Rui Hong; Ming Cai; Ju-Xiang Gou; Jia-Zhuang Xu; Zhong-Ming Li; Ka Li (Chemical Engineering Journal, 2026)

Inhibiting NAT10 suppresses hepatocellular carcinoma progression by reducing Nrf2 mRNA stability and increasing oxidative stress - Wei Gu; Ziyi Ren; Jie Gao; Ziyi Shen; Yuanhui Wang; Luanqi Xu; Rui Qian; Qinyi Miao; Yifan Wu; Xiaomeng Hu; Yan Wu; Wei Liu; et al. (Chemico-Biological Interactions, 2026)

The biphasic regulatory effect of adenosine A2B receptor in ischemic brain injury and its therapeutic potential - Xu Rui; Wang Xi; Li Mengzhu; Su Peiwei; Liu Mudong; Zhu Chao; Luo Wanyu; Zhao Haijun (Purinergic Signalling, 2026)

Twelve-year organic substitution fertilization mitigates microbial nutrient limitation and enhances soil carbon pool stability in a rubber plantation - Wenxian Xu; Yingying Zhang; Wenjie Liu; Congju Zhao; Ashar Tahir; Chuan Yang; Xinwei Guo; Rui Sun; Xiangshuai Yan; Huifang Yuan; Qiu Yang; Zhixiang Wu (Plant and Soil, 2026)

A deep learning multi-branch network method for landslide susceptibility mapping in the Sichuan-Tibet transportation corridor - Jichao Lv; Ruikai Hong; Xin Bao; Renzhe Wu; Xu He; Guoxiang Liu; Rui Zhang (Bulletin of Engineering Geology and the Environment, 2026)

From SPP to RTK: promoting the satellite navigation potential of acoustically excited antenna - Shangyang Wang; Yifan Fu; Rui Hu; Du Li; Bing Xu; Ruofan Liu; Yinuo Song; Junru Li; Bin Fang; Wenkui Lin; Zhongming Zeng; Xiangwei Zhu (GPS Solutions, 2026)

Quantitative analyzing method for floor acceleration amplification factor based on instrumented buildings - Tao Wang; Rui Pan; Guoshan Xu; Liyan Meng; Jisheng Liu (Earthquake Engineering and Engineering Vibration, 2026)

Differential impacts of tea-woody plant intercropping patterns on the status of soil organic carbon, macronutrients and metallic nutrients - Dan Wang; Yuhua Liang; Benjuan Liu; Rui Cao; Shiquan Chen; Hanhui Xu; Wanqin Yang (Agriculture, Ecosystems & Environment, 2026)

Coupling data assimilation and machine learning to improve land surface conditions and near-surface temperature and humidity forecasts - Xinlei He; Shaomin Liu; Tongren Xu; Fei Chen; Zhitao Wu; Ziwei Xu; Xiang Li; Rui Liu (Agricultural and Forest Meteorology, 2026)

Spatial Distribution Characteristics of Secondary PM2.5 in Beijing-Tianjin-Hebei Region Based on Time Series Decomposition - Qing Yao; Jing Ding; Zi-rui Liu; Xu Yang; Ying-xiao Tang; Zi-yin Cai; Su-qin Han (Aerosol Science and Engineering, 2026)

Construction and Simulation of Global Land Surface Microwave Emissivity Atlas Using FY-3D Satellite Data - Yonghong Liu; Fuzhong Weng; Fei Tang; Yang Han; Qingyang Liu; Rui Li; Yongming Xu; Jun Yang (Advances in Atmospheric Sciences, 2026)

Effect of 6-Month High-Impact and Resistance Exercise on Regional Strength and BMD of Spine: A Clinical Trial Combined with a Finite-Element Study - Pu Duan; Yinxia Nie; Shizhong Liu; Xiaoyu Xia; Rui Xu; Simin Li; Vadim V. Silberschmidt; Lin Meng; Juan Du; Dong Ming (Annals of Biomedical Engineering, 2026)

Raccoon dog parvovirus NS1 protein antagonizes type I interferon signaling by promoting selective autophagic degradation of IRF3 - Wen-yu Cao; Rui-qi Wang; Jin-yang Zheng; Ping Ma; Bo Hu; Cheng-qi Zhang; Ya-jie Sun; Jia-jia Liu; Ding-rui Guo; Zi-han Zhao; Xin Cao; Xue Bai; et al. (Veterinary Microbiology, 2026)

Rubber-based agroforestry systems enhancing soil carbon sequestration through improved soil aggregate stability - Wenxian Xu; Wenjie Liu; Bo Song; Yingying Zhang; Ashar Tahir; Yumiao Cao; Changgeng Kuang; Xinwei Guo; Rui Sun; Xian Zhang; Qiu Yang; Zhixiang Wu (Soil and Tillage Research, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

Genome-wide identification of the laccase gene family in wheat (Triticum aestivum L.) during Fusarium pseudograminearum infection - Li-Yu Chen; Yi Diao; Ju-Hong Ma; Xiang-Xue Zhang; Rui Li; Yan Liu; Hong-Tao Tang; Zhi Wang; Sha Gao; Rui-Huan Xu; Zhen-sheng Kang; De-Jun Han; et al. (Plant Science, 2026)

Oxidized- and hydroxylated-pennogenin saponins from the rhizomes of Paris fargesii and their hemostatic activity - Ling-Ling Yu; Lijin Jiao; Yan-Xi Li; Xu-Hong Li; Shan-Shan Ling; Long-Gao Xiao; Rui-Qi Liu; Wei Ni; Huan Yan; Yunheng Ji; Hai-Yang Liu (Phytochemistry, 2026)

Harvesting organic chelated calcium from sewage sludge for plant germination by alkaline-thermal treatments - Rui Liu; Ying Xu; Jiaqi Gao; Hui Geng; Liang Song; Yue Zhang; Xiaohu Dai (Journal of Environmental Sciences, 2026)

Drivers of CO2 and CH4 fluxes from shallow lakes and prediction based on climate factors under global warming - Zhentao Wu; Hui Liu; Fan Yang; Rui Ran; Huimin Yu; Haonan Xu; Danyun Chen; Geng Wang; Xiaobing Pang (Journal of Environmental Sciences, 2026)

Automated microseismic classification in deep coal seams: Application to stress redistribution and fault reactivation in the Dongtan coal mine - Jinhai Liu; Rui Xu; Kai Zhan; Jiajun Chen; Guangming Li; Chao Kong (Journal of Applied Geophysics, 2026)

Activation of the Nrf2-Keap1 pathway is associated with NAC-mediated alleviation of nitrite-induced oxidative and endoplasmic reticulum stress and apoptosis in Marsupenaeus japonicus - Yexin Lei; Rui Xu; Jinlong Zhan; Jianyong Liu (Fish & Shellfish Immunology, 2026)

Evidence of shallow subsurface ice at Tianwen-1 landing site - Xindong Meng; Ling Zhang; Yi Xu; Giannakis Iraklis; Roberto Bugiolacchi; Jiannan Zhao; Xiaoping Zhang; Qiquan Yang; Rui Chen; Renrui Liu; Xiaoting Xu; Huaqing Cao; et al. (Earth and Planetary Science Letters, 2026)

H₂-rich syngas from synergistic steam gasification of biomass with spent LIB cathodes: Catalytic kinetics and metal recovery - Ran Jiao; Lijie Sun; Bowen Li; Xinran Zhou; Yifei Xu; Yu Chen; Fenglei Qi; Xiaohao Liu; Rui Diao; Zhenting Zha; Peiyong Ma (Chemical Engineering Journal, 2026)

Interfacial environment modulation by nanoneedle-shaped polyaniline for enhanced hydrogen isotope separation by water electrolysis - Rui Li; Guoyu Li; Penghui Xiong; Yuhan Wu; Ruidong Liu; Hang Zhong; Yue Yao; Xin Xiang; Wenhua Luo; Jingsong Xu (Chemical Engineering Journal, 2026)

Integrating Machine Learning and Petrophysical Data for 3D Ore Body Modeling: A Case Study of the Bayan Obo Deposit - Shupeng Lu; Ya Xu; Rui Guo; Song Huang; Qianwen Zhang; Yonggang Zhao; Yun Liu; Jian Wang; Liang Zhao (Pure and Applied Geophysics, 2026)

The microbial mechanism of the impact of grazing degradation on the soil multifunctionality of the hummock wetland on the riverscape - Xiaoai Cao; Huamin Liu; Rui Zhang; Yunhao Wen; Shan Jiang; Zhichao Xu; Lu Wen; Yi Zhuo; Dongwei Liu; Ke Yu; Lixin Wang (Applied Soil Ecology, 2026)

Tracking the eyes to track decline: Global eye movement similarity as a novel neuropsychological marker of mild cognitive impairment - Zhan Wang; Hong-Zhou Xu; Fang Fang; Xue-Rui Peng; Ying-Chen Liu; Zhi-Jun Zhan; Jing Yu (GeroScience, 2026)

Mechanism of baicalein from Wudang Mountain Scutellaria baicalensis Georgi. against atopic dermatitis based on network pharmacology, transcriptomics and in vitro experimental validation - Liu Tang; Gang Liu; Dan Li; Tianshuai Wang; Chun Wang; Guangwen Luo; Rui Peng; Xu Cai (Natural Product Research, 2026)

Identification of novel B-cell neutralizing epitopes in goose Astrovirus type 2 - Shichao Yuan; Rui Fu; Bangfeng Xu; Wenqing Wang; Huamao Ding; Xue Pan; Chunxiu Yuan; Qinfang Liu; Zhifei Zhang; Qiaoyang Teng; Xiaona Shi; Minghao Yan; et al. (Veterinary Microbiology, 2026)

Seismic resilience assessment of water treatment plants considering the damages and interdependencies of internal facilities - Benwei Hou; Rui Jia; Bin Wu; Liang Liu; Chengshun Xu (Soil Dynamics and Earthquake Engineering, 2026)

Efficient conversion of carbohydrates in biomass into furan-based products over a carbon-nitrogen co-doped boron phosphate solid acid catalyst - Wang Zhao; Haonan Xu; Rui Liu; Shufang Wu; Weiqi Wei (Sustainable Chemistry and Pharmacy, 2026)

Zinc finger protein ZNF638 in brown fat deteriorates type 1 diabetes via retinol binding protein 4 - Meiyao Meng; Shuang Liu; Yinzhao Zhong; Jingyi Hu; Lijun Zhu; Jin Qiu; Rui Wang; Yuan Luo; Yingwen Wang; Wenhao Zhou; Guangyu Shan; Zhenyu Du; et al. (Science Bulletin, 2026)

Predicting and classifying deoxynivalenol in wheat flour using ATR-FTIR spectroscopy and explainable machine learning - Jiajun Liu; Kebing Yao; Chen Chen; Dongsheng Li; Dengan Xu; Rui Guo; Weicheng Yao; Yao Deng; Wenting Xue; Qinyan Wu; Tao Li; Xinyao He; et al. (Journal of Hazardous Materials, 2026)

Tracking food-nutrition-carbon footprint evolutions and driving forces of China's megacity: insights from dietary transitions in Chengdu - Xin Xiong; Qin Liu; Pengbo Du; Liwei Yang; Qiuyun Xu; Xinqing Li; Rui Zhao (Journal of Cleaner Production, 2026)

Novel green ternary deep eutectic solvents for efficient extraction of nitrogen compounds from oil - Yingying Zuo; Rui Zhou; Xiaohang Yang; Jian Wang; Xu Liu; Yushan Li; Zhengqi Liang; Boxing An; Fengjuan Niu (Journal of Environmental Chemical Engineering, 2026)

Cyclic loading test on seismic shear behavior of CFST column to USCC beam joints with T-shaped interior diaphragms - Jichun Liu; Rui Cheng; Yuhang Wang; Chao Hu; Xing Xu; Yusen Liu (Engineering Structures, 2026)

Isothiazolinone biocide aggravate disinfection-resistant bacterial fouling on reverse osmosis membranes - Yu-Qing Xu; Zheng-Yang Huo; Yuan Bai; Yun Wang; Wen-Long Wang; Hao-Bin Wang; Yu-Jia Gao; Rui-Ning Wang; Chen-Yu Li; Han Liu; Wei E. Huang; Hong-Ying Hu; et al. (Desalination, 2026)

A multi-stimuli-responsive supramolecular polymer from γ-Cyclodextrin and Viologen for dual-mode display and ammonia/amines sensing - Dong-Xue Xia; Chen-Yan Xu; Dan-Xuan Pan; Ming-Fu Ye; Rui-Lian Lin; Jing-Xin Liu (Chemical Engineering Journal, 2026)

Pretreatment sequence of torrefaction and leaching for high–alkali biomass valorization: Focus on elemental migration, mineral evolution, carbon structure and torrefaction mechanism - Bowen Li; Junling Du; Rui Diao; Xu Hu; Cunzhang Yang; Ran Jiao; Fenglei Qi; Zhenting Zha; Xiaohao Liu; Peiyong Ma (Bioresource Technology, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Phosphorus fertilization shapes rhizosphere beneficial microbial communities and soil–plant relations in arid cotton fields of Xinjiang, China - Bin Peng; Shuai Zhao; Cong-Rui Liu; Wen-Xuan Mai; Na Zhou; Ping Zhang; Shu-Ying Wang; Xu Liu; Bao-Zhan Wang; Chang-Yan Tian (Plant and Soil, 2026)

Mitochondria to nucleus/nucleolus migration probe for in-situ and dual-color visualization of MMP alteration and monitoring apoptosis - Mengmeng Wei; Derong Xiang; Yuxuan Zhang; Wuyou Qiang; Jiawei Liu; Jing Xu; Xiaoyan Tang; Qijian Zhang; Zhida Han; Xifeng Yang; Rui Yang (Analytica Chimica Acta, 2026)

Chebulagic acid targets FBXO38 to enhance natural killer cell-mediated anti-tumor immunity in lung adenocarcinoma - Xiwen Hu; Rui Sha; Feiran Yang; Jinwen Chai; Bin Liu; Xiaoqing Xu (Human Cell, 2026)

Diketopiperazines from marine-derived Exserohilum sp. M1-6 - Rui Xu; Jianjian Wang; Changyu Liu; Xuefang Yang; Minjun Chen; Zihan Jin; Shengyan Zheng; Peihai Li; Cong Wang; Shugeng Cao (Natural Product Research, 2026)

Bioaccumulation and trophic transfer of phthalate esters in mangrove food web - Jianan Liu; Yuyan Liu; Siwen Chen; Rui Xu; Haofeng Liu; Zefeng Wang; Xianbiao Lin; Ye Li; Min Liu (Marine Pollution Bulletin, 2026)

Transport behavior of polystyrene microplastics in a simulated groundwater–seawater mixing zone and its reliance on groundwater composition - Jun Xu; Rui Zuo; Jingchao Liu; Jiawei Liu; Ziyi Wu; Zhiwen Wang; Xianyuan Du; Jin Zheng (Journal of Hydrology, 2026)

Multi-load Undersea single-wire inductive power transfer system for sustainable ocean observation - Shui Pang; Jiayi Xu; Yehao Liu; Rui Guo; Chenguang Zhang; Jianyu Lu; Xingfei Li; Hongyu Li (Journal of Cleaner Production, 2026)

Mechanisms of AMF-mediated correlation between nutrient uptake and soil micropatterns in sugar beet plants under rotational and continuous cropping soil environments - Rui Chen; Yonglong Liu; Xinyi Zhang; Gui Geng; Lihua Yu; Yao Xu; Jiahui Liu; Yuguang Wang (Journal of Cleaner Production, 2026)

Deciphering the effects of cascade reservoirs on phytoplankton communities in a karst river: Importance of super-large reservoirs - Jiang Wu; Xiao-Nan Wu; Xiao-Hui Zhao; Xu Han; En-Hang Liang; Rui An; Jia-Ju Liu; Wei-Ling Sun; Nan Xu; Ting Wang (Journal of Environmental Management, 2026)

Grassland soil seed bank responses to grazing exclusion: a global synthesis - Jishuai Su; Lixin Yu; Rui Tian; Wanbing Liu; Ruolin Zhao; Menghan Niu; Zekai Yang; Yi Zhang; Fengwei Xu; Heyong Liu; Yong Jiang (Journal of Environmental Management, 2026)

The significant reduction of extraction time using high-pressurized microwave extraction method for arsenic species from rice - Fa Zhao; Rui Dong; Dawei Xu; Hanshuang Zhang; Wenjiang Yu; Dengyi Lv; Yanming Liu; Min Sun (Food Chemistry, 2026)

Molecular docking-guided enhancement of recombinant antibody affinity for shiga toxin 1B enables sensitive and rapid immunoassay in food matrices - Chunhao Wei; Zheng Zhang; Aihong Wu; Liqiang Liu; Rui Gao; Xinxin Xu; Hua Kuang; Chuanlai Xu; Liguang Xu (Food Bioscience, 2026)

Synergistic surface plasmon resonance effect of Ag and S-scheme heterojunction in Ag/AgBr/Bi24O31Cl10 towards enhanced enrofloxacin removal: Performance, degradation pathways and synergistic mechanism - Xiao-Ju Wen; Qian Zhan; Hongyu Ye; Jing Xu; Binbin Qian; Rui Luo; Xiankun Wu; Zongtang Liu; Zhenghao Fei; Hai Guo (Environmental Research, 2026)

Time-series InSAR with phase gradient stacking and slope-constrained clustering for large-scale landslide detection in the Sichuan-Tibet Region - Jichao Lv; Rui Zhang; Kun Fang; Kun Chen; Age Shama; Ruikai Hong; Xu He; Guoxiang Liu (Engineering Geology, 2026)

Ester-assisted low-temperature interfacial polymerization for nanofiltration membranes: Synergistic regulation of heat and mass transfer - Rui Han; Zhen-Liang Xu; Dianhua Liu; Sun-Jie Xu (Chemical Engineering Journal, 2026)

Interactive effects of polyethylene microplastics and Fe(VI)/S(IV) pretreatment on short-chain fatty acids production from waste activated sludge - Qinqin Cao; Rui Zhou; Muchen Zhu; Haokun Wu; Xianbao Xu; Zhihong Liu; Aijuan Zhou; Xiuping Yue; Jacek Mąkinia (Chemical Engineering Journal, 2026)

Interfacial charge transfer bridge enables high-quality heterojunction for braided coaxial ammonium-ion asymmetric supercapacitors - Jing Xu; Sheng-Jie Wang; Mao-Lan Liao; Zi-Tao Yang; Jia-Peng Hu; Rui-Lai Liu; Jia-Huan Tang; Zhi-Feng Zheng; Yi-Bing Xie (Chemical Engineering Journal, 2026)

ADAM17 Supports Disinhibition of Pre-sympathetic Glutamatergic Neurons Through Microglial Chemotaxis - Jiawei Wang; Zihan Qiu; Yue Han; Hanxue Wu; Miao Yuan; Yan Liu; Huichao Wang; Shenglan Yuan; Dengfeng Gao; Lina Sun; Xingjuan Chen; Eric Lazartigues; et al. (Neuroscience Bulletin, 2026)

Mechanistic Investigation of TSPO-Mediated Dysregulation of Mitochondrial Copper Homeostasis in Microglia and its Role in Perioperative Neurocognitive Disorders - Youli Fu; Jiahe Lian; Yinglong Liu; Yongxin Liu; Zihan Xu; Haoran Fan; Yongliang Zhu; Yingxia Liang; Lina Sun; Rui Zhang (Molecular Neurobiology, 2026)

Changes in litter chemical properties mediate the effects of soil arthropods on the microbial community during litter decomposition in a subalpine forest - Aomiao Wu; Jingru Liu; Rui Yin; Lin Xu; Chengming You; Zhenfeng Xu; Li Zhang; Han Li; Lixia Wang; Sining Liu; Hongwei Xu; Bo Tan (Applied Soil Ecology, 2026)

Automatic Image Co-registration of Carotid Angiography and Intravascular Optical Coherence Tomography Based on Machine Learning Method: A Pilot Feasibility Study - Hui Xu; Jia-Nan Li; Yan Xu; Jun-Ren Ma; Kang Zong; Rui Zhu; Yi-Hui Cao; Peng-Fei Yang; Rui Zhao; Jian-Min Liu (Annals of Biomedical Engineering, 2026)

Computational Investigation of Dicyanoisophorone-Based Fluorophores: Substituent and Site Effects - Yating Ding; Zhengze Zhang; Rui Wu; Ying Xu; Qu Zhang; Zhao Liu; Junqiang Lei (Journal of Fluorescence, 2025)

A novel dual-polarization SAR vegetation index for crop phenology detection - Xin Bao; Rui Zhang; Xu He; Age Shama; Gaofei Yin; Jie Chen; Hongsheng Zhang; Guoxiang Liu; Xianjian Shi (Computers and Electronics in Agriculture, 2025)

Release kinetics and bioaccessibility of heavy metal from antifouling paint particles in simulated digestive fluids: An emerging threat to marine biota - Zhen-Liang Li; Ting-Ting Xu; Shan-Shan Yao; Heng-Xiang Li; Shan Liu; Rui Hou; Lang Lin; Zhi-Xin Ni; Qun Xie; Xiao-Ping Huang; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

Urinary metal mixtures and cataract: Findings from a U.S. population-based study and network pharmacology analysis - Runzi Yang; Jing Li; Rui Liu; Tingting Ren; Nan Wang; Liangyuan Xu; Jianmin Ma (Toxicology Letters, 2025)

Highly selective electrocatalytic CO2 reduction to formate by a dinuclear nickel complex: cooperative catalysis across diverse conditions - Haitao Lei; Fengwang Li; Chengyu Liu; Jun Li; Yabo Wang; Dae-Hyun Nam; Yanwei Lum; Si-Xuan Guo; Yi Xu; Jie Zhang; Wenzhen Lai; Rui Cao (Science Bulletin, 2025)

Value decomposition reinforcement learning-based formation control for multi-USVs with incomplete information - Rui Xiao; Chun Liu; Hongtian Chen; Liang Xu; Youmin Zhang (Ocean Engineering, 2025)

Ship manoeuvring model identification using mutual information clustering with stepwise regression structural optimisation under small-sample constraints - Xiufeng Zhang; Rui Tian; Haitong Xu; Xiuwen Liu; C. Guedes Soares (Ocean Engineering, 2025)

Whole-genome resequencing unveils the phylogeographic coevolution of Oncomelania hupensis with Yangtze River dynamics in China - Lei Duan; Fang Luo; Qin Liu; Shen Chen; Xia Tian; Wen-Wen Lv; Lu He; Zi-Rui Ren; Jing Xu; Xiao-Nong Zhou; Shi-Zhu Li; Shan Lv; et al. (Molecular Phylogenetics and Evolution, 2025)

Factors affecting micro(nano)plastic release during intravenous therapy: Direct blood exposure - Haoming Xu; Penghui Li; Yujian Lai; Sujuan Yu; Rui Liu; Guomao Zheng; Bintian Zhang; Qian Sun; Jingfu Liu (Journal of Hazardous Materials, 2025)

Response of microbial communities in capillary zone to toluene natural attenuation under leaching/capillary rise - Jiawei Liu; Rui Zuo; Guanlan Wu; Qiao Li; Donghui Xu; Tianfei Chen; Jingchao Liu; Ziyi Wu; Jinsheng Wang (Journal of Hazardous Materials, 2025)

Study on intracellular detoxification mechanisms of Aspergillus sydowii under cadmium stress - Longteng Zhi; Yutong Liu; Rui Xu; Jingyan Guo; Hongyan Yu; Yue Teng (Journal of Environmental Management, 2025)

Mechanism of TGase-induced oyster peptide-chitosan oligosaccharide glycosylation and amelioration effects of its zinc complex on zinc deficiency-associated neuron damages and oxidative stress - Xuening Yu; Rui Liu; Yuewen Xu; Ningning Pan; Xiaoyang Liu; Yoshimasa Nakamura; Dayong Zhou (Food Research International, 2025)

Comparative analysis on antioxidant capacity, immunity and histopathological changes of largemouth bass (Micropterus salmoides) in response to mono- or co-infection with Aeromonas veronii and Nocardia seriolae - Gaofeng Cheng; Nengbin Zhu; Ruiping Xu; Eakapol Wangkahart; Lin Zhang; Lihe Liu; Rui Wang; Zhen Xu; Weiguang Kong; Hongsen Xu (Fish & Shellfish Immunology, 2025)

Soil pH and organic phosphorus co-shape the diversity and assembly processes of arbuscular mycorrhizal fungal community in subtropical broadleaved forests - Rui Xu; Zhucheng Yu; Yang Liu; Yidan Liu; Xingcong Ma; Xiaomin Ma; Wenhao Jin; Yongfu Li; Junhui Chen; Hua Qin (European Journal of Soil Biology, 2025)

Airway exposure to microplastics: Potential mechanisms from epithelial barrier damage to the development of allergic rhinitis - Xu Zhang; Mengyuan Liu; Zhiqiang Zhang; Xinyu Huang; Daoming Bai; Rui Yang; Maohua Wang; Peng Wang; Chunping Yang (Environmental Research, 2025)

Recent advances in manganese-based materials for water remediation: Multipollutant adsorption and catalytic oxidation - Hanghang Wang; Guangfei Qu; Yingying Cai; Chenyang Yin; Yaxin Tian; Rui Xu; Xinxin Liu; Minjie He; Changyi He; Jiao Wei (Environmental Research, 2025)

Atmospheric and room-temperature plasma mutagenesis enhances the tolerance of Arthrospira platensis to photoinhibition and high-CO2 levels - Ruolan Yuan; Chunli Yu; Rui Xu; Jin Liu; Lina Zhou; Shengxi Shao; Jun Qian; Jingjing Li; Peilun Xu; Wenguang Zhou (Chemical Engineering Journal, 2025)

Recent advances and perspectives in coordination polymer-based fluorescent sensors for vitamin detection - Zi-Hao Zhao; Zhi-Wei Liu; Xin-Rui Xu; Qian-Yu Yang; Zhao-Yang Tong (Chemical Engineering Journal, 2025)

Upcycling PET waste into carbon quantum dots as flame retardant of PET for closed-loop recycling - Jianfei Wei; Guocong Ma; Yaoyao Tang; Jing Zhang; Gaoling Jin; Chaohui Ma; Linhan Bing; Zhiguo Zhu; Zhenfeng Dong; Puzhen He; Ruichen Zhou; Rui Wang; et al. (Chemical Engineering Journal, 2025)

Structural and physicochemical characterization of plant-derived galactomannans: revealing promising substrates for mannooligosaccharides production - Shujun Hou; Yijin Zhang; Rui Yang; Wei Xu; Huanli Wang; Zhijin Zhang; Botao Liu; Guiyao Dai; Ting Wang; Pengfei Li; Liang He; Ke Wu; et al. (Carbohydrate Polymers, 2025)

Integration of transcriptome and metabolome analysis reveals that alternative splicing of TT8 modulates anthocyanin biosynthesis in postharvest blood orange stored at moderate temperature - Wang Jianhui; Xu Rui; Guo Weiqing; Li Zhihong; Liu dayu; Li Jingjing; Li Dagang; Chen Ying (Plant Molecular Biology, 2025)

CRP and HNF1A collaborate to regulate the progression of laryngeal cancer through the Wnt signaling pathway - Zhigang Zhao; Xiaojing Zhu; Jinyuan Xu; Penglong Song; Yanan Sun; Zhenming Yang; Li Wang; Jiarui Zhang; Rui Zhao; Xiaoxue Chen; Wenjing Li; Linli Tian; et al. (Functional & Integrative Genomics, 2025)

Integrated multi-omics analysis of UL16-binding protein 2 as a prognostic and immunotherapy biomarker for colorectal cancer - Xin-Yang Qu; Yong Xu; Rui-Min Wu; Gao-Chun Xiao; Ping-Feng Wang; Jin Xie; Xu-Sheng Liu (Functional & Integrative Genomics, 2025)

Immobilization of arsenic and antimony by silica-Fe (hydr)oxides composite: investigation of potential ecological effects on the soil microbial environment - Rui Xu; Yaxin Tian; Qian Li; Guangfei Qu; Lang Liao; Zhe Yin; Zhenguo Wu; Yuqi Han; Yan Zhang; Yongbin Yang; Dongbin Liu; Haiyan Yan; et al. (Environmental Geochemistry and Health, 2025)

Effects of Bacillus licheniformis supplementation on growth performance, intestinal health and oxidative stress in weaning transition male dairy calves - Yulin Ma; Yubin Ma; Shuangming Yang; Yuchen Cheng; Wenyi Ren; Xiaonv Liu; Rui Wang; Yan Kang; Haibo Li; Lili Zhang; Xiaofeng Xu (Animal Feed Science and Technology, 2025)

Research on Acoustic-Electrical Integrated Technology in Geothermal Resource Exploration, Development and Monitoring - Feng Chu; Rui Xu; Rong-hua Zhang; Yi-guo Xue; Deng-rui Wu; Lin-zhi Lang; Shu-ge Liu; Jing-kai Qu (Applied Geophysics, 2025)

Differential response patterns of bacterial communities in seawater and sediments to the Chaetomorpha valida bloom in sea cucumber Apostichopus japonicus aquaculture ponds - Hongxia Zhang; Kexin Xu; Ronglian Xing; Linqian Wang; Renyu Liu; Xin Wang; Lihong Chen; Rui Li; Zhen Yu; Xuebin Cao; Cao Cheng; Qun Su (Marine Pollution Bulletin, 2025)

Formyl peptide receptor 2 (FPR2) mediates cisplatin-induced cochlear inflammation and hair cell apoptosis - Jiaojiao Hou; Rui Liang; Yuhan Lin; Daiyao Liu; Jiamei Li; Yifan Liu; Tao Xu; Shuangyue Liu; Aimei Wang (Toxicology, 2025)

Development and validation of 10 K liquid chip for Inner Mongolia cashmere goat - Qi Xu; Haijiao Xi; Dongmei Shen; Tao Zhang; Jinquan Li; Rui Su; Qi Lv; Yanjun Zhang; Ruijun Wang; Na Wang; Baichuan Liu; Dong He; et al. (Small Ruminant Research, 2025)

Frititaipaines A−O, undescribed cevanine-type isosteroidal alkaloids from the bulbs of Fritillaria taipaiensis and their anti-neuroinflammatory and AChE inhibitory activities - Zai-Long Huang; En-Ke Qu; Lan-Run Yang; Rui Luo; Yan-Ni Liang; Shi-Jun Liu; Yuan-Zhen Xu; Dong-Bo Zhang (Phytochemistry, 2025)

Prediction method of propeller tip vortex cavitation inception based on bubble dynamics models and change-point detection - Jia Duan; Rongwu Xu; Lilin Cui; Bin Ji; Rui Wu; Heng Liu; Chang Chen (Ocean Engineering, 2025)

Discovery of ca. 2.33–2.22 Ga magmatic activities in the Longshan Complex bordering the southwestern margin of the North China Craton: Implications for tectonic transformation - Yi-Yi Zhang; Jun-Sheng Lu; Rui-Ying Zhang; Yu-Ting Li; Xu Kong; Gang Liu; Qiang Feng; Zeng-Yin Duan; Juan-Juan Li (Lithos, 2025)

Partial nitrification achievement through co-regulation of quorum sensing-mediated boric acid and free ammonia - Xu-Ming Liu; Bai-Hang Zhao; Hai-Shan Yang; Rui-Xuan Liu; Lei-Yue Wu (Journal of Water Process Engineering, 2025)

Enhancing NO3− reduction on BiFeO3/Cu cathode via ferroelectric polarization: A novel strategy for surface electronic structure regulation - Hao Chen; Houfen Li; Yue Zhao; Yunlong Ma; Zhichao Liu; Rui Li; Sufang Wang; Aijuan Zhou; Xiuping Yue; Haibing Meng; Hongtao Yu; Xu Zhao (Journal of Environmental Management, 2025)

Gas permeability characteristics and pore structure evolution of sandstones with high-temperature damage effects - Jiang-Feng Liu; Hong-Yang Ni; Xu Chen; Shi-Jia Ma; Zhi-Peng Wang; Rui-Nian Sun (International Journal of Rock Mechanics and Mining Sciences, 2025)

Cryoprotective activity of different characterized fractions isolated from sea cucumber intestinal protein hydrolysates against salmon - Zhe Xu; Shuang Guan; ShengAo Cao; Rui Zhang; Hanxiong Liu; Zijin Qin; Xiufang Dong; Jianping Wu; Tingting Li (Food Chemistry, 2025)

Fermented Sargassum hemiphyllum soluble dietary fiber exhibits enhanced bioactivity and gut microbiota regulation potential in C57BL/6 mice - Hongying Cai; Zhuo Wang; Rui Li; Qiaoli Zhao; Bingbing Song; Xiaofei Liu; Riming Huang; Baojun Xu; Shouchun Liu; Kit-Leong Cheong; Saiyi Zhong (Food Bioscience, 2025)

Air pollution, drought, and their synergistic effects on cardiovascular disease risk in China: a nationwide study - Chaohao Ling; Rui Li; Qian Shen; Lulu Cui; Mangen Yang; Zhou Liu; Tianzhao Xu; Wenwen Sun; Shaofu He (Environmental Pollution, 2025)

Changes in gas-to-aerosol-phase partitioning ratio of semi-volatile products affect secondary organic aerosol formation from α-pinene photooxidation - Shijie Liu; Xinbei Xu; Si Zhang; Rongjie Li; Zheng Li; Can Wu; Rui Li; Feiyong Chen; Guiqin Zhang; Gehui Wang (Atmospheric Environment, 2025)

Investigation of the mechanism of Dan Zhi Qing’e Formula for treating menopausal hot flashes using UHPLC-Q-TOF MS and network pharmacology - Xinyu Li; Xinyu Liu; Minghui Cai; Shuang Wei; Rui Wang; Nanjian Xu; Jingtian Qu; Yuming Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

The Impact of the Combined Application of Zinc and Selenium on the Physiological Mechanisms and Mercury Accumulation in Rice Under Mercury Stress - Qiu Huang; Jing Liu; Wanyu Li; Anqi Xu; Rui Wu; Fanxin Qin (Bulletin of Environmental Contamination and Toxicology, 2025)

Fusarium infection alters the effects of vegetable residue and its compost on nitrous oxide emissions from acid soil - Yumeng Xu; Xiaoxiao Xiang; Waqar Ahmed; Junhui Yin; Owen Fenton; Wenxuan Shi; Jiaqi Wang; Ruixue Chang; Rui Liu; Hao Chen; Guorong Xin; Qing Chen (Applied Soil Ecology, 2025)

S-Ketamine Alleviates Anxiety-Induced Chronic Postoperative Pain by Affecting Glucose Metabolism of Striatal Microglia in a Rat Model - Rui Xu; Wei Zhu; Xuan Xu; Yue Yao; Qi Liu; Yan Yang; Yulin Huang; Zhengliang Ma (Journal of Neuroimmune Pharmacology, 2025)

Nitric oxide regulates spindle dynamics to modulate the maturation of goat oocytes - Rui Xu; Zhi Zheng; Weizhao Bai; Minghui Liu; Sihai Lu; Sha Peng; Menghao Pan; Baohua Ma (Theriogenology, 2025)

Synergistic charge separation and magnetic recovery in a noble-metal-free Fe3O4/TiO2/Bi photocatalyst for bromate reduction - Ying Xu; Shuili Yu; Zhiqiang Fan; Xingli Ji; Cong Huang; Zheng Xu; Rui Liu; Chao Jiang (Journal of Water Process Engineering, 2025)

Data-driven collaborative safety evaluation for seepage reliability of embankments considering spatial variability - Bin Xu; Zichong Liu; Rui Pang; Yang Zhou (Journal of Hydrology, 2025)

Bismuth nanospheres enabling sacrificial-agent-free bromate photoreduction and total bromine mitigation for safer water treatment - Ying Xu; Shuili Yu; Zhiqiang Fan; Cong Huang; Lei Li; Rui Liu; Zheng Xu (Journal of Hazardous Materials, 2025)

Synergistic quorum quenching to the diffusible signal factor and AHLs mediated quorum sensing in Thiothrix controlling filamentous sludge bulking - Rui Liu; Lin Feng; Jie Li; Zhuo-Li Yan; Jian-Hong He; Yue Zhi; Xiao-Wei Xu; Peng Yan; You-Peng Chen (Journal of Environmental Chemical Engineering, 2025)

Sulfamethazine degradation via PMS activated by Co-Cu catalyst supported on modified geopolymer - Jiayin Liu; Rui Yang; Qi Jiang; Shaobo Chen; Menghao Fang; Shuguang Wang; Zhongjun Xu (Journal of Environmental Chemical Engineering, 2025)

Surface self-assembly of tannic acid network to enhance wastewater treatment and oil-water separation performance of dual-bismuth BiOBr–BiOCOOH/PVDF membranes - Dong Chen; Rui Zhang; Jie He; Maoqin Xu; Zixi Li; Yujie Liu; Lin Peng (Journal of Environmental Chemical Engineering, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Enhanced moisture tolerance and toluene oxidation activity of δ-MnO2 catalysts by Sn doping: Phase transition and surface protection - Yiming Li; Mengxia Xu; Rui Liu; Shuibo Wang; Taotao Sun; Zijun Yan; Cong Wan; Hongbo Yu; Haocheng Li; Haotian Li; Xudong Zhao; Kaijie Li; et al. (Fuel, 2025)

Elucidating the mechanism by which hofmeister anions influence rheological properties and microstructure of egg yolk low–density lipoprotein/κ–carrageenan double–network hydrogels - Jian Li; Mengzhuo Liu; Yunze Ma; Lina Xu; Huajiang Zhang; Hanyu Li; Lili Zhang; Ning Xia; Rui Chuang; Ahmed M. Rayan; Mohamed Ghamry (Food Hydrocolloids, 2025)

Benzotriazole (BT) and benzothiazole (BTH) derivatives as emerging marine pollutants in the Pearl River Estuary: Spatiotemporal distribution, environmental fates, and ecological risks - Xiaoxiao Chen; Qianyi Huang; Rui Hou; Shan Liu; Hengxiang Li; Tiantian Chen; Xiangrong Xu (Environmental Pollution, 2025)

Closing the loop with citramalic acid-based chiral polyester: A novel strategy as a game-changer for sustainable materials - Lei Song; Xinyu Liu; Ruimin Wang; Mo Zhou; Fei Li; Yunlong Sun; Lu Li; Yanming Hu; Ding Zhou; Xiaowei Xu; Mingyuan Zheng; Rui Wang (Chemical Engineering Journal, 2025)

Self-healing sodium alginate-PEDOT:PSS conductive hydrogel for accelerated burn wound healing and real-time monitoring - Xinshuo Liu; Feng Chen; Yifan Zhang; Zexiang Zheng; Rui Huang; Jinhuan Tian; Hong Li; Changren Zhou; Shuyun Zhang; Huihua Xu; Lihua Li (Chemical Engineering Journal, 2025)

Achieving stable partial nitrification through AHL-mediated quorum sensing combined with free ammonia: performance, microbial responses, and mechanistic insights - Bai-Hang Zhao; Xu-Ming Liu; Hai-Shan Yang; Rui-Xuan Liu; Lei-Yue Wu (Chemical Engineering Journal, 2025)

Application of platelet-rich plasma lysate combined with hyaluronic acid microneedles for the treatment of alopecia - Zhengxin Suo; Yingcan Xu; Along Zhang; Ye Cao; Jiaxin Liu; Hong Wang; Rui Zhong (Drug Delivery and Translational Research, 2025)

Jingfang granule extends lifespan and healthspan in Caenorhabditis elegans: insights from RNA-seq analysis of genetic mechanisms - Taili Zhao; Yunhua Hou; Chuanjiao Feng; Rui Zhao; Honghua Li; Peipei Zhao; Mengmeng Wang; Jingli Ren; Yiwei Meng; Kuidong Xu; Jia Liu; Xin Yin; et al. (Biogerontology, 2025)

Oral bioavailability property prediction based on task similarity transfer learning - Chen Zeng; Chengcheng Xu; Yingxu Liu; Yunya Jiang; Lidan Zheng; Yang Liu; Yanmin Zhang; Yadong Chen; Haichun Liu; Rui Gu (Molecular Diversity, 2025)

Enhancing the participation of water in the anaerobic digestion of sewage sludge for highly efficient methanogenesis - Jiachang Cao; Ying Xu; Chen Zhang; Xiang Li; Rui Liu; Xueye Wang; Xiaohu Dai (Water Research, 2025)

Global ocean surface p CO 2 retrieval and the influence of mesoscale eddies on its performance - Yujie Wang; Yadong Gao; Rui He; Yangyang Gao; Ziyang Xu; Changjie Wang; Fenfen Liu (Science of The Total Environment, 2025)

Quaternary sedimentary evolution and source apportionment in the northwestern South China Sea: Evidence from geochemical and zircon U-Pb data - Peng-Fei Xiong; Shu Jiang; Cong Cheng; Kai Zhang; Xiao-Yu Fang; Tao Jiang; Jia-Le Fu; Hong-Ji Liu; Xin-Rui Zhou; Xu-Shen Li (Quaternary Science Reviews, 2025)

Anti-neuroinflammatory naphthol dimers from the marine-derived fungus Penicillium sp. HQ1-23 - Yuan-Han Xie; Chun-Hong Wang; Rong Wang; Hui Jia; Fei Liu; Zi-Hong Peng; Ya-Hui Zhang; Jun Li; Rui-Yun Yang; Li-Jun Zhang; Wei-Feng Xu (Phytochemistry, 2025)

B2G: A novel framework for froth velocity estimation and quantification with graph neural networks - Rui Tian; Ziqi Lv; Xiu Liu; Meijie Sun; Yanan Tu; Zhiqiang Xu; Weidong Wang (Minerals Engineering, 2025)

Associations Between Pre- and Post-Diagnosis Dietary Inflammatory Patterns and Ovarian Cancer Survival: Results From the Ovarian Cancer Follow-Up Study - Jia-Xin Liu; Rui-Han Bao; Meng Luan; Chuan Liu; Lang Wu; Fang-Hua Liu; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Qian Xiao; Dong-Hui Huang; Xiao-Ying Li; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Atmospheric transport of microplastics from land to sea is inefficient: Evidence from multimedia observations - Xiangrong Xu; Zhen Yuan; Yanxu Zhang; Hengxiang Li; Lang Lin; Shan Liu; Rui Hou; Eddy Y. Zeng (Journal of Hazardous Materials, 2025)

Construction and application of a quantitative model for calculating LNAPL lateral migration in the capillary zone - Rui Zuo; Ziyi Wu; Jiawei Liu; Shida Zheng; Zuorong Xu; Zhiwen Wang; Zhenkun Xue; Chengzhi Wang (Journal of Hazardous Materials, 2025)

Electrocatalytic removal of nitrate by non-noble Fe3C/Cu: Property, mechanism, and practical water treatment performance - Yang Guo; Hao Chen; Houfen Li; Jiming Liu; Xiao Zhang; Aijuan Zhou; Xiuping Yue; Rui Li; Jindong Wang; Pengxiao Liu; Hongtao Yu; Xu Zhao (Journal of Hazardous Materials, 2025)

Genome-wide association and epidemiological evidence linking air pollution to aging mechanisms - Xiao-Yu Liu; Dong Peng; Xu-Rui Liu; Yuan-Hui Sheng; Jun-Nan Zhao; Rong-Bin Xu; Dan Zhang; Bo Chen (Journal of Hazardous Materials, 2025)

Recovery of rare earth elements from sediments affected by mining activities - De-Xiang Xu; Xuan-Pu Cheng; Cui-Ling Huang; Xiao-Rui Liu; Can-Die Xie; Rong-Liang Qiu; Chang Liu; Mei-Na Guo; Jean-Louis Morel; Wen-Shen Liu; Ye-Tao Tang (Journal of Hazardous Materials, 2025)

Earthworms mitigate drought effects on microbial decomposition of straw under varying microplastic conditions - Chuanxiong Huang; Weijie Zhao; Hangle Ren; Rui Wu; Ying Liu; Hongxin Xu; Benhua Sun; Jianglan Shi; Xiaohong Tian; Rui Yin (Journal of Hazardous Materials, 2025)

Targeted and non-targeted analyses reveal trophic biomagnification of rubber-derived chemicals in an estuarine food web near China's largest rubber production region - Yuan Liu; Jia-Ming Zhou; Nian-Nian Wu; Shan Liu; Xiao-Liang Liao; Haijiang Wu; Lin Zhu; Heng-Xiang Li; Lang Lin; Rui Hou; Zhi-Hua Li; Xiang-Rong Xu; et al. (Journal of Hazardous Materials, 2025)

High chemodiversity of nitrogen-containing organic compounds in vehicle emissions driven by transformative reactions - Shuang Chen; Yisheng Xu; Dandan Liu; Junjun Deng; Rui Liu; Shaofei Kong; Pingqing Fu (Journal of Hazardous Materials, 2025)

Synergistic infrared Co-pyrolysis for integrated resource Recovery: Gas-Induced metal extraction from spent lithium-ion batteries and bio-oil upgrading - Moshan Li; Erfeng Hu; Zuohua Liu; Guangwen Xu; Jianglong Yu; Zhaohui Lu; Guocan Zheng; Dean Pan; Rui Qu (Journal of Cleaner Production, 2025)

The decline in desert drift potential weakens aeolian dust emission - Tong Zhang; Lianyou Liu; Peijun Shi; Gangfeng Zhang; Rui Mao; Xia Xu; Zheng Fu; Honglei Jiang; Cuicui Shi; Li Ma; Zihui Zhao; Jiaojiao Dong; et al. (Global and Planetary Change, 2025)

Tart cherry extract alleviates gouty inflammatory response by down-regulating NF-κB signaling pathway - En Shi; Rui Wang; Lingfang Xu; Haijing Wang; Maichao Li; Kai Guo; Feng Zhang; Bingjie Liu; Yuwei He; Xianghong Meng (Food Bioscience, 2025)

Antioxidative stress and metabolic regulatory effects of black goji berry anthocyanins from aqueous two-phase extraction in Caenorhabditis elegans - Qiuxiong Xu; Bisheng Zheng; Tong Li; Rui Hai Liu (Food Bioscience, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Gradient distribution of trap states in polymer dielectrics induced by electric field for enhanced insulation properties - Bing Xia; Ming-Xiao Zhu; Zhi-Hao Xing; Rui Liu; Jie-Rui Ren; Xue-Kai Xu (Chemical Engineering Journal, 2025)

SiO2-assisted co-assembly of ultrafine aramid nanofiber-based porous thermal-resistant separator for Lithium-ion batteries - Fuhai Guo; Minghan Xu; Shi Feng; Keyu Zhang; Xiaotong Zheng; Hao Xue; Fulan Hao; Rui Zhuang; Qingchun Liu; Lei Zhang; Jianjun Zhang; Qingfu Wang (Chemical Engineering Journal, 2025)

Customized microbial inoculants enhance rhizosheath functionality and drive ecosystem restoration in desertified grasslands - Qiqi Han; Weimeng Liu; Yingjie Jiang; Pengyuan Yang; Zixuan Wang; Ziyuan Yan; Zhuo Zhang; Rui Xu; Hui Tang; Guixia Liu (Plant and Soil, 2025)

Effect of fulvic acid on aggregate characteristics and humus composition in saline-alkali soil - Rui Cai; Yaru Guo; Yanjie Li; Ling Li; Susu Xu; Ping Gong; Pengfei Li; Hongguang Liu (Plant and Soil, 2025)

Dynamic Transcriptome Analysis Uncovers Key Regulatory Genes During Stem Elongation Stages in Wheat - Rui Cao; Yaoyu Chen; Hongyong Dai; Zhencheng Xie; Lifen Wu; Zhan Li; Yuxin Yang; Lichao Zhang; Xu Liu; Xiuying Kong; Chuan Xia (Journal of Plant Growth Regulation, 2025)

Experimental and numerical investigation of gas preferential flow through geosynthetic clay liner overlap joint in landfill final cover system - Lin Qin; Fusheng Zha; Rui Xu; Songyu Liu; Abdelmalek Bouazza; He Huang; Qiao Wang (Bulletin of Engineering Geology and the Environment, 2025)

Algal diversity: A key driver of nitrogen immobilization by phototrophic biofilms at soil-water interfaces in paddy fields - Junzhuo Liu; Rui Sun; Ying Xu; Sichu Wang; Yonghong Wu (Science of The Total Environment, 2025)

A series of meroterpenoids with highly oxygenated skeletons from the endophytic fungus Penicillium sp. and their anti-inflammatory activities - Tu-Xiang Mo; Liu-Xia Lv; Xi-Shan Huang; Jia-Tong Zhou; Qian Wu; Xian-Hua He; Li-Qi Liang; Wei-Feng Xu; Jun Li; Rui-Yun Yang (Phytochemistry, 2025)

Mn-doped copper slag with oxygen vacancies boosts peroxymonosulfate activation for ofloxacin rapid removal - Linjin Li; Yaoze Wang; Guangfei Qu; Nanqi Ren; Yanping Liu; Jiao Wei; Dehui Kong; Changyi He; Minhua Cheng; Yingying Cai; Xiaofei Li; Rui Xu (Journal of Water Process Engineering, 2025)

Micro(nano)plastics (< 4 μm): An important but ignored concern during intravenous infusion - Penghui Li; Haoming Xu; Qingcun Li; Yujian Lai; Sujuan Yu; Rui Liu; Bintian Zhang; Jingfu Liu (Journal of Hazardous Materials, 2025)

Available medium and micronutrients in the soils of major citrus-producing areas in Southeast China - Zhangqian Xu; Yuzhou Zhou; Rui Liu; Haojie Cui; Jie Tan; Weijun Zhou; Kai Ouyang (Journal of Environmental Management, 2025)

Comparative in vivo study on the digestion behaviors of three typical saturated dietary fats in Sprague Dawley rats - Jiaying Yan; Yanjun Liu; Yanjun Guo; Rui Xu; Zhan Ye; Yuanfa Liu (Food Research International, 2025)

A self-powered photoelectrochemical sensor based on Cs3Bi2Br9/BiOBr photocathode for acetamiprid detection in vegetables - Kun Xu; Rui Xu; Xuejing Liu; Qin Wei (Food Chemistry, 2025)

Deciphering the molecular mechanisms of oil palm lipid metabolism through combined metabolomics and transcriptomics - Jerome Jeyakumar John Martin; Wen Xu; Xinyu Li; Xiaoyu Liu; Lixia Zhou; Rui Li; Dengqiang Fu; Qihong Li; Hongxing Cao (Food Chemistry, 2025)

l-theanine alleviates ulcerative colitis by repairing the intestinal barrier through regulating the gut microbiota and associated short-chain fatty acids - Aoxiang Liu; Bin Wang; Minming Wang; Rui Tang; Wei Xu; Wenjun Xiao (Food and Chemical Toxicology, 2025)

Directed evolution of Escherichia coli Nissle 1917 functioning as a methylotrophic chassis - Li-Hua Liu; Zhiqian Zhang; Bo Xu; Gangzhu Yang; Hua Cui; Lijun Su; Yu Zhang; Baoqing Sun; Yi-Rui Wu; Ao Jiang (Chemical Engineering Journal, 2025)

Adsorption and diffusion of vapour-phase PFAS in montmorillonite and kaolinite: Effect of moisture content and chain length - Qiao Wang; Rui Xu; Fusheng Zha; Songyu Liu; Huaxiang Yan (Chemical Engineering Journal, 2025)

Wound healing accelerated by stem cell bandage - Yingying Liu; Aman Lv; Jinjie Wu; Xiaoyan Wang; Yang Liu; Pui-In Mak; Rui P. Martins; Ren-He Xu; Yanwei Jia (Chemical Engineering Journal, 2025)

In-situ cascaded and selective bio-preparation of galactose-derived acids from cheese whey powder by the bifunctional regulation of resting-cell catalysis - Xia Hua; Rui Zhang; Yating Hu; Dylan Liu; Yong Xu (Bioresource Technology, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Droplet-vitrification for cassava shoot tip cryopreservation: protocol optimization and histological observation for rapid shoot tip recovery - Min-Rui Wang; Xiu-Qing Miao; Yun-Liu Fu; Lang-Xin Chen; Xiao-Bing Wang; Qing-Quan Yang; Li Xu; Zhiying Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Geochemical Characteristics of Natural Gas in the Upper Permian Reservoir of the Eastern Sichuan Basin, China: Implication of Multiple Sources Mixing - Lu Xu; Rui Liu; Yufeng Tang; Kangbin Zhang; Liang Feng; Xiucheng Tan; Fei Liu; Dingchuan Jiang (Journal of Earth Science, 2025)

Impact of Bacillus Licheniformis supplementation on growth performance, health status, and oxidative stress in male dairy calves during the weaning transition period - Yulin Ma; Yubin Ma; Shuangming Yang; Yuchen Cheng; Wenyi Ren; Xiaonv Liu; Rui Wang; Yan Kang; Haibo Li; Lili Zhang; Xiaofeng Xu (Animal Feed Science and Technology, 2025)

Regional Wave Spectra Prediction Method Based on Deep Learning - Yuning Liu; Rui Li; Wei Hu; Peng Ren; Chao Xu (Journal of Marine Science and Engineering, 2025)
The wave spectrum, as a key statistical feature describing wave energy distribution, is crucial for understanding wave propagation mechanisms and supporting ocean engineering applications. This study, based on ERA5 reanalysis spectrum data, proposes a model combining CNN and xLSTM for rapid gridded wave spectrum prediction over the Bohai and Yellow Seas domain. It uses 2D gridded spectrum data rather than a spectrum at specific points as input and analyzes the impact of various input factors at different time lags on wave development. The results show that incorporating water depth and mean sea level pressure significantly reduces errors. The model performs well across seasons with the seasonal spatial average root mean square error (SARMSE) of spectral energy remaining below 0.040 m2·s and RMSEs for significant wave height (SWH) and mean wave period (MWP) of 0.138 m and 1.331 s, respectively. At individual points, the spectral density bias is near zero, correlation coefficients range from 0.95 to 0.98, and the peak frequency RMSE is between 0.03 and 0.04 Hz. During a typical cold wave event, the model accurately reproduces the energy evolution and peak frequency shift. Buoy observations confirm that the model effectively tracks significant wave height trends under varying conditions. Moreover, applying a frequency-weighted loss function enhances the model’s ability to capture high-frequency spectral components, further improving prediction accuracy. Overall, the proposed method shows strong performance in spectrum prediction and provides a valuable approach for regional wave spectrum modeling.

Comparative analysis of phycospheric microbial diversity and metabolome between vegetative and matured conchocelis of Pyropia haitanensis - Rui Zhao; Zenghu Zhang; Fuli Liu; Qikun Xing; Ningning Xu; Wenjie Yan; Xu Gao (Aquaculture, 2025)

Molecular identification of heterotrophic nitrification and aerobic denitrification bacteria: From methods development to application demonstration - Rui-chun Yang; You-wei Cui; Zhen-ying Li; Ming-teng Li; Liu-xu Jiang; Ya-nan Mi; Yuan Sui; Hui-kai Liang (Water Research, 2025)

Carbon-friendly design method of tunnel lining segments based on Pareto optimal analysis - Tao Liu; Hehua Zhu; Yi Shen; Liankun Xu; Yi Rui (Tunnelling and Underground Space Technology, 2025)

A hybrid estimation of distribution algorithm for agile earth observing satellite task scheduling problem - Chunchun Ma; Panxing Huang; Xiaoze Liu; Chu-ge Wu; Rui Xu (Swarm and Evolutionary Computation, 2025)

Evolution and functional characterization of a biosynthetic gene cluster for saponin biosynthesis in Sapindaceae - Yingxiao Mai; Huimin Hu; Wenjuan Ji; Yaxuan Xiao; Hong Zhou; Zaohai Zeng; Wenshu Lv; Xingling Su; Jiakun Zheng; Jing Xu; Yanwei Hao; Zhenhua Liu; et al. (Molecular Plant, 2025)

Flow behavior and retarding mechanism of LNAPL pollutants in capillary zone - Rui Zuo; Chenxi Huang; Kexue Han; Donghui Xu; Xiao Zhao; Jiawei Liu; Ziyi Wu; Jinsheng Wang (Journal of Hydrology, 2025)

In Vitro metabolism of six representative organic UV stabilizers (OUVs) in marine fish liver microsomes: Kinetics, mechanisms and bioaccumulation evaluation - Yuchen Wang; Qianyi Huang; Siqi Zhang; Shan Liu; Hengxiang Li; Xiaodong Wang; Yan Wang; Rui Hou; Xiangrong Xu (Journal of Hazardous Materials, 2025)

Bentonite-goethite composite Colloids: Unraveling the mechanisms of strontium adsorption inhibition in claystone for nuclear waste geologic repositories - Rui Zuo; Zuorong Xu; Guanlan Wu; Jun Liu; Shida Zheng; Jun Xu; Jingchao Liu; Jiawei Liu; Weihai Cai (Journal of Environmental Radioactivity, 2025)

Multidimensional analysis of sensory perception and neurophysiological responses to marinated beef cooked by diverse methods - Tianyi Yang; Wei Jiang; Chencheng Luo; Jin Hu; Wei Xu; Peng Zhang; Xiaofei Jin; Yuxuan Zhou; Rui Liu; Zhiyu Qian; Yamin Yang (Innovative Food Science & Emerging Technologies, 2025)

Bioactives derived from egg by-products: Preparation, health benefits, and high-value-added applications - Yue Huang; Rui Chuang; Mengzhuo Liu; Huajiang Zhang; Hanyu Li; Lina Xu; Ning Xia; Chaogeng Xiao; Ahmed M. Rayan; Mohamed Ghamry (Food Chemistry, 2025)

Mechanistic applications of low-temperature plasma in starch-based biopolymer film: A review - Yanli Guo; Mengzhuo Liu; Rui Chuang; Huajiang Zhang; Hanyu Li; Lina Xu; Ning Xia; Chaogeng Xiao; Ahmed M. Rayan; Mohamed Ghamry (Food Chemistry, 2025)

Single and joint associations of exposure to polycyclic aromatic hydrocarbons with hypertensive disorders of pregnancy: A nested case-control study - Rui Yu; Cheng Chen; Mingyu Deng; Nian Wu; Yanling Xiao; Songlin An; Lin Tao; Xingting Zheng; Jing Yang; Zhongmei Hu; Pei Xu; Xingyan Liu; et al. (Environmental Pollution, 2025)

Rising disparities in grain self-sufficiency across China: Provincial divergence amidst overall national improvement - Xiaoyu Yu; Rui Xiao; Zhonghao Zhang; Feng Zhou; Fei Mo; Zhenci Xu; Feng Tian; Zhi Gao; Yansheng Li; Peng Zhu; Kailiang Yu; Lumeng Liu; et al. (Environmental Impact Assessment Review, 2025)

Fabrication of multifunctional sandwich-structured electrospun magnetic film for preventing postoperative recurrence of hepatocellular carcinoma and abdominal adhesions - Rui Wang; Xuanxuan Li; Liang Yan; Jinlong Hu; Haojie Lu; Jiaming Yao; Zhongxu Yuan; Jinshan Liu; Hongyu Xu; Xu Yan; Wenyong Wu; Baoqiang Cao (Chemical Engineering Journal, 2025)

Rapeseed transcription factor BnaC9bHLH35 promotes root growth and improves nitrogen use efficiency under low nitrate conditions - Qin-Xin Fang; Haokun Cheng; Zhongni Ma; Qiuyan Xu; Huanpeng Wang; Yunru Yan; Mengting Sun; Rui Wang; Wenlong Liu; Saeed Ullah; Yuhang Fan; Chunchun Huang; et al. (Theoretical and Applied Genetics, 2025)

Variations in lunar regolith mineralogy along the Chang’e-4, Yutu-2 traverse: Combined effects of ejecta sedimentation and subsequent modification - Zhenxing Zhao; Yazhou Yang; Dijun Guo; Yang Liu; Feng Zhang; Xing Wu; Rui Xu; Zhiping He; Yongliao Zou (Science China Earth Sciences, 2025)

Oil Film Detection for Marine Radar Image Using SBR Feature and Adaptive Threshold - Yulong Yang; Jin Yan; Jin Xu; Xinqi Zhong; Yumiao Huang; Jianxun Rui; Min Cheng; Yuanyuan Huang; Yimeng Wang; Tao Liang; Zisen Lin; Peng Liu (Journal of Marine Science and Engineering, 2025)
Marine oil spills pose a serious and persistent threat to marine ecosystems, coastal resources, and global environmental health. These incidents not only disrupt ecological balance by damaging marine flora and fauna but also lead to long-term economic consequences for fisheries, tourism, and maritime industries. Owing to their rapid spread and often unpredictable occurrence, timely and accurate detection is essential for effective containment and mitigation. An efficient detection system can significantly enhance the responsiveness of emergency teams, enabling targeted interventions that minimize ecological damage and economic loss. This paper proposes a marine radar-based oil spill detection method that combines the Significance-to-Boundary Ratio (SBR) feature with an improved Sauvola adaptive thresholding algorithm. The raw radar data was firstly preprocessed through mean and median filtering, grayscale correction, and contrast enhancement. SBR features were then employed to extract coarse oil spill regions, which were further refined using an improved Sauvola thresholding algorithm followed by a denoising step to obtain fine-grained segmentation. Comparative experiments using different threshold values demonstrate that the proposed method achieves superior segmentation performance by better preserving oil spill boundaries and reducing background noise. Overall, the approach provides a robust and efficient solution for marine oil spill detection and monitoring.

Identification and bioactivity evaluation of ring-opening and lactone forms of enterolactone from sheep fed flaxseed cake - Cong-Cong Zhuang; Chun-Rui Liu; Hai-Yan Xu; Xin-Yue Yang; Dan-Dan Wu; Zhong Zheng; Li-Wei Wang; Zheng Liu; Chao-Mei Ma (Natural Product Research, 2025)

Identification of key genes linking bisphenols exposure and breast cancer - Zhen Wang; Meng Cao; Tian Gao; Xinyue Xu; Weihua Yu; Jiangzheng Liu; Rui Liu; Xiaodi Zhang; Fei Li; Chunxu Hai (Toxicology, 2025)

The synthesis of arylmethylene bisindoles catalyzed by nickel perchlorate as potential antifungal agent against Clarireedia homoeocarpa - Ye Zhou; Ruyuan Wang; Rui Feng; Bi Wang; Shu Xu; Mei Tian; Wenhao Liang; Jin Chen; Yu Chen; Xu Feng; Li Lin; Jinyue Luo; et al. (Phytochemistry Letters, 2025)

Toxic effects and transcriptome analysis of the early life stages of Larimichthys crocea exposed to the bloom-forming dinoflagellate Alexandrium tamarense - Yongqi Cai; Anglu Shen; Hongtao Liu; Chongfeng Liu; Wantu Xu; Rui Jia (Marine Environmental Research, 2025)

Hydrogel materials in agriculture: A review - Hanghang Wang; Guangfei Qu; Xinxin Liu; Minjie He; Chenyang Yin; Rui Xu (Journal of Environmental Chemical Engineering, 2025)

Self-luminescent dual-ligand metal-organic framework based electrochemiluminescence probes for organophosphorus pesticides determination - Zheng Shen; Rui Xu; Guangxian Wang; Haifang Wang; Deyan Xu; JingJing Liu; Guanjie Wang; Yemin Guo; Xia Sun (Food Chemistry, 2025)

Discovery of novel DPP4 inhibitory peptides from egg yolk by machine learning and molecular docking: In vitro and in vivo validation - Yujie Xu; Yiqiao Pei; Zhifu Liu; Peng Tan; Rui Liu; Lulu Chu; Ye Zhang; Wenjie Wang; Hao Wang (Food Chemistry, 2025)

Antarctic krill oil phosphatidylcholine alleviates visceral hypersensitivity in irritable bowel syndrome: A lipidomics perspective - Siyan Wu; Yanjun Liu; Mengxue He; Zhan Ye; Rui Xu; Yuanfa Liu (Food Bioscience, 2025)

The recruitment of alkaline phosphatase-positive endogenous neural stem cells enables robust neurogenesis and neural pathways reconstruction following spinal cord injury - Rong-Jie Wu; Jia-Lin Liu; Zheng-Hong Chen; Jing Xu; Ying Ding; Hai-Yang Yu; Chuang-Ran Wu; Shang-Bin Yang; Rui Liu; Yi-Nan Guo; Yue Yang; Ting-Ting Wu; et al. (Chemical Engineering Journal, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Olaparib reverses prostate cancer resistance to Rapamycin by promoting macrophage polarization towards the M1 phenotype - Kai Ye; Gang Shi; Jian Xu; Kunyan Qiao; Qinghai Dai; Zhixiao Huo; Yu Cao; Wei Liu; Yue Hu; Lihua Yan; Yu Zhu; Ping Li; et al. (Molecular and Cellular Biochemistry, 2025)

Development of novel caffeic acid derivatives as multifunctional agents for the treatment of AD - Kerong Hu; Jing Yang; Qiyao Zhang; Xinxin Wang; Yujie Xu; Yuxin Zhang; Zhenghuai Tan; Wenmin Liu; Rui Chen; Zhipei Sang (Medicinal Chemistry Research, 2025)

Integrative transcriptomic and physiological analyses uncover mechanisms by which arbuscular mycorrhizal fungi mitigate salt stress in sugar beet - Zeyuan Cui; Xiaodong Li; Pingan Han; Rui Chen; Yinzhuang Dong; Gui Geng; Lihua Yu; Jiahui Liu; Yao Xu; Yuguang Wang (Mycorrhiza, 2025)

Ecological security and structural optimization of land space in the Pearl River Delta Urban Agglomeration: an approach based on the footprint family - Cong Huang; Jun Liu; Hanyu Yin; Zhonghao Zhang; Wei Cao; Wenfang Tan; Xufeng Fei; Chen Xu; Lumeng Liu; Jiali Chen; Kai Li; Rui Xiao (Environment, Development and Sustainability, 2025)

Ginsenoside Rf in wild ginseng adventitious roots extract inhibits melanogenesis via cAMP/PKA and NO/cGMP signalling pathways in α-melanocyte-stimulating hormone-stimulated B16F10 mouse melanoma cells and zebrafish - Hong Chen; Mengqiong Jian; Huanhuan Teng; Zhenzhuo Li; Xiaohao Xu; Xiangzhu Li; Rui Jiang; Daqing Zhao; Liwei Sun; Jianzeng Liu (Natural Product Research, 2025)

Growth monitoring of rapeseed seedlings in multiple growth stages based on low-altitude remote sensing and semantic segmentation - Fanguo Zeng; Rui Wang; Youming Jiang; Zhendong Liu; Youchun Ding; Wanjing Dong; Chunbao Xu; Dongjing Zhang; Jun Wang (Computers and Electronics in Agriculture, 2025)

Assessment of full-process VOCs emissions of on-road vehicles considering individual parking behaviors - Xinru Yang; Dawen Yao; Rui Xu; Yuzhuang Pian; Shikun Liu; Yonghong Liu (Transportation Research Part D: Transport and Environment, 2025)

Advanced oxidation processes for the removal of artificial sweeteners from aqueous environments: A comprehensive review - Jiayin Liu; Qi Jiang; Shaobo Chen; Rui Yang; Menghao Fang; Zhongjun Xu (Process Safety and Environmental Protection, 2025)

Recovery of volatile ethanol gas via microalgal-bacterial consortium: Ethanol-to-acetate conversion pathway boosts lipid production - Liu-Xu Jiang; You-Wei Cui; Ya-Nan Mi; Dong-Xu Zhou; Ming-Teng Li; Rui-Chun Yang (Journal of Environmental Management, 2025)

Time-series InSAR landslide three-dimensional deformation prediction method considering meteorological time-delay effects - Jichao Lv; Rui Zhang; Xin Bao; Renzhe Wu; Ruikai Hong; Xu He; Guoxiang Liu (Engineering Geology, 2025)

L-arginine-enhanced PEI-based polyamide Nanofiltration membranes for efficient heavy metal ion removal - Junwei Li; Shan Wang; Qingjuan Zhu; Daliang Xu; Yongmei Wang; Xi Zhang; Jiale Du; Qin Chen; Rui Zhao; Xiang Hu; Yong Liu; Raf Dewil; et al. (Desalination, 2025)

Process modeling guided start-up and stable operation of a pilot-scale mainstream partial denitrification-anammox system - Min Xu; Wenbo Chai; Wanlu Zhu; Yuyan Zhang; Rui Xiao; Changzhi Wang; Wenlong Liu; Huijie Lu (Chemical Engineering Journal, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Nitrogen addition and plant functional type mediate the mesofauna-driven litter element release of subtropical forest - Jihong Li; Qun Liu; Rui Yin; Chengming You; Li Zhang; Han Li; Lixia Wang; Hongwei Xu; Lin Xu; Sining Liu; Bo Tan; Zhenfeng Xu (Plant and Soil, 2025)

Dynamic transcriptomics and physiological insights reveal multi-tissue salt adaptation mechanisms in Amaranthus hypochondriacus across stress gradients - Qian Xu; Jinxin Gan; Zhikang Zhou; Tao Zhou; Rui Lu; Ningfang Liu; Longxing Hu (Plant Cell Reports, 2025)

Source identification of polycyclic aromatic hydrocarbons (PAHs) in river sediments within a hilly agricultural watershed of Southwestern China: an integrated study based on Pb isotopes and PMF method - Fen Xu; Chunmei Jiang; Qiang Liu; Rui Yang; Weiwei Li; Yao Wei; Linlin Bao; Hongjin Tong (Environmental Geochemistry and Health, 2025)

Simulating oasis-desert interactions in artificial and natural oasis-desert areas: Integration of remote sensing data and CFD methodology - Zhixing Peng; Shaomin Liu; Rui Liu; Xinlei He; Jin Ma; Ziwei Xu; Ji Zhou; Dongxing Wu (Agricultural and Forest Meteorology, 2025)

Chemical constituents of Pedicularis rex C. B. Clarke and their hepatoprotective activities - Yang Fei-Yu; Liu Huai-Qin; Fu-Rui Wang; Zhang Li-Jie; Liao Xing-Jiang; Guo-Bo Xu; Qin-Feng Zhu; Shang-Gao Liao (Natural Product Research, 2025)

Petrogenesis of Early Permian within-plate-type gabbros in the Western Qiangtang Terrane, Tibet: partial melting of lithospheric mantle metasomatized by subducted oceanic sediments on the northern margin of the Gondwana - Xiao-Rui Fan; Yun-Chuan Zeng; Ji-Feng Xu; Feng Huang; Ming-Jian Li; Xi-Jun Liu; Hong-Xia Yu; Jing Hu (International Geology Review, 2025)

FACNet: A high-precision pumpkin seedling point cloud organ segmentation method - Zerui Liu; Junhong Zhao; Yaowen Hu; Rui Li; Qiaomei Deng; Renxiang Guan; Ruoli Yang; Zhuonong Xu; Guoxiong Zhou (Computers and Electronics in Agriculture, 2025)

Diatomic "catalytic/co-catalytic" Fe/Mo catalysts promote Fenton-like reaction to treat organic wastewater through special interfacial reaction enhancement mechanism - Zhen Liu; Xin-Yi Xu; Fei Xu; Rui-Dian Su; Bin Li; Fang Zhang; Xing Xu; Yan Wang; De-Fang Ma; Bao-Yu Gao; Qian Li (Water Research, 2025)

Global analysis and prediction of the occurrence and fate of PFASs in dumpsites - Rui Xiang; Guangyuan Yao; Can Qian; Yuqiang Liu; Ya Xu; Qifei Huang (Resources, Conservation and Recycling, 2025)

Effect and mechanism of the moisture content on the kinetic retardation of LNAPL pollutant migration by the capillary zone - Kexue Han; Rui Zuo; Ronggao Qin; Donghui Xu; Xiao Zhao; Minghao Pan; Jiawei Liu; Yunxiang Xu; Jinsheng Wang (Journal of Hazardous Materials, 2025)

Study on the effect of surfactant ethoxy content on the wettability adjustment of bituminous coal interface - Lei Fang; Jiangshi Zhang; Yunfei Liang; Linquan Tong; Jianguo Liu; Hongfu Jia; Xinyang Chen; Pengcheng Liu; Rui Xu (Journal of Environmental Chemical Engineering, 2025)

Microwave-assisted synthesis and functionalization of biochar for environmental remediation: Regulate strategy and application potential - Jianhua Qu; Rui Yu; Xiaoyang Liu; Wei Peng; Fuxuan Bi; Xu Liu; Qiwen An; Yupeng Zhang; Qi Hu; Ying Zhang (Journal of Environmental Chemical Engineering, 2025)

Synthesis and performance evaluation of hydrate dissociation inhibitors suitable for cementing hydrate formations - Yuhuan Bu; Zilong Lu; Chang Lu; Huajie Liu; Shenglai Guo; Hexing Liu; Rui Ma; Zhen Zhang; Mengran Xu (Fuel, 2025)

Lactic acid bacteria-mediated transformation of black tea extract: Insights into metabolite profile and sensory characteristics - Zhi-Peng Cheng; Yao-Zeng Zhang; Zhong-Zheng Guan; Rui-shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2025)

Urinary concentrations of phthalate metabolites and the survival of high-grade serous ovarian cancer with advanced stage - Wen-Rui Zheng; Yi-Zi Li; Jin Xu; Ke-Xin Liu; Fang-Hua Liu; Wei-Yi Xing; Jia-Xin Liu; Lang Wu; Xiao-Ying Li; Dong-Hui Huang; Ting-Ting Gong; Qi-Jun Wu (Environmental Pollution, 2025)

High-throughput screening method for glycolipids based on substrate modification and their efficient biomanufacturing - Yuanyi Li; Zhilin Liu; Yiming Zheng; Ke Sun; Peng Lei; Yian Gu; Yongting Song; Jian Xue; Weidong Cai; Rui Wang; Hong Xu; Liang Sun (Bioresource Technology, 2025)

Grazing and Enclosure Alter the Vertical Distribution of Bacterial Communities in Different Microhabitats of Wetlands Along the Xilin River - Xiaoai Cao; Yating Tian; Huamin Liu; Hongbo Yu; Feng Niu; Rui Zhang; Zhichao Xu; Yi Zhuo; Lu Wen; Dongwei Liu; Lixin Wang (Wetlands, 2025)

Pharmacological Inhibition of TXNRD1 by a Small Molecule Flavonoid Butein Overcomes Cisplatin Resistance in Lung Cancer Cells - Rui Yang; Shibo Sun; Qiuyu Zhang; Haowen Liu; Ling Wang; Yao Meng; Na Chen; Zihan Wang; Haiyan Liu; Fengyun Ji; Yan Dai; Gaohong He; et al. (Biological Trace Element Research, 2025)

Weakly supervised dual-mask marginal segmentation and variable path planning method for bean weed based on UAV remote sensing - Jianlin Zhang; Xiangyu Lu; Rui Yang; Hongxing Xu; Yan Huai; Fei Liu (Computers and Electronics in Agriculture, 2025)

The bio-decolorization of methyl orange by S.putrefaciens CN32 and responding mechanism to salinity stress based on transcriptomic analysis - Bai-Hang Zhao; Bing-Lin Zhang; Bao-Yu Zhang; Rui-Xuan Liu; Xu-Ming Liu (Water Research, 2025)

Effect of rhizosphere soil microenvironment interaction on ginsenoside content in Panax ginseng: A case study of three-year-old agricultural ginseng - Zhefeng Xu; Yuqiu Chen; Rui Liu; Yibing Wang; Chunshuo Liu; Jing Fang; Qinghe Zhang; Tao Zhang; Changbao Chen (Rhizosphere, 2025)

Co-exposure to polystyrene nanoplastics and F-53B induces vascular endothelial cell pyroptosis through the NF-κB/NLRP3 pathway - Junli Lv; Zhenzhen Tan; Ziwen An; Rui Xu; Huaxing Zhang; Mingmei Guo; Fang Xiao; Mengwei Zhao; Yi Guo; Yi Liu; Xuehui Liu; Jingtao Ma; et al. (Journal of Hazardous Materials, 2025)

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

Biochar chemical-looping gasification for hydrogen-rich syngas production in solid-solid reaction: O, H and CaO of carbide slag effect NiFe2O4 oxygen carrier - Chenlong Liu; Wenqiang Tang; Xuechen zhang; Siddig Abuelgasim; Chenghua Xu; Rui Liu; Hengyi Xie; Fan Jiang (Journal of Environmental Management, 2025)

Effect of radio frequency combined oven pretreatment on the drying characteristics and quality of sweet potatoes - Qingqing Jiao; Xiangyu Guan; Juanjuan Xu; Li Liu; Rui Li; Yinfa Yan; Shaojin Wang (Innovative Food Science & Emerging Technologies, 2025)

Fat substitute in salad dressing: The role of soybean oil body self-aggregates in enhancing texture and rheological property - Xiaoyu Li; Rui Liu; Xin Lv; Ikram Alouk; Shuai Chen; Wenlu Li; Song Miao; Yanbo Wang; Duoxia Xu (Food Research International, 2025)

Structural characteristics and antioxidant activity of binary compounds formed by covalent modification of plant derived recombinant lactoferrin (OsrhLF) with four typical carbohydrates - Xiaoyan Guan; Kexin Wang; Yeting Wu; Jing Xu; Rui Liu; Zixian Xia; Yanchun Shao; Youyou Lu (Food Chemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Electrocatalytic reduction of nitrate to ammonia on CoMoO4 microspheres: A comparative study with Co3O4 - Yibo Xu; Long Cao; Hele Hua; Rui Li; Yunfang Wang; Jianxin Liu; Yawen Wang; Caimei Fan (Chemical Engineering Journal, 2025)

Dual-targeting of PDPN-expressing synovial fibroblasts and macrophages via CLEC-2-engineered exosomes for osteoarthritis therapy - Bo Yu; Rui Peng; Zitao Liu; Shanchuang Chen; Nanjun Xu; Qingjun Yang; Zhengang Zha; Bolai Chen; Tao Jiang; Tao Gui; Songwei Huan (Chemical Engineering Journal, 2025)

A photoswitchable phase-reversible gel engine for systemic redox homeostasis remodeling and on-demand chemodynamic immunotherapy with sustainable immunostimulation - Minghao Sun; Weiwei Liu; Yuanyuan Ma; Pengfei Ni; Wenjing Yao; Yingjie Xu; Rui Bao; Jue Wang; Fei Xiong; Xihe Kuang; Teng Zhang; Xiaochen Zhang; et al. (Chemical Engineering Journal, 2025)

Zinc-doped nickel sulfide/nickel hydroxide heterostructures for efficient and robust selective glucose oxidation reaction - Chi Zhang; Chunjian Xu; Linrui Yang; Xinyue Tao; Jianyi Liu; Rui Su; Xiangjun Meng; Ruoxi Yang; Dongfang Xue; Kaitian Zheng (Chemical Engineering Journal, 2025)

Molecular cation passivation and bromine vacancy supplement strategy for efficient wide-bandgap perovskite solar cells - Yue Yu; Maoxia Xu; Rui Liu; Haorong Ren; Jiangzhao Chen (Chemical Engineering Journal, 2025)

Dynamics of soil phosphorus fractions during the early recovery stage of two typical plantations in China after strip clearcutting - Linhui Zhang; Jihong Li; Su Chen; Wenlan Huang; Lulu Huang; Hongfeng Zhu; Yuanxiang Tang; Han Li; Chengming You; Lixia Wang; Sining Liu; Hongwei Xu; et al. (CATENA, 2025)

Shifting soil N regimes over a 70-year chronosequence of wetland reclamation and restoration - Kexin Li; Nannan Wang; Rui Su; Yunjiang Zuo; Jianzhao Liu; Ying Sun; Xinhao Zhu; Ziyu Guo; Lihua Zhang; Changchun Song; Ning Chen; Sergei Lupakov; et al. (CATENA, 2025)

Changes in Type 1 Diabetes-Associated Gut Microbiota Aggravate Brain Ischemia Injury by Affecting Microglial Polarization Via the Butyrate–MyD88 Pathway in Mice - Xianzhang Zeng; Can Ma; Wenchao Fu; Yongmei Xu; Rui Wang; Dan Liu; Lijuan Zhang; Narisu Hu; Dongmei Li; Wenzhi Li (Molecular Neurobiology, 2025)

Leveraging machine learning to explore nonlinear associations between urban heat vulnerability and morbidity risk - Jiaming Yang; Zhaomin Tong; Jiwei Xu; Rui An; Yanfang Liu; Yaolin Liu (Urban Climate, 2025)

Fertilization effects on soil organic matter chemistry - Dengjie Zhou; Rui Mou; Lihua Wang; Jingru Liu; Yuanxiang Tang; Ji Chen; Petr Heděnec; Zhenfeng Xu; Bo Tan; Xinglei Cui; Han Li; Li Zhang; et al. (Soil and Tillage Research, 2025)

First investigation of the luminescence dating of loess in the eastern Tibetan Plateau using K-feldspar MAR MET-pIRIR protocol - Li Liu; Shengli Yang; Pushuang Li; Jingzhao Zhang; Rui Li; Dongxue Li; Xuechao Xu; Yuanlong Luo; Xiuyun Yang (Quaternary Geochronology, 2025)

Regulation roles of dre-miR-187 in neurological damage by low concentration toluene in zebrafish - Shu-Hui Men; Jia-Yun Xu; Zhen-Guang Yan; Jin-Zhe Du; Ming-Rui Li; Zi-Ye Wang; Chen Liu; Xin Zheng (Journal of Cleaner Production, 2025)

Adsorption characteristics and mechanism insights of K2FeO4 coupling with ZnCl2-assisted modified functionalized biochar for Pb (II) in wastewater - Xuewen Yang; Fulin Yang; Can Liu; Hao Sun; Defa Hou; Yunwu Zheng; Hui Gao; Rui Shi; Xiahong He; Xu Lin (Journal of Environmental Chemical Engineering, 2025)

Improvement of ecological structure and function in phosphorus tailings-based soils through phosphorus-solubilizing bacteria inoculation and magnetic field treatment - Caiyue Jin; Xinxin Liu; Bangjin Chen; Guangfei Qu; Yaxin Tian; Fenghui Wu; Jieqian Yang; Rui Xu; Ping Ning (Journal of Environmental Chemical Engineering, 2025)

Preparation strategy of molecularly imprinted polymers adsorbent based on multifunctional carrier for precise identification and enrichment of fenthion - Lingjun Geng; Jingjing Liu; Jingcheng Huang; Haifang Wang; Peisen Li; Rui Xu; Chengqiang Li; Haowei Dong; Ibrahim A. Darwish; Yemin Guo; Xia Sun (Food Chemistry, 2025)

Methodology for quality risk prediction for milk powder production plants with domain-knowledge-involved serial neural networks - Kaiyang Chu; Rui Liu; Xu Shen; Guijiang Duan (Food Chemistry, 2025)

A multifunctional biosensor for selective identification, sensitive detection and efficient photothermal sterilization of Salmonella typhimurium and Staphylococcus aureus - Huasong Dai; Yingyue Zhang; Wenshi Zhao; Rui Guo; Sihan Qian; Yang Xu; Yuxuan Li; Yang Liu; Hongbo Liu (Analytica Chimica Acta, 2025)

Assessment of Peripheral Neuropathy Using Current Perception Threshold Measurement in Patients with Spinocerebellar Ataxia Type 3 - Xia-Hua Liu; Wei Lin; Hao-Ling Xu; Mao-Lin Cui; Zhuo-Ying Huang; Ying Li; Nan-Nan Zhang; Ning Wang; Zhi-Yong Wang; Shi-Rui Gan (The Cerebellum, 2025)

From Genes to Metabolites: HSP90B1’s Role in Alzheimer’s Disease and Potential for Therapeutic Intervention - Cheng Huang; Ying Liu; Shuxin Wang; Jinjun Xia; Di Hu; Rui Xu (NeuroMolecular Medicine, 2025)

Biodegradation of organic micropollutants by anoxic denitrification: Roles of extracellular polymeric substance adsorption, enzyme catalysis, and reactive oxygen species oxidation - Siqi Xu; Rui Li; Yang Liao; Jiyong Bian; Ruiping Liu; Huijuan Liu (Water Research, 2025)

To kill or to piggyback: Switching of viral lysis-lysogeny strategies depending on host dynamics - Chen Hu; Xiaowei Chen; Wei Wei; Douglas Wallace; Jihua Liu; Yao Zhang; Lianbao Zhang; Dapeng Xu; John Batt; Xilin Xiao; Qiang Shi; Qiang Zheng; et al. (Science of The Total Environment, 2025)

Comprehensive metabolome and transcriptome analyses shed light on the regulation of SlNF-YA3b in carotenoid biosynthesis in tomato fruit - Peiwen Wang; Siyu Ran; Yuanhang Xu; Fulei Mo; Fengshuo Li; Rui Lv; Fanyue Meng; Huixin Zhang; Yuxin Zou; Lei Yu; Tianyue Yu; Mozhen Cheng; et al. (Postharvest Biology and Technology, 2025)

Microbial mechanisms of sulfate reduction for low-temperature bioremediation of acid-mined uranium sandstone groundwater - Rui Xiao; Zhenghua Liu; Min Xu; Guoping Jiang; Yang Peng; Cunzeng Li; Jie Wang; Huaqun Yin; Lechang Xu (Journal of Water Process Engineering, 2025)

Effective removal of Pb from industrial wastewater: A new approach to remove Pb from wastewater based on engineered yeast - Hao Luo; Zheng Su; Yang Liu; Dong-Fang Yuan; Rui Wang; Yu-Hang Ning; Dong-Jiao Zhang; Xian-Ke Chen; Zhao-Bao Wang; Xue-Yan Gao; Yue-Chao Zhang; Guang Cheng; et al. (Journal of Hazardous Materials, 2025)

Noble gases in Paleozoic shale fluids document tectonic events and fluid migration in the Upper Yangtze Block - Rui Liu; Tao Wen; Daniele L. Pinti; Rui Xu; Fang Hao; Shang Xu; Zhiguo Shu (International Journal of Coal Geology, 2025)

Screening and characterization of an antifreeze peptide from sea cucumber intestinal protein hydrolysates - Zhe Xu; ShengAo Cao; Na Cui; Rui Zhang; Zijin Qin; Hanxiong Liu; Jianping Wu; Ming Du; Zhijian Tan; Tingting Li (Food Chemistry, 2025)

Mitochondrial protective effects of black goji berry anthocyanins in Caenorhabditis elegans: Defenses against oxidative stress - Qiuxiong Xu; Bisheng Zheng; Tong Li; Rui Hai Liu (Food Bioscience, 2025)

Exploring the immunomodulatory mechanisms of Osmunda japonica Thunb polysaccharides: Activation of MAPK and NF-κB signaling pathways - Xiaochen Liu; Rui Xu; Yuting Miao; Yining Zang; Yuxin Huang; Yuying Zheng; Fengwei Li; Ming Wei; Rui Xiao; Xiaohong Yu (Food Bioscience, 2025)

Alleviates effects of γ-cyclodextrin/genistein inclusion complex on oxidative stress injury induced by organic hydrogen peroxide in PC12 cells via Nrf2/GPx4 signaling pathway - Mengmeng Zhang; Jingbo Liu; Yiding Yu; Wenshuo Ren; Rui Yuan; Xuanting Liu; Xiaomin Shang; Zhiyang Du; Meng-Lei Xu; Ting Zhang (Food Bioscience, 2025)

Peptidomics and computational peptidology insights into the taste peptide profile of different extraction methods: A case study of fermented rice wine (Huangjiu) - Rui Chang; Zhilei Zhou; Yuezheng Xu; Xibiao Xu; Zhongwei Ji; Shuangping Liu; Jian Mao (Food Bioscience, 2025)

Poly-γ-glutamic acid chelates chromium (III) and copper (II), alleviating their toxicity in cucumber and affecting rhizosphere bacterial community assembly - Chaoyang Chen; Wenhui Yan; Yu Chen; Sijie Liu; Chuanjiang Nong; Liang Sun; Rui Wang; Hong Xu; Peng Lei; Yian Gu (Environmental Pollution, 2025)

Fatigue behavior of square steel strut-to-gusset plate welded connections under eccentric compression: Full-scale and reduced-scale tests - Xiaoqing Xu; Hongfa Luo; Bin Wang; Yuqing Liu; Kaixiang Miao; Rui Hao; Weiwei Lin; Yuwen Zhou; Dongyang He; Md Asadujjaman (Engineering Structures, 2025)

Ultrafine Na3V2(PO4)3@C with boosted interfacial charge transfer kinetics for low-temperature (−40 °C) Na-ion battery - Yanjing Liu; Shitan Xu; Huacheng Zhu; Yang Yang; Yang Yang; Yanping Zhou; Xianhong Rui (Chemical Engineering Journal, 2025)

ε-Poly-L-lysine/rhamnolipid bifunctional coating based on green electrostatic assembly technology for fruit packaging and preservation - Quanfei Li; Qian Chen; Kai Yang; Hao Liu; Delei Xu; Yian Gu; Liang Sun; Peng Lei; Rui Wang; Hong Xu (Chemical Engineering Journal, 2025)

The coupling model of random forest and interpretable method quantifies the response relationship between PM2.5 and influencing factors - Jinxing Liu; Hui Yu; Yaqing Zhang; Junjun Chen; Shiyuan Feng; Rui Guo; Feng Wang; Bo Xu; Guoliang Shi; Yinchang Feng (Atmospheric Environment, 2025)

Protective effect of SERCA2a-SUMOylation by SUMO-1 on diabetes-induced atherosclerosis and aortic vascular injury - Jinlin Liu; Shifang Xu; Bin Gao; Meng Yuan; Li Zhong; Rui Guo (Molecular and Cellular Biochemistry, 2025)

Assessment of myelination development in neonatal rats using chemical exchange saturation transfer (CEST) 7-T MRI - Rui Wang; Shuxian Xu; Fenglin Jia; Yi Liao; Jiayi Li; Jing Liu; Fengyan Zhao; Haibo Qu (Experimental Brain Research, 2025)

Nanozymes featuring a mesoporous silica shell for rapid enrichment and ultrasensitive lateral flow immunoassay of influenza A - Jing Liang; Xiaoxian Liu; Zhenzhen Liu; Xuanming Xu; Yinuo Sun; Yuan Chen; Rui Xiao; Yajie Wang (Analytica Chimica Acta, 2025)

SOTHE: SOlar-terrestrial habitability explorer - Jiajia Liu; Bingkun Yu; Fuchuan Pang; Siteng Fan; Lixiang Gu; Lingping He; Yajuan Lei; Bo Li; Rui Li; Yiren Li; Dongdong Liu; Kai Liu; et al. (Advances in Space Research, 2025)

Molecular intersections of traumatic brain injury and Alzheimer’s disease: the role of ADMSC-derived exosomes and hub genes in microglial polarization - Pengtao Li; Liguo Ye; Sishuai Sun; Yue Wang; Yihao Chen; Jianbo Chang; Rui Yin; Xiaoyu Liu; Wei Zuo; Houshi Xu; Xiao Zhang; Robert Chunhua Zhao; et al. (Metabolic Brain Disease, 2024)

Unveiling spatiotemporal distribution, partitioning, and transport mechanisms of tire additives and their transformation products in a highly urbanized estuarine region - Hai-Yan Zhang; Yue-Hong Liu; Li-Ni Wei; Rui-Qi Zhu; Jian-Liang Zhao; Shan Liu; Xiang-Rong Xu; Guang-Guo Ying (Science of The Total Environment, 2024)

Global distribution, drivers, and potential hazards of microplastics in groundwater: A review - Jun Xu; Rui Zuo; Guanlan Wu; Jingchao Liu; Jiawei Liu; Chenxi Huang; Zhiwen Wang (Science of The Total Environment, 2024)

Higher water content observed in smaller size fraction of Chang'e-5 lunar regolith samples - Honglei Lin; Rui Xu; Shuai Li; Rui Chang; Hejiu Hui; Yang Liu; Hengci Tian; Kai Fan; Zhiping He; Huaiyu He; Wei Yang; Yangting Lin; et al. (Science Bulletin, 2024)

β-Caryophyllene oxide inhibits lysine acetylation of histones in Fusarium proliferatum to block ribosomal biosynthesis and function - Hong-Xin Liao; Jing Yang; Jin-Rui Wen; Hong-Yan Nie; Jun Zhao; Fu-Rong Xu; Xiao-Yun Liu; Xian Dong (Pesticide Biochemistry and Physiology, 2024)

Boosting light harvesting and charge separation in Au nanoparticles and g-C3N4 co-modified TiO2 nanotube arrays for efficient photoelectrocatalytic reduction of nitrate in water - Rui Xu; Yong Guan; Lixue Cao; Xiaoxi Yu; Linsen Li; Bingrui Ma; Chunwei Liu (Journal of Water Process Engineering, 2024)

Xenobiotic metabolism activity of gut microbiota from six marine species: Combined taxonomic, metagenomic, and in vitro transformation analysis - Siqi Zhang; Rui Hou; Yuchen Wang; Qianyi Huang; Lang Lin; Hengxiang Li; Shan Liu; Zhijian Jiang; Xiaoping Huang; Xiangrong Xu (Journal of Hazardous Materials, 2024)

ABA-regulated MAPK signaling pathway promotes hormesis in sugar beet under cadmium exposure - Xiaoxin Zhao; Shuoqi Huang; Qi Yao; Rui He; Hao Wang; Zhaodan Xu; Wang Xing; Dali Liu (Journal of Hazardous Materials, 2024)

Landscape fragmentation of built-up land significantly impact on water quality in the Yellow River Basin - Jinghui Dou; Rui Xia; Kai Zhang; Chao Xu; Yan Chen; Xiaoyu Liu; Xikang Hou; Yingze Yin; Lina Li (Journal of Environmental Management, 2024)

1T/2H-MoS2/CdS heterojunction for the co-production of lactic acid photoreforming to hydrogen and value-added chemicals - Ermiao Liang; Xue Liu; Zheng Yang; Jifang Zhang; Yabo Qi; Rui Teng; Wenbo Cui; Mingcong Xu; Sha Luo; Chunhui Ma; Shouxin Liu; Wei Li (Journal of Environmental Chemical Engineering, 2024)

Effective variance attention-enhanced diffusion model for crop field aerial image super resolution - Xiangyu Lu; Jianlin Zhang; Rui Yang; Qina Yang; Mengyuan Chen; Hongxing Xu; Pinjun Wan; Jiawen Guo; Fei Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Study on the high-temperature corrosion mechanism of boiler steel 15CrMoG in ammonia-coal co-firing environment - Tiantian An; Bo Wei; Rui Ma; Lijuan Chen; Shan Wang; Meng Xu; Kunpeng Liu (Fuel, 2024)

Dissecting the effect of substrate on polyamide reverse osmosis membranes via regulating substrate pore size by drying shrinkage - Rui Bai; Jin-Kai Qiu; Liu-Kun Wu; Zhen-Liang Xu; Cheng Lian; Hong-Lai Liu; Jia-Hui Li; Yong-Jian Tang (Desalination, 2024)

Unraveling the chloride ion capture capability of nitrogen-doped porous carbon for capacitive deionization and desalination battery - Huazeng Yang; Rui Zhang; Zhiyuan Liu; Xin Xu; Yishuo Teng; Ming Hou; Guangshuai Zhang; Yongzhao Hou; Guangwu Wen; Dong Wang (Chemical Engineering Journal, 2024)

Mining of dynamic traffic-meteorology-atmospheric pollutant association rules based on Eclat method - Yonghong Liu; Xinru Yang; Kui Liu; Rui Xu; Yuzhuang Pian; Shikun Liu (Atmospheric Pollution Research, 2024)

Deep Learning Approach for Hydraulic Support Anomaly Detection: Utilizing Convolutional Autoencoders and Dynamic Time Warping Technology - Xigui Zheng; Cong Wang; Chao Kong; Cancan Liu; Kai Zhan; Rui Xu (Rock Mechanics and Rock Engineering, 2024)

Study of the effect of keap1 on oxidative stress in human umbilical cord mesenchymal stem cells - Hongrong Deng; Yunxia Chen; Huiwen Liu; Li Wang; Hao Xu; Bin Tan; Qin Yi; Rui Wang; Bolin He; Jie Tian; Jing Zhu (Molecular Biology Reports, 2024)
Background HucMSCs had shown promising efficacy in treating childhood diseases, but oxidative stress induced by the poor microenvironment at the site of damage resulted in low cell survival after transplantation, thus preventing the cells from maximizing therapeutic efficacy. Therefore, this study aimed to investigate the role and mechanism of keap1 in oxidative stress injury of human umbilical cord mesenchymal stem cells (hucMSCs), and to provide theoretical support for improving the efficacy of stem cell therapy. Methods The hucMSCs were treated with hypoxic low-sugar-free serum (GSDH) to mimic the damaged site microenvironment after implantation. Adenoviral overexpression of keap1 gene of hucMSCs was performed in vitro, and cell proliferation ability was detected by CCK8 assay, crystal violet staining assay, and cell cycle assay. Cellular redox level was assessed by Amplex Red, MDA, and GSH/GSSG kit. Mitochondrial morphology was evaluated by mitotracker Red staining. ATP production was estimated by ATP detection kit. The mRNA and protein expression levels were tested by western blotting and RT-qPCR. Results GSDH treatment substantially upregulated keap1 expression. Subsequently, we found that overexpression of keap1 notably inhibited cell proliferation and caused cells to stagnate in G1 phase. At the same time, overexpression of keap1 induced the production of large amounts of H 2 O 2 and the accumulation of MDA, but suppressed the GSH/GSSG ratio and the expression of antioxidant proteins NQO1 and SOD1, which caused oxidative stress damage. Overexpression of keap1 induced cells to produce a large number of dysfunctional mitochondria resulting in reduced ATP production. Moreover, Overexpression of keap1 significantly decreased the IKKβ protein level, while upregulating IkB mRNA levels and downregulating P50 mRNA levels. Conclusions Overexpression of keap1 may induce oxidative stress injury in hucMSCs by down-regulating IKKβ expression and inhibiting NF-κB pathway activation. This implies the importance of keap1 in hucMSCs and it may be a potential gene for genetic modification of hucMSCs.

Muscone inhibits angiotensin II–induced cardiac hypertrophy through the STAT3, MAPK and TGF-β/SMAD signaling pathways - Yi-jiang Liu; Jia-jia Xu; Cui Yang; Yan-lin Li; Min-wei Chen; Shi-xiao Liu; Xiang-hui Zheng; Ping Luo; Rui Li; Di Xiao; Zhong-gui Shan (Molecular Biology Reports, 2024)
Background Muscone is a chemical monomer derived from musk. Although many studies have confirmed the cardioprotective effects of muscone, the effects of muscone on cardiac hypertrophy and its potential mechanisms are unclear.The aim of the present study was to investigate the effect of muscone on angiotensin (Ang) II-induced cardiac hypertrophy. Methods and results In the present study, we found for the first time that muscone exerted inhibitory effects on Ang II-induced cardiac hypertrophy and cardiac injury in mice. Cardiac function was analyzed by echocardiography measurement, and the degree of cardiac fibrosis was determined by the quantitative real-time polymerase chain reaction (qRT-PCR), Masson trichrome staining and western blot assay. Secondly, qRT-PCR experiment showed that muscone attenuated cardiac injury by reducing the secretion of pro-inflammatory cytokines and promoting the secretion of anti-inflammatory cytokines. Moreover, western blot analysis found that muscone exerted cardio-protective effects by inhibiting phosphorylation of key proteins in the STAT3, MAPK and TGF-β/SMAD pathways. In addition, CCK-8 and determination of serum biochemical indexes showed that no significant toxicity or side effects of muscone on normal cells and organs. Conclusions Muscone could attenuate Ang II-induced cardiac hypertrophy, in part, by inhibiting the STAT3, MAPK, and TGF-β/SMAD signaling pathways.

A novel data-driven hybrid intelligent prediction model for reservoir landslide displacement - Dezhi Zai; Rui Pang; Bin Xu; Jun Liu (Bulletin of Engineering Geology and the Environment, 2024)

Chang’E-7 Lunar Soil Water Molecule Analyzer (LSWMA) Prototype for High-Precision Measurement of Water Content and Hydrogen Isotope Ratio - Rui Chen; Wenzhen Lu; Xiang Li; Xingping Wang; Kan Chen; Chi Zhang; Nailiang Cao; Zhenyu Xu; Yi Xu; Ruifeng Kan; Renrui Liu; Qiquan Yang; et al. (Journal of Earth Science, 2024)

On the Nearshore Significant Wave Height Inversion from Video Images Based on Deep Learning - Chao Xu; Rui Li; Wei Hu; Peng Ren; Yanchen Song; Haoqiang Tian; Zhiyong Wang; Weizhen Xu; Yuning Liu (Journal of Marine Science and Engineering, 2024)
Accurate observation of nearshore waves is crucial for coastal safety. In this study, the feasibility of extracting wave information from wave video images captured by shore-based cameras using deep learning methods was explored, focusing on inverting nearshore significant wave height (SWH) from instantaneous wave video images. The accuracy of deep learning models in classifying wind wave and swell wave images was investigated, providing reliable classification results for SWH inversion research. A classification network named ResNet-SW for wave types with improved ResNet was proposed. On this basis, the impact of instantaneous wave images, meteorological factors, and oceanographic factors on SWH inversion was evaluated, and an inversion network named Inversion-Net for SWH that integrates multiple factors was proposed. The inversion performance was significantly enhanced by the specialized models for wind wave and swell. Additionally, the inversion accuracy and stability were further enhanced by improving the loss function of Inversion-Net. Ultimately, time series inversion results were synthesized from the outputs of multiple models; the final inversion results yielded a mean absolute error of 0.04 m and a mean absolute percentage error of 8.52%. Despite certain limitations, this method can still serve as a useful alternative for wave observation.

A multimodal classification method: Cow behavior pattern classification with improved EdgeNeXt using an inertial measurement unit - Yingqi Peng; Yingxi Chen; Yuxiang Yang; Meiqi Liu; Rui Hu; Huawei Zou; Jianxin Xiao; Yahui Jiang; Zhisheng Wang; Lijia Xu (Computers and Electronics in Agriculture, 2024)

Unraveling the toxicity mechanisms of nanoplastics with various surface modifications on Skeletonema costatum: Cellular and molecular perspectives - Ting-Ting Xu; Zhen-Liang Li; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Tao Li; Eddy Y. Zeng; Ke-Fu Yu; Xiang-Rong Xu (Science of The Total Environment, 2024)

Divergent responses of woody plant leaf and root non-structural carbohydrates to nitrogen addition in China: Seasonal variations and ecological implications - Rui Mou; Yi Jian; Dengjie Zhou; Jihong Li; Yao Yan; Bo Tan; Zhenfeng Xu; Xinglei Cui; Han Li; Li Zhang; Hongwei Xu; Lin Xu; et al. (Science of The Total Environment, 2024)

Mechanisms of litter input changes on soil organic carbon dynamics: a microbial carbon use efficiency-based perspective - Jia Zeng; Xiangyang Li; Rui Song; Haoxuan Xie; Xiangnan Li; Weichao Liu; Hanyu Liu; Yaoyao Du; Miaoping Xu; Chengjie Ren; Gaihe Yang; Xinhui Han (Science of The Total Environment, 2024)

KMT2D deficiency leads to cellular developmental disorders and enhancer dysregulation in neural-crest-containing brain organoids - Ziyun Shan; Yingying Zhao; Xiuyu Chen; Guodong Zhan; Junju Huang; Xuejie Yang; Chongshen Xu; Ning Guo; Zhi Xiong; Fang Wu; Yujian Liu; He Liu; et al. (Science Bulletin, 2024)

Composited sea surface responses to tropical cyclones in the Bay of Bengal during 2003–2020 - Mengyuan Xu; Xiuting Wang; Liang Sun; Haihua Liu; Rui Liu; Gaopeng Lu (Marine Environmental Research, 2024)

Astronomical forcing of terrestrial organic carbon burial in East Asia during the Eocene - Juan Liu; Juye Shi; Yongchao Lu; Xiaojie Fan; Ze Zhang; Rui Zhang; Zhixiang Wang; Ke Xu; Anguo Xiao; David B. Kemp; Chunju Huang (Earth and Planetary Science Letters, 2024)

Formate-facilitated recovery of wastewater anammox granular sludge from oxygen inhibition: Effects and mechanisms - Min Xu; Rui Xiao; Fengqian Xu; Wenbo Chai; Wenlong Liu; Huijie Lu (Chemical Engineering Journal, 2024)

A superior material with antithrombotic properties serves as a secure adsorbent for the elimination of bilirubin in vitro and in pig models - Rui Su; Wei Liu; Gang Shi; Dongling Chen; Lihua Yan; Qian Li; Haichao Ni; Meili Yu; Liang Xu (Chemical Engineering Journal, 2024)

Half-antibody spur one-to-one recognition mechanism can function with chemical-staining technology for next-generation lateral flow immunoassay - Jingke Xu; Jing Zhou; Kai Liu; Tong Bu; Leina Dou; Rui Shu; Sijie Liu; Shaochi Wang; Xuechi Yin; Daohong Zhang; Ruiling Zhang; Jie Cheng; et al. (Chemical Engineering Journal, 2024)

Quantifying night-time light change drivers in China’s Yangtze River economic zone - Pinglang Kou; Yuxiang Tao; Ali P. Yunus; Qiang Xu; Rui Liu; Zhao Jin; Wenli Liang; Ying Xia; Shuang Yuan (International Journal of Remote Sensing, 2024)

Relative importance of altitude shifts with plant and microbial diversity to soil multifunctionality in grasslands of north-western China - Ning Wang; Junhui Cheng; Yunhua Liu; Qicheng Xu; Chen Zhu; Ning Ling; Junjie Guo; Rui Li; Wei Huang; Shiwei Guo; Baorong Wang; Shaoshan An; et al. (Plant and Soil, 2024)

Probiotic nucleotides increase IL-10 expression in airway macrophages to mitigate airway allergy - Jinmei Xue; Zhizhen Liu; Bailing Xie; Rui Dong; Juan Wu; Yisha Wu; Zhihan Xu; Yuhe Tian; Yao Wei; Zhigang Geng; Lei Lu; Yu Liu; et al. (Inflammation Research, 2024)

Analysis of factors affecting microbial degradation of cyanobacterial toxins based on theoretical calculations - Jianglong Ling; Ye Ruan; Congchao Xu; Di Liu; Bowen Shi; Yihong Yang; Zihao Jia; Tianyu Zhang; Mingxuan Guo; Rui Li; Xixi Li (Environmental Geochemistry and Health, 2024)

Tree species-mediated soil properties shape soil fauna community structure more strongly in the soil layer: Evidence from a common garden experiment - Jingru Liu; Aomiao Wu; Rui Yin; Zhenfeng Xu; Chengming You; Li Zhang; Lin Xu; Hongwei Xu; Lixia Wang; Han Li; Sining Liu; Yang Liu; et al. (Applied Soil Ecology, 2024)

Source identification of nitrate in groundwater of an agro-pastoral ecotone in a semi-arid zone, northern China: Coupled evidences from MixSIAR model and DOM fluorescence - Anqi Chen; Yao Du; Zichen Wang; Xiaoliang Sun; Rui Xu; Yaojin Xiong; Liangping Yang; Junting Liu; Yiqun Gan (Applied Geochemistry, 2024)

A novel hollow flower shaped Cu9S8 antibacterial agent for removing sulfonamide in water environment: effects of composite with magnetic biochar, differential adsorption, and mechanism study - Rui-peng Li; Zheng-rong Hu; Xing Wang; Jun Chen; Qing-qing Liu; Ying Zhao; Zhong-bao Zhao; Xu-lin Lu; Zhi-wei Zhang (Environmental Science and Pollution Research, 2024)

Exploring the multiscale island terrestrial ecosystem service relationships and coastal vulnerability under the influence of coastal ecosystems - Rui Du; Baiqiong Liu; Zhou Chen; Min Xu (Ocean & Coastal Management, 2024)

A global urban heat island intensity dataset: Generation, comparison, and analysis - Qiquan Yang; Yi Xu; TC Chakraborty; Meng Du; Ting Hu; Ling Zhang; Yue Liu; Rui Yao; Jie Yang; Shurui Chen; Changjiang Xiao; Renrui Liu; et al. (Remote Sensing of Environment, 2024)

Environmental safety performance dynamics and estimation of the deterioration of leachate containment elements: Implications for the lifespan of hazardous waste landfills - Rui Xiang; Can Qian; Guangyuan Yao; Yuqiang Liu; Heyu Du; Ya Xu; Qifei Huang (Journal of Cleaner Production, 2024)

Iron-based materials for immobilization of heavy metals in contaminated soils: A critical review - Yaxin Tian; Guangfei Qu; Rui Xu; Xinxin Liu; Caiyue Jin (Journal of Environmental Chemical Engineering, 2024)

Self-cleaning of metal-organic framework membranes achieved by photocatalytic ZIFs for dye and antibiotic separation - Jie He; Rui Zhang; Dong Chen; Ziyin Chen; Jiacheng Jiang; Maoqing Xu; Yujie Liu; Zixi Li; Lin Peng; Yong Shu; Luming Jiang; Guixiang Zhao (Journal of Environmental Chemical Engineering, 2024)

In-orbit detection of the spectral smile for the Mars Mineral Spectrometer - Bing Wu; Rui Xu; Chengyu Liu; Zhiping He (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Reaction mechanism for NH3-SCR of NOx over CrMn1.5O4 catalyst - Zheng-nan Yuan; Rui-tang Guo; Xiao-jing Liu; Yi-feng Xu; Lu Liu; Wei-guo Pan (Fuel, 2024)

Chronic PM2.5 exposure disrupts intestinal barrier integrity via microbial dysbiosis-triggered TLR2/5-MyD88-NLRP3 inflammasome activation - Zihan Ran; Jingcheng Yang; Liang Liu; Shaobo Wu; YanPeng An; Wanwan Hou; Tianyuan Cheng; Youyi Zhang; Yiqing Zhang; Yechao Huang; Qianyue Zhang; Jiaping Wan; et al. (Environmental Research, 2024)

Spatial distribution and enrichment characteristics of selenium in paddy soil and rice around the Dongting Lake - Rui Liu; Weijun Zhou; De Yu; Guiduo Shang; Yuzhou Zhou; Zhangqian Xu; Dou Tang; Haojie Cui; Chaolin Liao (Environmental Pollution, 2024)

Triple effective water treatment agent: P(AA/AMPS) capped sulfur quantum dots boast remarkable antiscale, antibacterial, and real-time tracking capabilities - Hengtong Xia; Rui Ding; Chao Xia; Ruodong Yang; Zhihao Chen; Hui Xu; Xiaoshuang Yin; Ying Liu; Wenzhong Yang (Desalination, 2024)

Monitoring crack opening via seismic velocity variation to assess that fatal effect of precipitation for landslide motion - Zhiqiang Liu; Chuntao Liang; Christoph Sens-Schönfelder; Wei Hu; Xinlei Sun; Tuo Zhang; Rui Xu; Zhiyu Jiang; Hao Jiang (Earth and Planetary Science Letters, 2024)

High-throughput generation of monodisperse double emulsions via controllable symmetric splitting in Y-shaped microchannels - Lin-Ling Fan; Wei Wang; Xiao-Jie Ju; Zhuang Liu; Rui Xie; Jianhong Xu; Guangsheng Luo; Da-Wei Pan; Liang-Yin Chu (Chemical Engineering Journal, 2024)

Anion vacancy engineering in carbon coating VS4 microspheres assembled by nanorod arrays for high-performance rechargeable Mg-Li hybrid batteries - Xu Zhang; Qinke Tang; Yana Liu; Yunfeng Zhu; Jiguang Zhang; Jun Wang; Rui Shi (Chemical Engineering Journal, 2024)

Enhancing reaction kinetics in aprotic magnesium-air batteries using a freestanding flexible metal-free carbon fiber cathode - Wenbo Liu; Ning Wang; Rui Zhong; Fanfan Liu; Yongjun Wu; Qianyi Zhang; Xiaoyan Chen; Yanmei Li; Minghui Yu; Rui Xu; Yifei Yuan; Dan Luo; et al. (Chemical Engineering Journal, 2024)

Multifunctional-Element doping of NASICON-Structured cathode enables High-Rate and stable sodium storage - Xi Liu; Chengcheng Zhu; Tianhe Xu; Chang Li; Xinyu Guo; Nan Jiang; Yan Chen; Yushuang Xu; Runduo Zhu; Wenxia Zou; Wenjun Deng; Rui Li (Chemical Engineering Journal, 2024)

Dialdehyde starch cross-linked aminated gelatin sponges with excellent hemostatic performance and biocompatibility - Yu-He Zhu; Chen-Yu Zhou; Xu Peng; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Xiao-Jie Ju; Liang-Yin Chu (Carbohydrate Polymers, 2024)

Investigating thermal exposure during daily walking through a human-scale approach: An analysis of a hot summer in Wuhan - Jiwei Xu; Xinkun Xu; Zimeng Wang; Huiting Chen; Qiran Ren; He Huang; Yao Cui; Rui An; Yaolin Liu (Building and Environment, 2024)

Arbuscular Mycorrhizal Fungi Enhance Tolerance to Drought Stress by Altering the Physiological and Biochemical Characteristics of Sugar Beet - Zeyuan Cui; Rui Chen; Tai Li; Bingchen Zou; Gui Geng; Yao Xu; Piergiorgio Stevanato; Lihua Yu; Vadim N. Nurminsky; Jiahui Liu; Yuguang Wang (Sugar Tech, 2024)

Effects of Different Concentrations of Weak Acid Fracturing Fluid on the Microstructure of Coal - Gan Rui; Zuo Shaojie; Si Junting; Liu Chengwei; Tian Feng; Jiang Zhizhong; Wang Changwei; Peng Shouqing; Xu Zhiyuan (Natural Resources Research, 2024)

RIP3 regulates doxorubicin-induced intestinal mucositis via FUT2-mediated α-1,2-fucosylation - Wei Wen; Xiaomin Hu; Jialin Liu; Fanxin Zeng; Yihua Xu; Ye Yuan; Chunyan Gao; Xueting Sun; Bo Cheng; Jue Wang; Xinli Hu; Rui-Ping Xiao; et al. (Inflammation Research, 2024)

Microbial Community Structure and Metabolism of Xinjiang Fine-Wool Sheep based on High-Throughput Sequencing Technology - Rui Yao; Fulin Li; Xuyang Dong; Yueren Xu; Ruirui Hu; Limin Wang; Kuojun Cai; Xiaogang Liu; Wei Ni; Ping Zhou; Shengwei Hu (Current Microbiology, 2024)

Lightweight seamless lane-level positioning with the integration of BDS-3 PPP-B2b and VINS: a case study using smartphone - Rui Shang; Chengfa Gao; Xiaolin Meng; Zhenhao Xu; Qi Liu; Qianqian Chen; Xiangdong An (GPS Solutions, 2024)

Digital twin-driven safety management and decision support approach for port operations and logistics - Kan Wang; Hang Xu; Hao Wang; Rui Qiu; Qianqian Hu; Xiaolei Liu (Frontiers in Marine Science, 2024)
Ports are of great significance in processing cargo containers and facilitating global marine logistics. Nevertheless, the susceptibility of the container shipping network for hazardous cargo is likely to intensify in the event of a significant disruption at a major port, such as adverse weather conditions, inadequate management practices, or unforeseen catastrophes. Such situations require the deployment of port protection emergency response and prevention in advance. This study proposes a digital twin (DT) model that employs extensive and trajectory data within containers to comprehensively analyze the occurrence of hazardous cargo failures within the port storage process. The virtual models of physical entities in the port are created through a data-driven approach, and the behavior of these entities in a port environment with big data is then simulated. A combination of a convolutional neural network (CNN) and a long short-term memory (LSTM) algorithm is employed to provide predictions for the service layer of the DT system. The predicted correlation coefficients of temperature and humidity in the container reach 0.9855 and 0.9181, respectively. The developed system driven by DT models integrated with a CNN and the LSTM algorithm can more effectively assist the safety manager in achieving prevention in port operations. This study enables marine authorities and decision-makers to optimize emergency procedures, thereby reducing the probability of accidents in port operations and logistics.

Short-term exposure to ambient fine particulate matter constituents and myocardial infarction mortality - Yingxin Li; Bing Lu; Jing Wei; Qingqing Wang; Wancheng Ma; Rui Wang; Ruijun Xu; Zihua Zhong; Lu Luo; Xi Chen; Ziquan Lv; Suli Huang; et al. (Chemosphere, 2024)

Extracellular-proton-transfer driving high energy-conserving methanogenesis in anaerobic digestion - Haoyu Liu; Ying Xu; Xinyu Li; Hong Wang; Rui Liu; Xiaohu Dai (Water Research, 2024)

Magnetic porous microspheres altering interfacial thermodynamics of sewage sludge to drive metabolic cooperation for efficient methanogenesis - Hui Geng; Ying Xu; Rui Liu; Jun Xu; Xiang Li; Dianhai Yang; Xiaohu Dai (Water Research, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Fracture stratigraphy in oil-rich shale of the Upper Xiaganchaigou Formation (upper Eocene), western Qaidam Basin - Rui Liu; Shuanglong Shi; Kunyu Wu; John N. Hooker; Guoyong Liu; Songtao Wu; Qinghui Zhang; Lu Xu; Guoxin Li; Xiucheng Tan (Marine and Petroleum Geology, 2024)

Construction of g-C3N4@Bi-MOF@BiOCl double Z-type heterojunctions for photodegradation of antibiotics under visible light irradiation: Mechanism, pathway, and toxicity assessment - Maoqin Xu; Rui Zhang; Jie He; Zixi Li; Yujie Liu; Dong Chen; Lin Peng; Yong Shu; Luming Jiang; Guixiang Zhao (Journal of Water Process Engineering, 2024)

Water–Rock reactions in the acid leaching of Uranium: Hydrochemical characteristics and reaction mechanisms - Bing Wang; Yue Luo; Xun Li; Ya–zhou Liu; Chang–rui Xu; Yu–xiu Zheng; Yan–hong Zhang; Yi–ru Zhou (Journal of Hydrology, 2024)

Farmland’s silent threat: Comprehensive multimedia assessment of micropollutants through non-targeted screening and targeted analysis in agricultural systems - Yang Qiu; Lijun Liu; Caifei Xu; Bo Zhao; Hang Lin; He Liu; Weixuan Xian; Han Yang; Rui Wang; Xingjian Yang (Journal of Hazardous Materials, 2024)

Release dynamics, risk evolution and driving mechanisms of heavy metals in superalkaline fly ash co-disposed by MSW landfill - Zhaozhi Jia; Ya Xu; Rongbin Xu; Rui Xiang; Shuna Sun; Changxin Nai; Yuqiang Liu (Environmental Pollution, 2024)

A novel anti-angiogenesis peptide in combination with cisplatin self-assembling into tube-like nanomedicine for oral treatment of gastric cancer - Linwei Chen; Qin Wang; Yong Jiang; Liu Xu; Nina Wei; Chang Lu; Chenqi Chang; Dandan Song; Yutong Wang; Li Wu; Weidong Li; Xiaobin Jia; et al. (Chemical Engineering Journal, 2024)

Research progress of natural polysaccharide-based and natural protein-based hydrogels for bacteria-infected wound healing - Huiqing Xu; Yilin Che; Rui Zhou; Lu Wang; Jiaying Huang; Wei Kong; Chang Liu; Lei Guo; Yixin Tang; Xue Wang; Xi Yang; Erlei Wang; et al. (Chemical Engineering Journal, 2024)

An information quantity and machine learning integrated model for landslide susceptibility mapping in Jiuzhaigou, China - Yunjie Yang; Rui Zhang; Tianyu Wang; Anmengyun Liu; Yi He; Jichao Lv; Xu He; Wenfei Mao; Wei Xiang; Bo Zhang (Natural Hazards, 2024)

Farrerol Alleviates Cerebral Ischemia–Reperfusion Injury by Promoting Neuronal Survival and Reducing Neuroinflammation - Rui Zhao; Xin Zhou; Zhiyuan Zhao; Wenhao Liu; Mengfei Lv; Zhaolong Zhang; Changxin Wang; Tianli Li; Zixiong Yang; Qi Wan; Rui Xu; Yu Cui (Molecular Neurobiology, 2024)

In vivo manufacture and manipulation of CAR-T cells for better druggability - Rui Hou; Xiaoxue Zhang; Xu Wang; Xuan Zhao; Sijin Li; Zhangchun Guan; Jiang Cao; Dan Liu; Junnian Zheng; Ming Shi (Cancer and Metastasis Reviews, 2024)

A new algorithm of critical control rod position search in MC code - Rui Li; Yuanguang Fu; Peng Liu; Dunfu Shi; Li Deng; Haibo Xu (Annals of Nuclear Energy, 2024)

Full title: The performance evaluation of marine ecological civilization construction (MECC): A case study of coastal cities in Jiangsu Province, China - Yang Yang; Dingwu Liu; Rui Xu; Zhuona Li; Chenwei Shi; Xiaodong Zhu; Xiang Sun (Ocean & Coastal Management, 2024)

Exploring the relationship between land use change patterns and variation in environmental factors within urban agglomeration - Rui Xiao; Hanyu Yin; Ruoxin Liu; Zhonghao Zhang; Sukhbaatar Chinzorig; Kun Qin; Wenfang Tan; Yi Wan; Zhi Gao; Chen Xu; Lumeng Liu; Tao Jia (Sustainable Cities and Society, 2024)

Feasibility of nanofiltration process for efficient separation of gallic acid from the extract of black tea in aqueous solution - Yiwei Dong; Rui Zhao; Chunyan Xu; Jinxin Liu; Zhiguo Dong; Ziqi Chen; Jinfeng He; Chuanrun Li; Haiyang Yan; Li Sun (Journal of Water Process Engineering, 2024)

Exploring the spatial patterns of landslide susceptibility assessment using interpretable Shapley method: Mechanisms of landslide formation in the Sichuan-Tibet region - Jichao Lv; Rui Zhang; Age Shama; Ruikai Hong; Xu He; Renzhe Wu; Xin Bao; Guoxiang Liu (Journal of Environmental Management, 2024)

Artificial phytoremediation solar interface evaporator for efficient heavy metal salt separation and saline soil remediation - Yaping Xu; Chenyang Dang; Xiangkun Elvis Cao; Yunteng Cao; Jiu Huang; Yuxiang Xu; Minghui Shan; Rui Liu; Peng Li; Guiyin Xu; Meifang Zhu (Journal of Environmental Chemical Engineering, 2024)

Energy control and block performance optimization of bench blasting - Ming Tao; Yuanquan Xu; Rui Zhao; Yulong Liu; Chengqing Wu (International Journal of Rock Mechanics and Mining Sciences, 2024)

Exploring the neural correlates of fat taste perception and discrimination: Insights from electroencephalogram analysis - Tianyi Yang; Peng Zhang; Jin Hu; Wei Xu; Wei Jiang; Rui Feng; Yajun Lou; Xiaofei Jin; Zhiyu Qian; Fan Gao; Keqiang Gao; Rui Liu; et al. (Food Chemistry, 2024)

Engineering marine phospholipid nanoliposomes via glycerol-infused proliposomes: Mechanisms, strategies, and versatile applications in scalable food-grade nanoliposome production - Dong-wen Fu; Hang Xu; Rui-qi Sun; Xue-li Liu; Zhe Ji; Da-yong Zhou; Liang Song (Food Chemistry, 2024)

Ile-Pro-Pro attenuates sympathetic activity and hypertension - Jun-Liu Chen; Rui Ge; Xiu-Zhen Li; Yue Zhang; Wen-Yuan Hao; Na Li; Zhi-Qin Xu; Qi Chen; Yue-Hua Li; Guo-Qing Zhu; Xiao Tan (Journal of Physiology and Biochemistry, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

An “off-on-enhanced on” electrochemiluminescence biosensor based on resonance energy transfer and surface plasmon coupled 3D DNA walker for ultra-sensitive detection of microRNA-21 - Meng-Li Li; Ming-Yu Zhong; Jia Zhang; Yi-Jia Zhang; Yu-Qi Zhang; Yan Liu; Xiang-Kai Li; Shu-Tian Gan; Gong-Rui Meng; Li Mi; Yong-Hong Hu; Fang Zhang; et al. (Analytica Chimica Acta, 2024)

Projected changes in wind erosion climatic erosivity over high mountain Asia: results from dynamical downscaling outputs - Rui Mao; Yuanyuan Xu; Jianze Zhu; Xuezhen Zhang; Shuaifeng Song; Dao-Yi Gong; Lianyou Liu; Peijun Shi (Asia-Pacific Journal of Atmospheric Sciences, 2024)

Phylogenetic origin of an insect fauna at the boundary of the Palaearctic and Oriental realms: Evidence from ‘site‐based’ mitogenomics - Rui‐E Nie; Lu‐Lu Li; Anderson Feijó; Mei‐Xia Yang; Ming Bai; Thomas J. Creedy; Xu Jin; Jia‐Sheng Hao; Yong‐Ying Ruan; Hua‐Xi Liu; Beulah H. Garner; Ladislav Bocak; et al. (Journal of Biogeography, 2024)
Aim Knowledge of taxonomy and species distributions in highly diverse lineages of invertebrates remains too incomplete for the study of biogeographical patterns at the global scale. This limits the understanding of processes leading to the formation and maintenance of boundaries between major biogeographical realms. Site‐based metagenomic approaches may provide an alternative source of data for inference of historical processes of in situ speciation and interchange among biogeographical regions. We applied the methodology to explore the historical biogeography of the Qinling Mountains at the boundary of the Oriental and Palaearctic regions. Location The focal area in the Qinling Mountains; sites in Borneo, Panama, and Spain, representing the Oriental, Neotropical and Palaearctic faunas. Time Period Contemporary. Major Taxa Studied Chrysomelidae, a group of ~40,000 species with worldwide distribution. Methods Mass‐trapped insects were subjected to deep Illumina DNA sequencing and mitochondrial genome assembly, followed by phylogenetic analysis and historical biogeographical inference on a dated tree. The methodology produced 622 mitogenomes (304 newly sequenced) each representing a morphologically distinct species. Results Ancestral area reconstruction revealed that the Qinling fauna is a composite of distinct clades that, respectively, have Oriental or Palaearctic ancient origins, while in situ speciation and local clade formation were limited. The global diversity of Chrysomelidae consists of regionalised deep clades at the level of the major zoogeographic realms, which remain recognisable where these realms abut in the Qinling mountains. Yet, the Qinling fauna is clearly distinct from the source areas although local lineage ages are generally Main Conclusions The Qinling fauna is a composite of clades that have either Oriental or Palaearctic origin, indicating the important role of immigration at the realm boundary. Global site‐based phylogenetic analyses based on metagenomic sequencing can address previously intractable questions about the historical biogeography of poorly studied groups even without a fully developed taxonomy.

Micronutrient perspective on COVID-19: Umbrella review and reanalysis of meta-analyses - Yafei Xie; Jianguo Xu; Dan Zhou; Mingyue Guo; Mengxiang Zhang; Ya Gao; Ming Liu; Jiyuan Shi; Kelu Yang; Qingyong Zheng; Liang Zhao; Yu Qin; et al. (Critical Reviews in Food Science and Nutrition, 2024)

SAD2 functions in plant pathogen Pseudomonas syringae pv tomato DC3000 defense by regulating the nuclear accumulation of MYB30 in Arabidopsis thaliana - Tiantian Shi; Yuan Zheng; Rui Wang; Sha Li; Andi Xu; Luoying Chen; Yuanhang Liu; Rong Luo; Chenchen Huang; Yinglu Sun; Jinfeng Zhao; Xiaoying Guo; et al. (Plant Science, 2024)

Ent-eudesmane sesquiterpenoids with anti-neuroinflammatory activity from the marine-derived fungus Eutypella sp. F0219 - Zhong-Ping Jiang; Rui Su; Meng-Ting Chen; Jun-Yi Li; Han-Yu Chen; Lu Yang; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Wan-Shan Li; Yong Rao; Ling Huang (Phytochemistry, 2024)

The non-linear associations between blood manganese level and sarcopenia in patients undergoing maintenance hemodialysis: A multicenter cross-sectional study - Rui Hu; Qiangying Zeng; Qingdong Xu; Hongmei Zhou; Rongshao Tan; Xiaoshi Zhong; Yan Liu; Yi Li; Yun Liu (Journal of Trace Elements in Medicine and Biology, 2024)

Prediction and explanation of debris flow velocity based on multi-strategy fusion Stacking ensemble learning model - Tianlong Wang; Keying Zhang; Zhenghua Liu; Tianxing Ma; Rui Luo; Hao Chen; Xu Wang; Wei Ge; Hongyue Sun (Journal of Hydrology, 2024)

Per- and polyfluoroalkyl substances and human health outcomes: An umbrella review of systematic reviews with meta-analyses of observational studies - Wei-Yi Xing; Jia-Nan Sun; Fang-Hua Liu; Li-Shen Shan; Jia-Li Yin; Yi-Zi Li; He-Li Xu; Yi-Fan Wei; Jia-Xin Liu; Wen-Rui Zheng; Ying-Ying Zhang; Xin-Jian Song; et al. (Journal of Hazardous Materials, 2024)

Electrochemiluminescence detection of diazinon in vegetables based on the synergistic interaction of WO3-x dots with Au@SiO2 nanocapsules - Wenzheng Liu; Haifang Wang; Peisen Li; Chengqiang Li; Donghan Li; Zhenying He; Yuhao Zhang; Jingcheng Huang; Jin Hua; Rui Xu; Lianming Xia; Yemin Guo; et al. (Food Chemistry, 2024)

Inoculation fermentation with Lactobacillus fermentum L28 and Staphylococcus epidermidis S24 for improving the protein degradation of air-dried goose - Mangang Wu; Chen Gu; Likun Duan; Peipei Yin; Tianhao Zhu; Yuyu Xu; Qing Yin; Rui Liu; Qingfeng Ge; Hai Yu (Food Chemistry, 2024)

The role of hormones in the regulation of lactogenic immunity in porcine and bovine species - Kexin Hua; Dan Liu; Qianshuai Xu; Yuna Peng; Yu Sun; Rongrong He; Rui Luo; Hui Jin (Domestic Animal Endocrinology, 2024)

A NIR-II quantum dot-assisted dual-color imaging strategy enables simultaneous tracking of two subtypes of extracellular vesicles in vivo - Xing-Chi Liu; He-Jing Zhang; Rui Xu; Jing Liu; Hou-Fu Xia; Qi-Hui Xie; Zhi-Quan Tian; Zi-Li Yu; Gang Chen (Chemical Engineering Journal, 2024)

Metagenomic data highlight shifted nitrogen regime induced by wetland reclamation - Kexin Li; Nannan Wang; Fenghui Yuan; Xinhao Zhu; Yunjiang Zuo; Jianzhao Liu; Ziyu Guo; Ying Sun; Rui Su; Lihua Zhang; Sergei Lupakov; Yanyu Song; et al. (Biology and Fertility of Soils, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Effects of pH-varying thermal modification on sewage sludge: A focus on releasing nitrogen- and phosphorus-containing substances - Rui Liu; Ying Xu; Jiachang Cao; Hui Geng; Renjie Chen; Haoyu Liu; Yongdong Chen; Shijie Yuan; Xiaohu Dai (Water Research, 2024)

Tracing the impacts of ecological water replenishment on the sources and transformation of groundwater nitrate through isotope and microbial analysis - Congchao Xu; Bowen Shi; Zihao Jia; Di Liu; Weiwu Hu; Chuanping Feng; Rui Li (Science of The Total Environment, 2024)

A new Late Devonian plant assemblage in West Junggar, Xinjiang, China and its floral evolution during the Devonian - Bing-Cai Liu; Kai Wang; Rui-Wen Zong; Jiao Bai; Yao Wang; Ning Yang; Yi Wang; Hong-He Xu (Review of Palaeobotany and Palynology, 2024)

Celastrol induced the autophagy of spermatogonia cells contributed to tripterygium glycosides-related testicular injury - Dong-Xiao Cui; Ze-Chen Niu; Xi Tang; Chun-Zhou Cai; Ding-Qiao Xu; Rui-Jia Fu; Wen-Juan Liu; Yu-Wei Wang; Yu-Ping Tang (Reproductive Toxicology, 2024)

Neoproterozoic back-arc and arc-type magmatisms in the Rutong and Shiquanhe region, west of Tibet: Tectonic implications for the early-stage evolution of the Bangong-Nujiang suture zone and North Lhasa terrane - Xu Zhang; Di-Zhu Cai; Harald Furnes; Wei-Liang Liu; Rui Wang; Wei Li; Xing Liao; Chi Yan; Ru-Xin Ding; Yun Zhong (Precambrian Research, 2024)

Synergistic effects of Co-pyrolysis on the immobilization and transformation of lead (Pb), chromium (Cr), nickel (Ni), and fluorine (F) in phosphogypsum-biomass mixtures - Minjie He; Rui Xu; Guangfei Qu; Xianyu Fu; Xinxin Liu; Hanghang Wang; Yaxin Tian; Chenyang Yin (Journal of Environmental Management, 2024)

Synergistic multifactor influence and management of commercial vanadium-based catalyst lifetimes - Yi-feng Xu; Xiao-jing Liu; Rui-tang Guo; Tong Wu; Hong-lei Ding; Dong Ye; Wei-guo Pan (Fuel, 2024)

Chemical constituents from the leaves of Fraxinus hubeiensis, an endemic plant from China - Li-Min Gong; Hong-Xia Tang; Ya-Jie Li; Rui-Ding Wen; Xin-Yi Liu; Yu-Wen Deng; Qing-Lai Wu; Zhi-Feng Zhang; Xu-Dong Zhou; Wei Wang (Biochemical Systematics and Ecology, 2024)

Climate and soil: Key Drivers of Plant Traits and Community Functional Differences in the Lakeshore Wetlands of Northern China - Rui Zhang; Zhichao Xu; Huamin Liu; Hongbo Yu; Feng Niu; Haitao Fang; Linqian Ma; Yunhao Wen; Lu Wen; Yi Zhuo; Lixin Wang (Wetlands, 2024)

Adaptive strategies of high and low nucleic acid prokaryotes in response to declining resource availability and selective grazing by protozoa - Chen Hu; Liuqian Yu; Xiaowei Chen; Jihua Liu; Yao Zhang; John Batt; Xilin Xiao; Qiang Shi; Rui Zhang; Tingwei Luo; Nianzhi Jiao; Dapeng Xu (Science China Earth Sciences, 2024)
Prokaryotes play a fundamental role in global ocean biogeochemical cycles. However, how the abundance and metabolic activity of ecologically distinct subgroups (i.e., high nucleic acid (HNA) and low nucleic acid (LNA) cells), and their regulating factors, change in response to changing marine environmental conditions remains poorly understood. Here, we delved into the time-evolving dynamic responses of the HNA and LNA prokaryotic subgroups to declining resource availability and selective grazing by protozoa by conducting a 73-day incubation experiment in a large-volume (117,000 L) macrocosm that facilitates community-level exploration. We found that the metabolic activity of the HNA subgroup was higher than that of the LNA subgroup when the macrocosm was resource replete but that the HNA subgroup declined more rapidly than the LNA subgroup as the resources became increasingly scarce, leading to a steadily increasing contribution of LNA cells to prokaryotic activity. Meanwhile, as resources in the macrocosm became limited, protozoan grazing preference shifted from the HNA to the LNA subgroup and the contributions of the LNA subgroup to the carbon flow within the macrocosm increased. The findings highlight the resilience of LNA cells in resource-limited environments, illuminate the critical role of selective grazing by protozoa in balancing distinct prokaryotic subgroups under changing resource conditions, and demonstrate the complex and adaptive interactions between protozoa and prokaryotes across diverse environmental contexts.

Multiple signal-enhanced electrochemiluminescence aptamer sensors based on carboxylated ruthenium (II) complexes for acetamiprid detection - Chenchen Li; Bingxin Zhang; Zhourui Wu; Ying Liu; Rui Xu; Yaoguang Wang; Yong Zhang; Qin Wei (Analytica Chimica Acta, 2024)

Two new cytochalasins from the endophytic fungus Xylaria sp. GDGJ-77B - Zhao-Long Xu; Ben-Chao Li; Li-Li Huang; Liu-Xia Lv; Yan Luo; Wei-Feng Xu; Rui-Yun Yang (Natural Product Research, 2024)

Current status and trends in island ecosystem services research: A bibliometric analysis from 2000 to 2023 - Rui Du; Baiqiong Liu; Min Xu (Marine Policy, 2024)

Evaporation-driven interfacial restructuring induces highly efficient methanogenesis of waste biomass - Ying Xu; Haoyu Liu; Hui Geng; Rui Liu; Xiaohu Dai (Water Research, 2024)

Magnetic porous microspheres enhancing the anaerobic digestion of sewage sludge: Synergistic free and attached methanogenic consortia - Hui Geng; Ying Xu; Rui Liu; Dianhai Yang; Xiaohu Dai (Water Research, 2024)

Assessing ammonium pollution and mitigation measures through a modified watershed non-point source model - Feng Han; Qing Tian; Nengwang Chen; Zhaoping Hu; Yao Wang; Rui Xiong; Peng Xu; Wei Liu; Alejandra Stehr; Ricardo O. Barra; Yi Zheng (Water Research, 2024)

Anthropogenic-induced ecological risks on marine ecosystems indicated by characterizing emerging pollutants in Pearl River Estuary, China - He Liu; Bo Zhao; Meng Jin; Rui Wang; Zirong Ding; Xiong Wang; Wenjie Xu; Qianghua Chen; Rizhu Tao; Jianping Fu; Danping Xie (Science of The Total Environment, 2024)

Release potential, neglected leakage and reduction countermeasures of COD and Ammonia in MSWLs - Haonan Yang; Qifei Huang; Ya Xu; Rui Xiang; Yuqiang Liu (Science of The Total Environment, 2024)

Biomineralization of phosphorus during anaerobic treatment of distillery wastewaters - Lei Zhang; Yiyang Yuan; Chengyuan Li; Yingdi Zhang; Huijuan Sun; Rui Xu; Yang Liu (Science of The Total Environment, 2024)

Synergistic effects of chemical additives and mature compost on reducing H2S emission during kitchen waste composting - Yongdi Liu; Haihou Wang; Hao Zhang; Yueyue Tao; Rui Chen; Sheng Hang; Xiaoyan Ding; Meidi Cheng; Guochun Ding; Yuquan Wei; Ting Xu; Ji Li (Journal of Environmental Sciences, 2024)

Insights into “wheat aroma”: Analysis of volatile components in wheat grains cultivated in saline–alkali soil - Qianqian Sun; Rui Zhang; Yu Liu; Liya Niu; Hongyan Liu; Peifang Ren; Bianna Xu; Boli Guo; Bo Zhang (Food Research International, 2024)

Cytotoxic withanolides from the stems and leaves of Physalis ixocarpa - Ke Xiang; Yan Liu; Rui Zhu; Yang Xu; Dejuan Sun; Yueying Yang; Yushu Yan; Bingyou Yang; Hua Li; Lixia Chen (Food Chemistry, 2024)

Factors controlling accumulation and bioavailability of selenium in paddy soils: A case study in Luxi County, China - Zhangqian Xu; Weijun Zhou; Yuzhou Zhou; Haojie Cui; Rui Liu; Guiduo Shang (Environmental Pollution, 2024)

BDTX-189, a novel tyrosine kinase inhibitor, inhibits cell activity via ERK and AKT pathways in the EGFR C797S triple mutant cells - Rui Wang; Wenrui Cui; Lanxin Li; Xiangkai Wei; Chunhong Chu; Guoliang Zhang; Chenxue Liu; Huixia Xu; Chenyang Liu; Ke Wang; Yanming Li; Lei An (Chemico-Biological Interactions, 2024)

A Senescence-Associated Secretory Phenotype of Bone Marrow Mesenchymal Stem Cells Inhibits the Viability of Breast Cancer Cells - Meng Li; Jie-Xi Liu; Bo Ma; Jin-Yu Liu; Ji Chen; Fang Jin; Cheng-Hu Hu; Hao-Kun Xu; Chen-Xi Zheng; Rui Hou (Stem Cell Reviews and Reports, 2024)

Analysis on the causes of massive stranding of Yellow Sea green tide on Lianyungang and Rizhao coasts in 2022 - Lingjuan Wu; Juan Huang; Yi Ding; Guiyan Liu; Shuai Huang; Song Gao; Chao Yuan; Jiangling Xu; Ping Wu; Rui Huang; Ruobing Wen; Jie Mei (Journal of Oceanology and Limnology, 2024)

Exquisite visualization of mitophagy and monitoring the increase of lysosomal micro-viscosity in mitophagy with an unusual pH-independent lysosomal rotor - Rui Yang; Wei He; Changxin Zhu; Xifeng Yang; Yawei Kuang; Tao Zhu; Jingyang Xu; Yuang Zhao; Tingwang Jiang; Yushen Liu; Mengmeng Wei (Analytica Chimica Acta, 2024)

Power law in species–area relationship overestimates bacterial diversity in grassland soils at larger scales - Biao Zhang; Kai Xue; Wenjing Liu; Shutong Zhou; Shipeng Nie; Yichao Rui; Li Tang; Zhe Pang; Linfeng Li; Junfu Dong; Cong Xu; Lili Jiang; et al. (Global Ecology and Biogeography, 2024)
Aim Species–area relationships (SAR) are widely utilized for estimating the species richness and its spatial turnover across various scales. Despite the prevalent characterization of SAR using the power law in many microbial community studies, its efficacy remains unvalidated. This study aims to characterize the microbial SAR and its mechanisms in alpine grassland soils on the Qinghai‐Tibet Plateau (QTP). Location Qinghai‐Tibet Plateau, China. Time Period August 2014. Major Taxa Studied Soil bacteria. Methods Soil samples were collected from five alpine grassland sites on the QTP. Employing a nested sampling strategy at each site, soil samples were collected in plot sizes ranging from 0.5 × 0.5 m 2 to 2048 × 2048 m 2 . Soil bacterial communities were analysed by sequencing 16S ribosomal RNA gene amplicons using an Illumina MiSeq. Results The bacterial SAR exhibited a logarithmic power law ( R 2 : 0.952–0.999), outperforming the power law ( R 2 : 0.701–0.852). Consequently, the most widely adopted power law led to an overestimation of species richness by up to 15.07% in areas >256 × 256 m 2 , and the regional maximum theoretical richness based on Chao1 by up to 9.88%. Mechanistically, the passive sampling hypothesis was refuted through the rarefied species richness analysis, and the disproportionate effect hypothesis was rejected based on analyses of the effective numbers of species number conversions for the probability of interspecific encounters ( S PIE ). Notably, Pearson and multiple linear regression analyses indicated that the spatial turnover of bacterial richness was determined by the environmental heterogeneity ( R 2 : 0.855–0.999), rather or better than environmental variables themselves, supporting the ‘environment heterogeneity hypothesis’. Main Conclusions Soil bacterial SAR in alpine grasslands exhibited a logarithmic power relationship. Spatial turnover was primarily governed by the environmental heterogeneity. In contrast, the traditional power law leads to an overestimation of soil bacterial diversity at the regional scale.

Vanadium isotope evidence for seawater contribution to V enrichment/mineralization in early Cambrian metalliferous black shales - Lin-Hui Dong; Wei Wei; Lingang Xu; Yi-Bo Lin; Ze-Rui Liu; Songqi Pan; Zhenhua Jing; Fang Huang (Science Bulletin, 2024)

DeepWMH: A deep learning tool for accurate white matter hyperintensity segmentation without requiring manual annotations for training - Chenghao Liu; Zhizheng Zhuo; Liying Qu; Ying Jin; Tiantian Hua; Jun Xu; Guirong Tan; Yuna Li; Yunyun Duan; Tingting Wang; Zaiqiang Zhang; Yanling Zhang; et al. (Science Bulletin, 2024)

Competition between ocean thermal structure and tropical cyclone characteristics modulates ocean environmental responses in the Yellow and Bohai Seas - Xiuting Wang; Jiagen Li; Liang Sun; Mengyuan Xu; Haihua Liu; Rui Liu (Marine Environmental Research, 2024)

Hollow α-Bi2O3/TiO2 nanotube arrays hierarchical heterojunction with strong interface interaction for efficient photocatalytic ciprofloxacin degradation - Bingrui Ma; Yuxin Zha; Rui Xu; Jincheng Li; Yajing Guo; Jie Liu; Songxue Wang; Boyin Yan; Yunlong Lan; Baoxiu Zhao; Haijiao Xie (Journal of Water Process Engineering, 2024)

Detecting anomalous commuting patterns: Mismatch between urban land attractiveness and commuting activities - Zhaomin Tong; Ziyi Zhang; Rui An; Yaolin Liu; Huiting Chen; Jiwei Xu; Shihang Fu (Journal of Transport Geography, 2024)

Experimental analysis of a CO2 closed heat pump drying system combined with rotary dehumidification for drying banana slices drying - Zhili Sun; Qianqian Wang; Yingying Yuan; Dandan Wang; Qiang Zhou; Chunwei Xu; Kexin Meng; Haowei Peng; Lei Yan; Rui Jin; Lei Li; Haowei Liu; et al. (International Journal of Refrigeration, 2024)

The isomorphous substitution of Si(4Al) with P in FAU zeolite and its stabilization effect - Qiang Zhang; Hongjuan Zhao; Xingyu Liu; Rui Li; Tian Xia; Yue Ma; Yuren Wang; Kang Chen; Jiujiang Wang; Penghui Zeng; Honghai Liu; Chaowei Liu; et al. (Chemical Engineering Journal, 2024)

A renal-targeted gene delivery system derived from spermidine for arginase-2 silencing and synergistic attenuation of drug-induced acute kidney injury - Xu-Rui Gu; Kun Liu; Yi-Xuan Deng; Bi-Xiao Xiang; Ling-Yun Zhou; Wen-Jun Yin; Jia-Xin Huang; Ying-Cai Meng; Dian-Ke Li; Rui-Man Que; Zhi-Yao Tang; Guang-Liang Zhou; et al. (Chemical Engineering Journal, 2024)

Scale-up of microalgal systems for decarbonization and bioproducts: Challenges and opportunities - Peilun Xu; Shengxi Shao; Jun Qian; Jingjing Li; Rui Xu; Jin Liu; Wenguang Zhou (Bioresource Technology, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Analysis of landslide deformation in eastern Qinghai Province, Northwest China, using SBAS-InSAR - Haibo Tian; Pinglang Kou; Qiang Xu; Yuxiang Tao; Zhao Jin; Ying Xia; Jiangfan Feng; Rui Liu; Yongcheng Gou (Natural Hazards, 2024)

Salinity as a key factor affecting viral activity and life strategies in alpine lakes - Lin Zang; Yongqin Liu; Nianzhi Jiao; Kevin Xu Zhong; Xuanying Song; Yunlan Yang; Lanlan Cai; Keshao Liu; Guannan Mao; Mukan Ji; Rui Zhang (Limnology and Oceanography, 2024)
Viruses are major players in the biosphere, yet little is known about their dynamics and life strategies in alpine lakes, particularly those on the Tibetan Plateau. We investigated microbial abundance, viral dynamics, and viral life strategies in 10 high‐altitude Tibetan lakes and found that they harbor high levels of active viruses. Salinity was identified as a crucial factor influencing viral abundance, dynamics, as well as viral life strategies. Lytic and lysogenic viral productions in moderate‐ and high‐salinity lakes were significantly higher than those in freshwater lakes. A trade‐off between viral life strategies resulted in a switch from lysis to lysogeny in high‐salinity lakes. Virus‐mediated cell lysis and virus decay in sampled Tibetan lakes could release about 162.72 and 2.84 μ g C L −1 d −1 , respectively. These findings revealed the crucial role of viruses in the carbon cycle of Tibetan lakes, and a switch in viral life strategies may impact their contribution to the carbon cycle. The potential impact of salinity changes triggered by climate change on the carbon cycle in alpine lakes worldwide is highlighted.

Correction to: A new strategy for groundwater level prediction using a hybrid deep learning model under Ecological Water Replenishment - Zihao Jia; Qin Zhang; Bowen Shi; Congchao Xu; Di Liu; Yihong Yang; Beidou Xi; Rui Li (Environmental Science and Pollution Research, 2024)

Phenolic components from the fruits of Solanum xanthocarpum with anti-inflammatory activity - Yan Liu; Rui Yang; Hai-Dan Zou; Zhen-Peng Xu; Juan Pan; Jia-Tong Wu; Wei Guan; Zhi-Chao Hao; Adnan Mohammed Algradi; Hai-Xue Kuang; Bing-You Yang (Natural Product Research, 2024)

Unraveling sources of cyanate in the marine environment: insights from cyanate distributions and production during the photochemical degradation of dissolved organic matter - Rui Wang; Jihua Liu; Yongle Xu; Li Liu; Kenneth Mopper (Frontiers in Marine Science, 2024)
Cyanate is a nitrogen and energy source for diverse marine microorganisms, playing important roles in the nitrogen cycle. Despite the extensive research on cyanate utilization, the sources of this nitrogen compound remain largely enigmatic. To unravel the sources of cyanate, distributions and production of cyanate during photochemical degradation of natural dissolved organic matter (DOM) were investigated across various environments, including freshwater, estuarine, coastal areas in Florida, and the continental and slope regions of the North American mid-Atlantic Ocean (NATL). Cyanate production was also examined during the photochemical degradation of exudates from a typical strain of Synechococcus , an important phytoplankton component. To deepen our understanding of the sources and production mechanisms of cyanate, its production was assessed during the photochemical degradation of a natural seawater DOM supplemented with five nitrogen–containing compounds with distinguishing structures and functional groups. Generally, cyanate exhibited higher concentrations in the Florida coastal, estuarine, and freshwater environments than the NATL. However, cyanate distribution did not consistently align with its production rates. Despite significantly low concentrations in the NATL, DOM from this region exhibited cyanate production rates comparable to estuarine and Florida coastal environments. Although relatively high cyanate concentrations were observed in the freshwaters, DOM in this environment exhibited very low cyanate production rates. A highly significant correlation was observed between cyanate and chlorophyll a (Chl a ) concentrations in these areas. Moreover, in most estuarine and NATL stations, cyanate concentration and production rate in the Chl a maximum layer were significantly higher than in other layers. Cyanate was produced during the photochemical degradation of the Synechococcus exudates. The cyanate production was significantly enhanced when the natural seawater DOM was supplemented with GlycylGlycine, 4-(methylamino) benzoic acid, 4-[ethyl(methyl)amino] benzaldehyde or methyl 2-aminobenzoate. Our study implies that photochemical degradation of marine DOM, especially phytoplankton-derived DOM, is a substantial source of cyanate in the ocean. Additionally, cyanate may form during the degradation of peptides and small aromatic compounds in DOM, providing novel insights into the nitrogen cycle.

A novel ZnCo2O4/BiOBr p-n/Z-scheme heterojunction photocatalyst for enhancing photocatalytic activity - Tao Xiong; Qi Feng; Cimei Fang; Rui Chen; Yanxi Wang; Longjun Xu; Chenglun Liu (Environmental Science and Pollution Research, 2024)

A new strategy for groundwater level prediction using a hybrid deep learning model under Ecological Water Replenishment - Zihao Jia; Qin Zhang; Bowen Shi; Congchao Xu; Di Liu; Yihong Yang; Beidou Xi; Rui Li (Environmental Science and Pollution Research, 2024)

Manganese disrupts the maturation and degradation of axonal autophagosome leading to hippocampal synaptic toxicity in mice via the activation of LRRK2 on phosphorylation of Rab10 - Zhuo Ma; Kuan Liu; Rui-feng Zhang; Zi-xin Xie; Wei Liu; Bin Xu (Science of The Total Environment, 2024)

Modulator of TMB-associated immune infiltration (MOTIF) predicts immunotherapy response and guides combination therapy - Zheng-Yu Qian; Yi-Qian Pan; Xue-Xin Li; Yan-Xing Chen; Hao-Xiang Wu; Ze-Xian Liu; Martin Kosar; Jiri Bartek; Zi-Xian Wang; Rui-Hua Xu (Science Bulletin, 2024)

Constructing high-resolution fingerprints and analyzing complex pollution source of electronic waste recycling base - Rui Wang; Lu Zhan; Zhenming Xu; Yukun Liu (Resources, Conservation and Recycling, 2024)

Topological spin-orbit-coupled fermions beyond rotating wave approximation - Han Zhang; Wen-Wei Wang; Chang Qiao; Long Zhang; Ming-Cheng Liang; Rui Wu; Xu-Jie Wang; Xiong-Jun Liu; Xibo Zhang (Science Bulletin, 2024)

First insights into the bioaccumulation, biotransformation and trophic transfer of typical tetrabromobisphenol A (TBBPA) analogues along a simulated aquatic food chain - Chuan-Sheng Sun; Sheng-Wu Yuan; Rui Hou; Si-Qi Zhang; Qian-Yi Huang; Lang Lin; Heng-Xiang Li; Shan Liu; Yuan-Yue Cheng; Zhi-Hua Li; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Endophytic Enterobacter sp. YG-14 mediated arsenic mobilization through siderophore and its role in enhancing phytostabilization - Jiawei Chen; Xuan Zhang; Min Kuang; Kunpeng Cui; Ting Xu; Xuanming Liu; Rui Zhuo; Ziwei Qin; Zhigang Bu; Zhongliang Huang; Hui Li; Jing Huang; et al. (Journal of Hazardous Materials, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

New insights into the interaction of sodium hexametaphosphate with coal slime and its application in the purification of kaolin - Chengwen Wang; Yanxiu Wang; Wei Sun; Runqing Liu; Yingdi Dong; Rui Xu; Dandan Huang; Le Tao (Journal of Cleaner Production, 2024)

A quantitative model to estimate major oxide abundances on the Moon based on in situ reflectance spectral data of Chang'e missions - Zhenxing Zhao; Yazhou Yang; Xing Wu; Yang Liu; Feng Zhang; Rui Xu; Zhiping He; Yangting Lin; Yongliao Zou (Icarus, 2024)

Experimental and theoretical study on seismic behavior of a new UHPFRC sandwich wall and wall-wall joint - Ru-Rui Liu; Ran Ding; Yong-Tao Sun; Jian-Sheng Fan; Ding-Qiu Chen; Jian-Chao Xu (Engineering Structures, 2024)

Catalytic oxidation of VOCs and CO on cobalt-based Materials: Strategies and mechanisms for improving activity and stability - Yanfei Zheng; Weinuo Xu; Jining Yang; Cangpeng Shan; Yunchong Wang; Rui Han; Guolong Zang; Qingling Liu (Chemical Engineering Journal, 2024)

Biochar loaded with ferrihydrite and Bacillus pseudomycoides enhances remediation of co-existed Cd(II) and As(III) in solution - Rui Cao; Guodong Kang; Weiwen Zhang; Jihai Zhou; Wangliang Xie; Zhenzhen Liu; Li Xu; Feng Hu; Zhen Li; Huixin Li (Bioresource Technology, 2024)

Influence of atmospheric circulation on the stable isotope of precipitation in the monsoon margin region - Siyu Lu; Guofeng Zhu; Gaojia Meng; Xinrui Lin; Yuwei Liu; Dongdong Qiu; Yuanxiao Xu; Qinqin Wang; Longhu Chen; Rui Li; Yinying Jiao (Atmospheric Research, 2024)

In silico prediction and a systematic toxicology-based in vivo investigation uncovering the mechanism of aquatic toxicity caused by beta-lactam antibiotics - Ruixian Guo; Xinyan Ma; Huibo Xu; Yuanyuan Ma; Rui Zhang; Xinyan Liu; Binan Lu; Jingpu Zhang; Ying Han (Chemosphere, 2024)

Neonicotinoids: Advances in hazards of residues, screening of aptamers and design of aptasensors - Jingcheng Huang; Haifang Wang; Haowei Dong; Mengyue Liu; Lingjun Geng; Jiashuai Sun; Zhen Guo; Rui Xu; Giovanna Marrazza; Xia Sun; Yemin Guo (Trends in Food Science & Technology, 2024)

Impacts of climate change and human activity on the potential distribution of Aconitum leucostomum in China - Li Xu; Yuan Fan; Jianghua Zheng; Jingyun Guan; Jun Lin; Jianguo Wu; Liang Liu; Rui Wu; Yujia Liu (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Microbial community of municipal drinking water in Hangzhou using metagenomic sequencing - Wei Lan; Haiyang Liu; Rui Weng; Yaxiong Zeng; Jian Lou; Hongxin Xu; Yunsong Yu; Yan Jiang (Environmental Pollution, 2024)

Short-term exposure to ambient air pollution and hospital admissions for angina among older adults in South China - Luxi Xu; Ruijun Xu; Yunshao Ye; Rui Wang; Jing Wei; Chunxiang Shi; Qiaoxuan Lin; Ziquan Lv; Suli Huang; Qi Tian; Yuewei Liu (Atmospheric Environment, 2024)

Cycloaspeptide H, a cyclopentapeptide from the endophytic fungus Penicillium virgatum - Ben-Chao Li; Liu-Xia Lv; Li-Li Huang; Jia-Tong Zhou; Xi-Shan Huang; Jun Li; Rui-Yun Yang; Wei-Feng Xu (Natural Product Research, 2024)

Integrating bulk-RNA sequencing and single-cell sequencing analyses to characterize adenosine-enriched tumor microenvironment landscape and develop an adenosine-related prognostic signature predicting immunotherapy in lung adenocarcinoma - Tao Han; Jing Wu; Yafeng Liu; Jiawei Zhou; Rui Miao; Jianqiang Guo; Zhi Xu; Yingru Xing; Ying Bai; Dong Hu (Functional & Integrative Genomics, 2024)

High-density lipoprotein cholesterol is associated with lowered cognitive recovery among acute ischemic stroke patients with mild cognitive impairment - Rui Wang; Zhuomin Jiao; Anxin Wang; Yijun Zhang; Xiangxiang Hong; Shan Huang; Jin Fu; Yinglian Zhou; Yifei Wang; Chunyang Li; Yue Liu; Ke Wei; et al. (Acta Neurologica Belgica, 2024)

Mitigating cadmium accumulation in dicotyledonous vegetables by iron fertilizer through inhibiting Fe transporter IRT1-mediated Cd uptake - Zhong-Rui Xu; Ting-Ting You; Wen-Yi Liu; Kang Ye; Fang-Jie Zhao; Peng Wang (Chemosphere, 2024)

Cation exchange resins enhance anaerobic digestion of sewage sludge: Roles in sequential recovery of hydrogen and methane - Hui Geng; Ying Xu; Rui Liu; Dianhai Yang; Xiaohu Dai (Water Research, 2024)

Evolution of Silurian phytogeography, with the first report of Aberlemnia (Rhyniopsida) from the Pridoli of West Junggar, Xinjiang, China - Bing-Cai Liu; Rui-Wen Zong; Kai Wang; Jiao Bai; Yi Wang; Hong-He Xu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

New insights into micro-algal astaxanthin's effect on deoxynivalenol-induced spleen lymphocytes pyroptosis in Cyprinus carpio: Involving mitophagy and mtROS-NF-κB-dependent NLRP3 inflammasome - Lei Diao; Wenjie Liu; Yawei Xu; Bin Zhang; Lingnan Meng; Rui Yin; Huijie Chen (Fish & Shellfish Immunology, 2024)

Synthesis of amorphous-MnO2/Clinoptilolite and its utilization for NH4+-N oxidation in an anoxic environment - Caocong Liu; Yiyuan Zhuo; Yuzhe Chen; Yuanxiang Mao; Qiushi Shen; Jiangsen Ma; Rui Ma; Linsong Cheng; Fangying Ji; Xiaoyi Xu (Environmental Research, 2024)

Polyrate 2023: A computer program for the calculation of chemical reaction rates for polyatomics. New version announcement - Rubén Meana-Pañeda; Jingjing Zheng; Junwei Lucas Bao; Shuxia Zhang; Benjamin J. Lynch; José C. Corchado; Yao-Yuan Chuang; Patton L. Fast; Wei-Ping Hu; Yi-Ping Liu; Gillian C. Lynch; Kiet A. Nguyen; et al. (Computer Physics Communications, 2024)

Urea-boosted gas-exfoliation synthesis of lignin-derived porous carbon for zinc ion hybrid supercapacitors - Beichen Xue; Chaozhen Liu; Xiaofeng Wang; Yi Feng; Jiahuan Xu; Feng Gong; Rui Xiao (Chemical Engineering Journal, 2024)

Integrative transcriptomic and metabolomic analyses reveal the phenylpropanoid and flavonoid biosynthesis of Prunus mume - Rui Wu; Chengcheng Qian; Yatian Yang; Yi Liu; Liang Xu; Wei Zhang; Jinmei Ou (Journal of Plant Research, 2024)

A high-resolution α-glucosidase inhibition profiling for targeted identification of natural antidiabetic products from Lycopodiella cernua (L.) Pic. Serm and their inhibitory mechanism study - Bing-Rui Liu; Xu-Liu Shi; Jian-Kun Yan; Rui Zhao (Natural Product Research, 2023)

First report of Fusarium sacchari causing root rot of tobacco (Nicotiana tabacum L.) in China - Rui Qiu; Caihong Li; Xiaojie Li; Yingying Zhang; Chang Liu; Chenjun Li; Yuguo Chen; Jingke Bai; Min Xu; Ruifang Song; Shujun Li (Crop Protection, 2023)

Nano- and micro-plastic transport in soil and groundwater environments: Sources, behaviors, theories, and models - Jun Xu; Rui Zuo; Jinhua Shang; Guanlan Wu; Yanan Dong; Shida Zheng; Zuorong Xu; Jingchao Liu; Yunxiang Xu; Ziyi Wu; Chenxi Huang (Science of The Total Environment, 2023)

Fabrication of high permeability and antifouling composite membrane loaded with Fe3O4 nanoparticles via a magnetic field induced phase separation - Meng Zhang; Shu Jiang; Xishou Guo; Xiaobin Tang; Langming Bai; Jinlong Wang; Han Zhang; Daliang Xu; Rui Wu; Luming Liu; Heng Liang (Journal of Water Process Engineering, 2023)

Low-carbon economic analysis of a virtual power plant with wind and solar power considering the integrated flexible operation mode of a carbon capture thermoelectric unit - Chunming Zhu; Gang Bao; Rui Xu; Zhenyan Song; Yikai Liu (International Journal of Greenhouse Gas Control, 2023)

Cyanidin-3-O-glucoside from blueberry anthocyanin extracts protects ARPE-19 cells against high glucose damage via REDD1/GSK3β pathway - Rui Li; Zhan Ye; Yong-jiang Xu; Yuanfa Liu (Food Bioscience, 2023)

Conversion of highly polymerized lignin into monophenolic products via pyrolysis: A comparative study of acidic and alkaline depolymerization pretreatments using deep eutectic solvents - Xin Yue; Jinxin Lin; Terhi Suopajärvi; Otto Mankinen; Atte Mikkelson; Rui Liu; Harri Huttunen; Liheng Chen; Chunlin Xu; Ville-Veikko Telkki; Shirong Sun; Henrikki Liimatainen (Chemical Engineering Journal, 2023)

Oxalic acid-enhanced sulfamethoxazole degradation by V2O3/percarbonate process: Insights into the reactive oxygen species generation and conversion - Rui Liu; Mu-cheng Xu; Jin-yan Yang (Chemical Engineering Journal, 2023)

Research Progress on TRPA1 in Diseases - Jiajing Li; Hongfei Zhang; Qian Du; Junyu Gu; Jiangbo Wu; Qi Liu; Zhuo Li; Ting Zhang; Jingyu Xu; Rui Xie (The Journal of Membrane Biology, 2023)
For a long time, the physiological activity of TRP ion channels and the response to various stimuli have been the focus of attention, and the physiological functions mediated by ion channels have subtle links with the occurrence of various diseases. Our group has been engaged in the study of ion channels. In recent years, the report rate of TRPA1 , the only member of the TRPA subfamily in the newly described TRP channel, has been very high. TRPA1 channels are not only abundantly expressed in peptidergic nociceptors but are also found in many nonneuronal cell types and tissues, and through the regulation of Ca 2+ influx, various neuropeptides and signaling pathways are involved in the regulation of nerves, respiration, circulation, and various diseases and inflammation throughout the body. In this review, we mainly summarize the effects of TRPA1 on various systems in the body, which not only allows us to have a more systematic and comprehensive understanding of TRPA1 but also facilitates more in-depth research on it in the future. Graphical Abstract

The Role of Cystathionine-β-Synthase, H2S, and miRNA-377 in Hypoxic-Ischemic Encephalopathy: Insights from Human and Animal Studies - Chun-Yang Liu; Hisham Al-Ward; Ning Liu; Francine Ngaffo Mekontso; Wei Chen; Wenxia Gao; Chunxue Zhang; Abduh Murshed; Zi-Rui Yu; Orion Fan; Yi Eve Sun; Hui Xu (Journal of Molecular Neuroscience, 2023)

Mitochondrial dysfunction: a new molecular mechanism of intervertebral disc degeneration - Chao Song; Yulin Xu; Qinghua Peng; Rui Chen; Daqian Zhou; Kang Cheng; Weiye Cai; Tao Liu; Chenyi Huang; Zhijiang Fu; Cong Wei; Zongchao Liu (Inflammation Research, 2023)

Soil microbial communities as potential regulators of N2O sources in highly acidic soils - Junhui Yin; Huaihai Chen; Pengpeng Duan; Kun Zhu; Naihui Li; Yan Ma; Yumeng Xu; Jingheng Guo; Rui Liu; Qing Chen (Soil Ecology Letters, 2023)

Dynamic assessment of population exposure to traffic-originated PM2.5 based on multisource geo-spatial data - Hui Zhong; Rui Xu; Hongliang Lu; Yonghong Liu; Meixin Zhu (Transportation Research Part D: Transport and Environment, 2023)

A novel 1T-2H MoS2/NaBi(MoO4)2 alternating-phase piezoelectric composites for high-efficient ultrasound-drived piezoelectric catalytic removal of Sildenafil - Qing-rui Zeng; Zi-ang Jia; Xu Liu; Jin-ping Cheng (Process Safety and Environmental Protection, 2023)

TBtools-II: A “one for all, all for one” bioinformatics platform for biological big-data mining - Chengjie Chen; Ya Wu; Jiawei Li; Xiao Wang; Zaohai Zeng; Jing Xu; Yuanlong Liu; Junting Feng; Hao Chen; Yehua He; Rui Xia (Molecular Plant, 2023)

Surface reconstruction of copper foil via electrochemical etching to proliferate CH4 production from CO2 electroreduction - Weicong Xu; Chao Liu; Peijun Li; Hongyun Zeng; Xianjun Lu; Xinyu Li; Tao Li; Rui Xiao (Journal of Cleaner Production, 2023)

Influence of urban extent discrepancy on the estimation of surface urban heat island intensity: A global-scale assessment in 892 cities - Qiquan Yang; Yi Xu; Xiaohua Tong; Ting Hu; Yue Liu; T.C. Chakraborty; Rui Yao; Changjiang Xiao; Shurui Chen; Zonghan Ma (Journal of Cleaner Production, 2023)

A review of the toxic effects of ammonia on invertebrates in aquatic environments - Tian-Xu Zhang; Ming-Rui Li; Chen Liu; Shu-Ping Wang; Zhen-Guang Yan (Environmental Pollution, 2023)

Corrigendum to “Combining functional physiological phenotyping and simulation model to estimate dynamic water use efficiency and infer transpiration sensitivity traits” [Eur. J. Agron. 150 (2023) 126955] - Ting Sun; Rui Cheng; Rujia Jiang; Yunxiu Liu; Yudong Sun; Zhuoyi Wang; Pingping Fang; Xinyang Wu; Kang Ning; Pei Xu (European Journal of Agronomy, 2023)

Epithelial lining inspired protective shield for prolonged endotracheal intubation - Baisong Zhao; Meng-Han Bai; Luxi Zhang; Qingning Wang; Yongying Pan; Yan-Pu Li; Rui Hong; Juxiang Gou; Dongjie Zhang; Yuwei Liu; Gan-Ji Zhong; Ka Li; et al. (Chemical Engineering Journal, 2023)

Transient, printable and recyclable gelatin hydrogels with enhanced mechanical sensing and electromagnetic shielding performance by incorporation of reduced graphene oxide - Rui Yin; Chen Zhang; Youyou Chen; Yu Wang; Qiang Feng; Yaming Liu; Minghan Yu; Yunhuan Yuan; Cheng-Yan Xu; Feihua Liu; Weiwei Zhao (Chemical Engineering Journal, 2023)

Reduced attention on restricted organochlorine pesticides, whereas still noteworthy of the impact on the deep soil and groundwater: a historical site study in southern China - Changlin Xu; Yue Cai; Rui Wang; Jing Wu; Guoyi Yang; Yahui Lv; Dehong Liu; Yu Deng; Yaqi Zhu; Qing Zhang; Lijun Wang; Shengwei Zhang (Environmental Geochemistry and Health, 2023)

Enzymatic DNA repairing amplification-powered construction of an Au nanoparticle-based nanosensor for single-molecule monitoring of cytosine deaminase activity in cancer cells - Wen-jing Liu; Rui Song; Xiao-ran Zou; Dong-ling Li; Qinfeng Xu; Chun-yang Zhang (Analytica Chimica Acta, 2023)

Portable multichannel detection instrument based on time-resolved fluorescence immunochromatographic test strip for on-site detecting pesticide residues in vegetables - Rui Xu; Yaodong Xiang; Zheng Shen; Gaozhen Li; Jiashuai Sun; Peiyu Lin; Xiaofeng Chen; Jingcheng Huang; Haowei Dong; Zhenying He; Wenzheng Liu; Lu Zhang; et al. (Analytica Chimica Acta, 2023)

Meta-analytic and experimental evidence that warmer climate leads to shift from advanced to delayed spring phenology - Jing Guo; Qimei Ma; Hanfeng Xu; Yue Luo; Dashan He; Fucheng Wang; Jiasheng Wu; Yongshuo H. Fu; Jianquan Liu; Rui Zhang; Lei Chen (Agricultural and Forest Meteorology, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Vertical distribution and transport of microplastics in the urban atmosphere: New insights from field observations - Zhen Yuan; Cheng-Lei Pei; Heng-Xiang Li; Lang Lin; Rui Hou; Shan Liu; Kai Zhang; Ming-Gang Cai; Xiang-Rong Xu (Science of The Total Environment, 2023)

Hydrogeological controls on chromium enrichment along the groundwater flow path in the Baiyangdian Catchment, North China Plain - Chao Liu; Huaming Guo; Wendi Fan; Rui Xu; Shuangbao Han; Bingying Gao; Bo Zhao; Chunping Jiang (Science of The Total Environment, 2023)

Diversity and function of mountain and polar supraglacial DNA viruses - Yongqin Liu; Nianzhi Jiao; Kevin Xu Zhong; Lin Zang; Rui Zhang; Xiang Xiao; Yi Shi; Zhihao Zhang; Ye Tao; Liping Bai; Bianli Gao; Yunlan Yang; et al. (Science Bulletin, 2023)

Effects of multi-frequency ultrasound on inactivating Chironomus kiiensis eggs: Evidence from a case study in drinking water treatment plant - Hai-guang Yuan; Rui-jian Zhang; Ye-qin Xu; Zhi Dang; Yong Hu; Qian-Bin Wang; Hao-tao Dong; Jia-xin Liu; Shu-juan Pu; Zhi-li Du; Ying-shi Liu; Zong-jia Zhang (Journal of Water Process Engineering, 2023)

Catalytic degradation of benzene at room temperature over FeN4O2 sites embedded in porous carbon - Hui Ding; Lingxiao Xue; Jiahao Cui; Yongqiang Wang; Dan Zhao; Xing Zhi; Rui Liu; Jianfeng Fu; Shejiang Liu; Bingfeng Fu; Jiahui Shi; Ximeng Xu; et al. (Journal of Hazardous Materials, 2023)

Association between urinary neonicotinoid insecticide levels and dyslipidemia risk: A cross-sectional study in Chinese community-dwelling elderly - Jian Sun; Pei He; Rui Wang; Zhong-Yuan Zhang; Yu-Qing Dai; Xiao-Yu Li; Si-Yu Duan; Cai-Ping Liu; Hao Hu; Guang-Jun Wang; Yan-Ping Zhang; Fei Xu; et al. (Journal of Hazardous Materials, 2023)

The metal-organic frameworks as unique platform for photocatalytic CO2 conversion to liquid fuels - Xiahong Xu; Kangle Xie; Junjie Hu; Suijun Liu; Hong Zhong; He-Rui Wen (Journal of Environmental Chemical Engineering, 2023)

Combining functional physiological phenotyping and simulation model to estimate dynamic water use efficiency and infer transpiration sensitivity traits - Ting Sun; Rui Cheng; Rujia Jiang; Yunxiu Liu; Yudong Sun; Zhuoyi Wang; Pingping Fang; Xinyang Wu; Kang Ning; Pei Xu (European Journal of Agronomy, 2023)

Seismic and hydrological triggers for a complex cascading geohazard of the Tianmo Gully in the southeastern Tibetan Plateau - Rui Guo; Liming Jiang; Zhida Xu; Chao Li; Ronggang Huang; Zhiwei Zhou; Tao Li; Yi Liu; Hansheng Wang; Xuanmei Fan (Engineering Geology, 2023)

Hybrid tribo/piezoelectric nanogenerator textile derived from 3D interlocked parallel-arranged yarns for bio-motion energy harvesting and tactile sensing - Lin Liu; Yuantao Li; Muchun Xu; Rui Tao; Qiao Zhong; Xi Yang; Shixia Lan; Jiyang Xie; Guo Chen; Yongyun Mao; Wanbiao Hu (Chemical Engineering Journal, 2023)

Intrinsic reaction selectivity between gaseous HCl and SO2 over ethanol-hydrated CaO adsorbent in coal-fired flue gas dechlorination - Xiaoshuo Liu; Rui Wang; Xinze Geng; Ao Shen; Cong Chen; Yifan Xu; Xunlei Ding; Yufeng Duan; Shilin Zhao (Chemical Engineering Journal, 2023)

Bradykinin-pretreated Human cardiac-specific c-kit+ Cells Enhance Exosomal miR-3059-5p and Promote Angiogenesis Against Hindlimb Ischemia in mice - Jingzhou Li; Fei Song; Ruolan Chen; Jinjuan Yang; Jie Liu; Li Huang; Fuyu Duan; Meng Kou; Boon Xuan Lian; Xiaoxia Zhou; Weimin Han; Liang Mao; et al. (Stem Cell Reviews and Reports, 2023)

Lactiplantibacillus plantarum Regulated Intestinal Microbial Community and Cytokines to Inhibit Salmonella typhimurium Infection - Rui-Han Liu; An-Qi Sun; Ye Liao; Zheng-Xu Tang; Shi-Han Zhang; Xin Shan; Jing-Tao Hu (Probiotics and Antimicrobial Proteins, 2023)

Urine 2-hydroxyphenanthrene is associated with current asthma: evidence from NHANES 2007–2012 - Lingyi Lu; Tingfeng Mao; Rui Xu; Lanxia Liu; Jiefeng Qian; Kai Yang; Anjie Yuan; Xinyue Wang; Rong Ni (International Archives of Occupational and Environmental Health, 2023)

Mn(VII) enhanced by CaSO3 to remove trace organic pollutants in high salt organic wastewater: Further enhancement of salinity - Linsong Cheng; Yuanxiang Mao; Lei Jiang; Rui Ma; Jiangsen Ma; Yiyuan Zhuo; Qiushi Shen; Caocong Liu; Liuwei Zhao; Xiaoyi Xu; Fangying Ji (Chemosphere, 2023)

Loss of amino acids 67-76 in the neuraminidase protein under antibody selection pressure alters the tropism, transmissibility and innate immune response of H9N2 avian influenza virus in chickens - Jianjun Zhang; Quan Li; Rui Zhu; Shunshun Xu; Shifeng Wang; Huoying Shi; Xiufan Liu (Veterinary Microbiology, 2023)

Seismic failure probability analysis of slopes via stochastic material point method - Dezhi Zai; Rui Pang; Bin Xu; Jun Liu (Soil Dynamics and Earthquake Engineering, 2023)

Uncertainty in China's food self-sufficiency: A dynamic system assessment - Xinyuan Liang; Xiaobin Jin; Xiaoxiao Xu; Hefeng Chen; Jing Liu; Xuhong Yang; Weiyi Xu; Rui Sun; Bo Han; Yinkang Zhou (Sustainable Production and Consumption, 2023)

Association between PM2.5 exposure and the outcomes of ART treatment: A prospective birth cohort study - Yifan Wang; Yun Qiu; Bo Huang; Jiangbo Du; Liya Liu; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; et al. (Science of The Total Environment, 2023)

Insights on rational design and regulation strategies of Prussian blue analogues and their derivatives towards high-performance electrocatalysts - Yu-Rui Ji; Ya-Fei Guo; Xu Liu; Peng-Fei Wang; Ting-Feng Yi (Chemical Engineering Journal, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Cutting Efficiency of a Newly Developed Incubator-Based Laser Cutting Method and Its Effects on Potato Tissue Culture Plantlet Growth - Tao Xu; Hongbing Duan; Xingkui Cai; Rui Yang; Feihu Yao; Benfang Tan; Fengshun Liu (Potato Research, 2023)

The biocontrol agent Bacillus velezensis T-5 changes the soil bacterial community composition by affecting the tomato root exudate profile - Yian Gu; Weina Liang; Zhidan Li; Sijie Liu; Sun Liang; Peng Lei; Rui Wang; Nan Gao; Sha Li; Zongqi Xu; Hong Xu (Plant and Soil, 2023)

Prediction of landslide block movement based on Kalman filtering data assimilation method - Yong Liu; Qing-jie Xu; Xing-rui Li; Ling-feng Yang; Hong Xu (Journal of Mountain Science, 2023)

Otolith microchemistry reveals various habitat uses and life histories of Chinese gizzard shad Clupanodon thrissa in the Min River and the estuary, Fujian Province, China - Qing Xu; Qing-qiang Ren; Tao Jiang; Chen-rui Jiang; Lü-ping Fang; Ming-zhe Zhang; Jian Yang; Min Liu (Fisheries Research, 2023)

Theory, framework, and methodology for physical lifespan prediction of hazardous waste landfills - Xu Ya; Yao Guangyuan; Liu Yuqiang; Liu Jingcai; Xiang Rui; Qian Can (Science of The Total Environment, 2023)

Enhanced selective nitrate-to-nitrogen electrocatalytic reduction by CNTs doped Ni foam/Cu electrode coupled with Cl− - Xinrui Liu; Rui Guo; Xia Qin; Cuicui Xu (Journal of Water Process Engineering, 2023)

Effects of gums on 3D printing performance of Pleurotus eryngii powder - Anqi He; Juan Xu; Qiuhui Hu; Liyan Zhao; Gaoxing Ma; Lei Zhong; Rui Liu (Journal of Food Engineering, 2023)

A “smart-sensing” bactericidal protein-based Pickering emulsion - Lishan Yao; Rui Wang; Shurui Peng; Zhenbin Liu; Hongbo Li; Dan Xu; Liangbin Hu; Haizhen Mo (Journal of Food Engineering, 2023)

Structure-guided camera localization for indoor environments - Qing Li; Rui Cao; Kanglin Liu; Zongze Li; Jiasong Zhu; Zhenyu Bao; Xu Fang; Qingquan Li; Xianfeng Huang; Guoping Qiu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Self-shedding of multifunctional biomolecular nanocarriers for H-FABP monitoring in magnetic separation self-powered photoelectrochemical and colorimetric immunoassay platform - Dongquan Leng; Rui Xu; Xiang Ren; Hongmin Ma; Lei Liu; Qin Wei; Huangxian Ju (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Specific pupylation as IDEntity reporter (SPIDER) for the identification of protein-biomolecule interactions - He-Wei Jiang; Hong Chen; Yun-Xiao Zheng; Xue-Ning Wang; Qingfeng Meng; Jin Xie; Jiong Zhang; ChangSheng Zhang; Zhao-Wei Xu; Zi-Qing Chen; Lei Wang; Wei-Sha Kong; et al. (Science China Life Sciences, 2023)

Spatial distribution of landslide shape induced by Luding Ms6.8 earthquake, Sichuan, China: case study of the Moxi Town - Xuemei Liu; Pengcheng Su; Yong Li; Zhaoxu Xia; Siyuan Ma; Rui Xu; Yao Lu; Dahu Li; Heng Lu; Renmao Yuan (Landslides, 2023)

Analysis of cuproptosis-related lncRNA signature for predicting prognosis and tumor immune microenvironment in pancreatic cancer - Hong-Fei Yao; Da-Peng Xu; Jia-Hao Zheng; Yu Xu; Qin-Yuan Jia; Yu-Heng Zhu; Jian Yang; Rui-Zhe He; Ding Ma; Min-Wei Yang; Xue-Liang Fu; De-Jun Liu; et al. (Apoptosis, 2023)

Distribution, sources and influencing factors of organic carbon in the surface sediments of the coastal tidal flats in Jiangsu Province - Rui Zhao; Xinrui Dong; Qing Liu; Min Xu; Yifei Zhao (Frontiers in Marine Science, 2023)
Coastal tidal flats are situated in the interaction zone between the ocean and land and are vulnerable to natural changes, human activities, and global changes; these areas serve as an important mixing zone and burial area for carbon and nitrogen storage. Coastal tidal flats contribute significantly to the global carbon cycle due to their high biological productivity, high sedimentation rate, and low decomposition rate. However, there is a lack of research on the sources and influencing factors of organic carbon in surface sediments in the coastal tidal flat area of Jiangsu Province. In this study, fourteen surface sediment samples were collected from the Jiangsu coastal tidal flats, and the distribution of organic carbon was analyzed. The sources and influencing factors of sediment organic carbon were also investigated by analyzing the contents, ratios and stable isotopes of carbon and nitrogen in the sediments. The results indicated that the total organic carbon (TOC) and total nitrogen (TN) contents in the surface sediments of Jiangsu coastal tidal flats ranged from 0.09% to 0.82% and from 0.01% to 0.1%, with mean values of 0.36% and 0.04%, respectively, and that there was a significant positive correlation between TOC and TN. Moreover, the high-value areas were located mostly along the borders or in sections covered in vegetation, whereas the mudflat areas without vegetation had lower values. Considering the status of the Jiangsu coastal zone, the abandoned Yellow River estuary, Yangtze River inlet, marine benthic microalgae, C3 plants and C4 plants were selected as end members of organic carbon concentrations. The contributions of different sources were quantified using a Bayesian mixture model (MixSIAR). Among them, the abandoned Yellow River estuary and Yangtze River inlet contributed 28.1% and 19.3%, respectively, followed by marine benthic microalgae with a contribution of 26%, whereas C3 and C4 plants made limited contributions of 9% and 8.8%, respectively. Additionally, the sediment particle size, hydrodynamics, and tidal flat vegetation such as Spartina alterniflora were the key factors influencing the organic carbon distribution. In general, this study contributes to a better understanding of the biogeochemical processes and sources of organic carbon in coastal tidal flats. It also provides a solid foundation for the creation of carbon sink measures in nearshore tidal flats.

Iron-rich red mud and iron oxide-modified biochars: A comparative study on the removal of Cd(II) and influence of natural aging processes - Huabin Wang; Dingxiang Chen; Yi Wen; Yong Zhang; Ying Liu; Rui Xu (Chemosphere, 2023)

Magnetic anaerobic granular sludge for sequestration and immobilization of Pb - Rui Zhou; Han Li; Chengshuai Liu; Yizhang Liu; Jyh-Fu Lee; Yu-Jung Lin; Zhang Yan; Zhangyi Xu; Xiaoyun Yi; Chunhua Feng (Water Research, 2023)

Molecular insights into the dissolved organic matter of leather wastewater in leather industrial park wastewater treatment plant - Xiao-Xu Gao; Yun-Wen Wang; Ye-Chen An; Rui-Yun Ren; Yao-Hui Lin; Ning Wang; Yi-Fan Wang; Jing-Long Han; Zhi-Neng Hao; Jing-Fu Liu; Ai-Jie Wang; Nan-Qi Ren (Science of The Total Environment, 2023)

Benzene abatement catalyzed by Ceria-Supported platinum nanoparticles and single atoms - Jing Liu; Xue Fang; Daoqing Liu; Xiaolei Hu; Tian Qin; Junxiao Chen; Rui Liu; Dongrun Xu; Weiye Qu; Yangyang Dong; Liwei Chen; Zhen Ma; et al. (Chemical Engineering Journal, 2023)

A Novel D-π-A Type Fluorescent Probe for Cu2+ Based on Styryl-Pyridinium Salts Conjugating Di-(2-picolyl)amine (DPA) Units - Rui Cao; Mengyu Zhang; Wen Tang; Jing Wu; Meixiang Wang; Xiaoxiao Niu; Zhaodi Liu; Fuying Hao; Huajie Xu (Journal of Fluorescence, 2023)

Removal of toilet paper fibers from residential wastewater: a life cycle assessment - Xiaoyu Wang; Guoqiang Liu; Weimin Sun; Zhiguo Cao; Huaqing Liu; Yiqun Xiong; Baoqin Li; Xiaoxu Sun; Yongbin Li; Rui Xu; Duanyi Huang; Pin Gao (Environmental Science and Pollution Research, 2023)

The discovery of 3-fluoroalkyl indoles as potential antifungal agents to control tomato gray mold caused by Botrytis cinerea - Rui Feng; Fei Liu; Yan Wang; Shu Xu; Wuzhang Liu; Siwei Qiao; Songtao Liu; Yu Chen; Xu Feng; Qizhi Wang; Weidong Rao (Phytochemistry Letters, 2023)

Efficient emerging contaminants (EM) decomposition via peroxymonosulfate (PMS) activation by Co3O4/carbonized polyaniline (CPANI) composite: Characterization of tetracycline (TC) degradation property and application for the remediation of EM-polluted water body - Jin Qian; Xiaohui Mi; Zhijie Chen; Weihang Xu; Wen Liu; Rui Ma; Yichu Zhang; Yufei Du; Bing-Jie Ni (Journal of Cleaner Production, 2023)

Deciphering riverine dissolved organic matter biodegradation: Evidence from three-dimensional fluorescence - Rong Xu; Jing Zhang; Jianwei Li; Rui Liu; Maofei Ni; Guangneng Zeng (Journal of Environmental Chemical Engineering, 2023)

Use of nano titanium hydroxide and nano zirconium hydroxide fixed filter paper for rapid detection of Staphylococcus aureus in dairy products by PCR without pre-enrichment - Chun Wang; Ruohong Zhang; Xiaofang Wang; Rui Xu; Hejing Yan; Xiaoran Li; Shaojun Liu; Shuren Yin; Hong Yao; Yang Yang; Shenghui Cui; Yunchang Guo (Food Control, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Immunoregulatory hydrogel decorated with Tannic acid/Ferric ion accelerates diabetic wound healing via regulating Macrophage polarization - Na Xu; Yuanping Gao; Zheng Li; Yu Chen; Menglong Liu; Jiezhi Jia; Rui Zeng; Gaoxing Luo; Jiangfeng Li; Yunlong Yu (Chemical Engineering Journal, 2023)

Correction to: Inhibition of mGluR5 alters BDNF/TrkB and GLT‑1 expression in the prefrontal cortex and hippocampus and ameliorates PTSD‑like behavior in rats - Shuyue Cheng; Jingjing Xu; Wei Wang; Rui Wang; Haonan Li; Zhijun Jiang; Dexiang Liu; Fang Pan (Psychopharmacology, 2023)

Free and conjugated forms of metabolites are indispensable components of steroids: The first evidence from an estuarine food web - Shan Liu; Ru Xu; Yun-Feng Pan; Qian-Yi Huang; Nian-Nian Wu; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu (Water Research, 2023)

Diversity and distribution variation of urban spontaneous vegetation with distinct frequencies along river corridors in a fast-growing city - Xiaopeng Li; Sining Zhang; Rui Huang; Li Feng; Sihui Xu; Baichuan Liu (Journal of Environmental Management, 2023)

Wide-Scope Multi-residue analysis of pesticides in beef by gas chromatography coupled with quadrupole Orbitrap mass spectrometry - Xu Pang; Jing Qiu; Zhaoyang Zhang; Pi Li; Jiangtao Xing; Xin Su; Guiqiao Liu; Changyuan Yu; Rui Weng (Food Chemistry, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Increased hypertension risk for the elderly with high blood levels of strontium and lead - Jiebao Zhang; Chunfang Xu; Yan Guo; Xingyi Jin; Zi Cheng; Qi Tao; Lin Liu; Rui Zhan; Xuemin Yu; Hongjuan Cao; Fangbiao Tao; Jie Sheng; et al. (Environmental Geochemistry and Health, 2023)

Recent advances in CO2 fixation by microalgae and its potential contribution to carbon neutrality - Peilun Xu; Jun Li; Jun Qian; Bang Wang; Jin Liu; Rui Xu; Paul Chen; Wenguang Zhou (Chemosphere, 2023)

Evaluation method of rowing performance and its optimization for UAV-based shot seeding device on rice sowing - Wei Liu; Zhiyan Zhou; Xuelang Xu; Qingyu Gu; Shuaishuai Zou; Weizhuo He; Xiwen Luo; Junhao Huang; Jianqin Lin; Rui Jiang (Computers and Electronics in Agriculture, 2023)

The effect of repeated energy inputs on the release profiles of extracellular organic substances in sewage sludge - Rui Liu; Ying Xu; Liang Song; Shiyu Liu; Zixuan Liang; Danyang Zhu; Xiaohu Dai (Water Research, 2023)

Regulation of denitrification performance and microbial topology by lights: Insight into wavelength effects towards microbiota - Yang Liao; Jiyong Bian; Shiyu Miao; Siqi Xu; Rui Li; Ruiping Liu; Huijuan Liu; Jiuhui Qu (Water Research, 2023)

Post COVID-19 pandemic recovery of intracity human mobility in Wuhan: Spatiotemporal characteristic and driving mechanism - Rui An; Zhaomin Tong; Xiaoyan Liu; Bo Tan; Qiangqiang Xiong; Huixin Pang; Yaolin Liu; Gang Xu (Travel Behaviour and Society, 2023)

Association between exposure to ambient air pollution and semen quality: A systematic review and meta-analysis - Ruijun Xu; Yanling Zhong; Rui Li; Yingxin Li; Zihua Zhong; Tingting Liu; Qiling Wang; Ziquan Lv; Suli Huang; Yong-Gang Duan; Xinzong Zhang; Yuewei Liu (Science of The Total Environment, 2023)

Atmospheric microplastics at a southern China metropolis: Occurrence, deposition flux, exposure risk and washout effect of rainfall - Zhen Yuan; Chenglei Pei; Hengxiang Li; Lang Lin; Shan Liu; Rui Hou; Ran Liao; Xiangrong Xu (Science of The Total Environment, 2023)

Environmental risk of tailings pond leachate pollution: Traceable strategy for leakage channel and influence range of leachate - Bowen Shi; Xixi Li; Weiwu Hu; Beidou Xi; Shengrong Liu; Di Liu; Congchao Xu; Zihao Jia; Rui Li (Journal of Environmental Management, 2023)

The effect of clay type and solid wettability on bitumen extraction from Canadian oil sands - An Li; Rui Li; Ci Yan; Han Wang; Qingxia Liu; Jacob H. Masliyah; Hongbo Zeng; Zhenghe Xu (Fuel, 2023)

Fabrication of starch-based emulsion gel beads by an inverse gelation technique for loading proanthocyanidin and curcumin - Xiaotong Bu; Minghang Guan; Lei Dai; Na Ji; Yang Qin; Xingfeng Xu; Liu Xiong; Rui Shi; Qingjie Sun (Food Hydrocolloids, 2023)

Inhibition of human sulfotransferases (SULTs) by per- and polyfluoroalkyl substances (PFASs) and structure-activity relationship - Yong-Zhe Liu; Kai Yang; Wei Zhang; Qian zhang; Tong-Feng Liu; Tong Xu; Yang Li; Rui-Xue Ran; Kun Yang; Yun-Feng Cao; Zhong-Ze Fang (Food and Chemical Toxicology, 2023)

Long-term exposure to fine particulate matter and site-specific cancer mortality: A difference-in-differences analysis in Jiangsu province, China - Zhaoyu Fan; Yingxin Li; Jing Wei; Gongbo Chen; Rui Wang; Ruijun Xu; Tingting Liu; Ziquan Lv; Suli Huang; Hong Sun; Yuewei Liu (Environmental Research, 2023)

Ultra-thin hierarchical porous carbon coated metal phosphide self-assembled efficient tri-functional electrodes for overall water splitting and rechargeable zinc-air batteries - Rui He; Tuo Lu; Nengneng Xu; Guicheng Liu; Yanxing Zhang; Jinli Qiao (Chemical Engineering Journal, 2023)

Magnetic hydrochar derived from waste lignin for thallium removal from wastewater: Performance and mechanisms - Huabin Wang; Ran Duan; Lin Ding; Lin Tian; Ying Liu; Yong Zhang; Rui Xu (Bioresource Technology, 2023)

Inhibition of mGluR5 alters BDNF/TrkB and GLT-1 expression in the prefrontal cortex and hippocampus and ameliorates PTSD-like behavior in rats - Shuyue Cheng; Jingjing Xu; Wei Wang; Rui Wang; Haonan Li; Zhijun Jiang; Dexiang Liu; Fang Pan (Psychopharmacology, 2023)

Activating α7nAChR helps post-myocardial infarction healing by regulating macrophage polarization via the STAT3 signaling pathway - Xiao-Hui Niu; Rong-Hua Liu; Xiao Lv; Rui-Lin He; Fang-Zhou Lv; Shu-Jie Wu; Xu-Qing Li; Lei Li; Jia-Feng Lin (Inflammation Research, 2023)

Energy and environmental performance evaluation of China's non-ferrous metals industry from the perspective of network structure - Rui Yang; Yujin Xu; Kaiyuan Liu (Clean Technologies and Environmental Policy, 2023)

Diffusion simulation and risk assessment model establishment of chlorine gas leakage based on terrain conditions - Xiao-ting Ren; Xiao-ling Ma; Jiang-zheng Liu; Rui Liu; Chen-qian Zhao; Hao Wu; Zhao Wang; Chun-xu Hai; Xiao-di Zhang (Environmental Science and Pollution Research, 2023)

‘Yunnan’ quince rootstock promoted flower bud formation of ‘Abbé Fetel’ pear by altering hormone levels and PbAGL9 expression - Liu Cong; Hutian Ling; Shanshan Liu; Azheng Wang; Rui Zhai; Chengquan Yang; Zhigang Wang; Lingfei Xu (Journal of Plant Physiology, 2023)

Morphology and location of sensilla in the antennae and ovipositor of Sirex noctilio (Hymenoptera: Siricidae) - Enhua Hao; Rui Liu; Ruirui Xu; Pengfei Lu; Haili Qiao (Arthropod Structure & Development, 2023)

Effects of Alpine Grassland Degradation on Soil Microbial Communities in Qilian Mountains of China - Chunming Li; Derong Zhang; Gengchun Xu; Rui Yan; Yang Huang; Liuqing Feng; Jin Yi; Xiangyu Xue; Huixia Liu (Journal of Soil Science and Plant Nutrition, 2023)

rTFPI Protects Cardiomyocytes from Hypoxia/Reoxygenation Injury through Inhibiting Autophagy and the Class III PI3K/Beclin-1 Pathway - Runan Yan; Wei Gao; Wenjia Chen; Yue Liu; Li Shen; Yue Dai; Rui Xu; Qing Chang; Yu Fu; Yong Zhao (Cell Biochemistry and Biophysics, 2023)

Combined effects of fluoroquinolone antibiotics and organophosphate flame retardants on Microcystis aeruginosa - Yang Zhao; Yingping Huang; Shuang Hu; Tao Xu; Yanfen Fang; Huigang Liu; Ying Xi; Rui Qu (Environmental Science and Pollution Research, 2023)

Spatiotemporal difference of leachate production and its impact on the development and dynamics of LCS clogging - Ya Xu; Guangyuan Yao; Rui Xiang; Yuqiang Liu; Qifei Huang (Waste Management, 2023)

SLP-2 regulates the generation of reactive oxygen species and the ERK pathway to promote papillary thyroid carcinoma motility and angiogenesis - Jianping Chen; Duting Wang; Rui Xu; Ting Yao; Yu Guo; Qi Liu; Erlong Yang; Zhengqing Wu; Zhenyu Xu (Tissue and Cell, 2023)

Manganese-induced α-synuclein overexpression promotes the accumulation of dysfunctional synaptic vesicles and hippocampal synaptotoxicity by suppressing Rab26-dependent autophagy in presynaptic neurons - Zhuo Ma; Kuan Liu; Rui-feng Zhang; Zi-xin Xie; Wei Liu; Yu Deng; Xin Li; Bin Xu (Science of The Total Environment, 2023)

The F-box protein OsEBF2 confers the resistance to the brown planthopper (Nilparvata lugens Stål) - Feilong Ma; Zixin Li; Sayi Wang; Kejia Li; Fei Tang; Jingxuan Jia; Qiujin Zhao; Peihua Jing; Wenqing Yang; Congmin Hua; Haifu Han; Jiayin Xu; et al. (Plant Science, 2023)

Self-assembly of Au nanocrystals into large-area 3-D ordered flexible superlattice nanostructures arrays for ultrasensitive trace multi-hazard detection - Wei Liu; Qian Li; Jiabin Wu; Weizhe Wang; Rui Jiang; Chunli Zhou; Shuangbao Wang; Xueming Zhang; Tangyou Sun; Zhimou Xu; Dingsheng Wang (Journal of Hazardous Materials, 2023)

Antifouling modification of PVDF membranes via incorporating positive-charge tuned quaternized chitosan magnetic particles - Ziming Zhu; Xuan Zhou; Rui Zhang; Yahong Li; Yuan Liu; Jianxian Zeng; Xiaoping Huang; Pengfei Liu; Jianrong Xue; Kaipeng Cheng; Hongfei Xu (Journal of Environmental Chemical Engineering, 2023)

Expanded polystyrene buoys as an important source of hexabromocyclododecanes for aquatic ecosystem: Evidence from field exposure with different substrates - Yun-Feng Pan; Shan Liu; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Environmental Pollution, 2023)

Facile fabrication of flexible and ultrathin self-assembled Ti3C2T /bacterial cellulose composite films with multifunctional electromagnetic shielding and photothermal conversion performances - Hao Liu; Zhou Cui; Lijin Luo; Qiugang Liao; Rui Xiong; Chao Xu; Cuilian Wen; Baisheng Sa (Chemical Engineering Journal, 2023)

Friction induced mechanochemistry: self-adaptive lubrication through in-situ tribo-click system - Rui Dong; Yunlei Zhang; Hao-Zhe Xu; Luyao Bao; Shuanhong Ma; Xin-Gang Wang; Qiangliang Yu; Meirong Cai; Feng Zhou; Weimin Liu (Chemical Engineering Journal, 2023)

Long-term exposure to ambient particulate matter and kidney function in older adults - Yingxin Li; Xueli Yuan; Jing Wei; Yuanying Sun; Wenqing Ni; Hongmin Zhang; Yan Zhang; Rui Wang; Ruijun Xu; Gongbo Chen; Yuewei Liu; Jian Xu (Atmospheric Environment, 2023)

Effects of earthworm (Eisenia fetida) and arbuscular mycorrhizal fungi improving plant hormones and antioxidant enzymes under simulated acid rain stress - Wang Binglei; Wang Chong; Liu Xuelian; Xue Rui; Liu Mengli; Xu Guangxia; Li Zhiyi (Applied Soil Ecology, 2023)

Effects of single or conjoint administration of lactic acid bacteria as potential probiotics on the growth, immune responses, and disease resistance of Carassius auratus - Ruoming Li; Teng Chi; Qing Xu; Juntong Liu; Xiaofeng Shan; Rui Zhou; Jiayun Yao; Wuwen Sun; Guiqin Wang (Aquaculture International, 2023)

Kingella pumchi sp. nov., an organism isolated from human vertebral puncture tissue - Meng Xiao; Ruina Liu; Juan Du; Rui Liu; Lei Zhai; He Wang; Su Yao; Ying-Chun Xu (Antonie van Leeuwenhoek, 2023)

Sedimentation of cohesive sediments at the subtidal flat affected by wind wave in high turbidity estuary - Qi Shen; Qin Zhu; Shuguang Liu; Sha Lou; Hualin Wu; Zhenchang Zhu; Bin Xu; Rui Yuan (Frontiers in Marine Science, 2023)
Sedimentation is an important mechanism to mitigate the shrinking of tidal flat and to restore its ecological function by means of sand or mud nourishment. To explore the sedimentation of cohesive sediments, a seabed tripod observation system was deployed at the subtidal region of the Hengsha Shoal adjacent to the turbidity maximum zone of the Yangtze Estuary for 11 days. The results showed that the fine sediment with the median grain size around 8 mm occupied the whole water column. The seabed was in relative equilibrium state with the fluctuation of bed level smaller than 16 mm during the moderate wind condition while the seabed experienced a rapid erosion of 38mm and a successive intensive accretion of 68mm during the process of wind wave and swell. The bottom hydrodynamic at 0.3mab during the bed accretion was stronger than that during the bed erosion. The deposition process of cohesive sediments can be better described by the simultaneous deposition paradigm than that by the exclusive deposition paradigm according to the direct data-model comparison of the bed level changes, especially during the impact of fluid mud. Three possible reasons for the better performance of the simultaneous deposition paradigm were proposed. The first possibility is that the fine suspended sediments do maintain a continuous contact with the sediment bed since the direct bed level changes during our observation period has been well reproduced by the simultaneous deposition paradigm. The second possibility is the SSC-induced turbulence damping which facilitates the fine sediment settling in the form of cohesive sediment flocs, indicating the settling of sediments can’t be judged by the critical shear stress for deposition just based on the single particle grain size. The last possibility is the fluid mud-induced overestimated bed shear stress by using turbulent velocity fluctuation above the fluid mud-water interface, which produces excess sediment erosion waiting to be compensated by the simultaneous deposition paradigm. For practical modeling purposes, modeling under the simultaneous deposition paradigm can give satisfactory results for the sedimentation of cohesive sediment especially during the impact of wave or swell.

Effects of chemical additives and mature compost on reducing nitrogen loss during food waste composting - Shangao Xiong; Yongdi Liu; Hao Zhang; Shaoqi Xu; Songrong Li; Xinqi Fan; Rui Chen; Guochun Ding; Ji Li; Yuquan Wei (Environmental Science and Pollution Research, 2023)

Bicarbonate enhanced heterogeneous activation of peroxymonosulfate by copper ferrite nanoparticles for the efficient degradation of refractory organic contaminants in water - Chun Cai; Yangfan Liu; Rui Xu; Jiaheng Zhou; Jin Zhang; Yu Chen; Lingyu Liu; Lexiang Zhang; Shuping Kang; Xianjun Xie (Chemosphere, 2023)

Insight into the formation and biological effects of natural organic matter corona on silver nanoparticles in water environment using biased cyclical electrical field-flow fractionation - Zhiqiang Tan; Weichen Zhao; Yongguang Yin; Ming Xu; Wenxiao Pan; Yanwanjing Liu; Qinghua Zhang; Bruce K. Gale; Yukui Rui; Jingfu Liu (Water Research, 2023)

Hotspots of riverine greenhouse gas (CH4, CO2, N2O) emissions from Qinghai Lake Basin on the northeast Tibetan Plateau - Penglin Lin; Zhiheng Du; Lei Wang; Jingfeng Liu; Qian Xu; Jia Du; Rui Jiang (Science of The Total Environment, 2023)

Synergistic activation of anionic redox via cosubstitution to construct high-capacity layered oxide cathode materials for sodium-ion batteries - Haocheng Ji; Wenhai Ji; Haoyu Xue; Guojie Chen; Rui Qi; Zhongyuan Huang; Hui Fang; Mihai Chu; Lele Liu; Zhewen Ma; Shenyang Xu; Jingjun Zhai; et al. (Science Bulletin, 2023)

Impact of international trade on water scarcity: An assessment by improving the Falkenmark indicator - Rui Zhong; Aifang Chen; Dandan Zhao; Ganquan Mao; Xu Zhao; Hao Huang; Junguo Liu (Journal of Cleaner Production, 2023)

Habitat quality dynamics in China's first group of national parks in recent four decades: Evidence from land use and land cover changes - Xin Chen; Le Yu; Yue Cao; Yidi Xu; Zhicong Zhao; Youbo Zhuang; Xuehua Liu; Zhenrong Du; Tao Liu; Bo Yang; Lu He; Hui Wu; et al. (Journal of Environmental Management, 2023)

Learn then match: A fast coarse-to-fine depth image-based indoor localization framework for dark environments via deep learning and keypoint-based geometry alignment - Qing Li; Rui Cao; Jiasong Zhu; Hao Fu; Baoding Zhou; Xu Fang; Sen Jia; Shenman Zhang; Kanglin Liu; Qingquan Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Composite organic amendment boosts soil remediation and Cd detoxification to rape under different nitrogen level - Xu Zhang; Qingkai Guan; Linghui Kong; Rui Yang; Xuesheng Liu; Juanjuan Qu; Yu Jin (European Journal of Soil Biology, 2023)

Controlled design of Na–P1 zeolite/ porous carbon composites from coal gasification fine slag for high-performance adsorbent - Rui Shu; Qixia Qiao; Feiqiang Guo; Kaiming Dong; Sha Liu; Liya Xu; Yonghui Bai; Nan Zhou (Environmental Research, 2023)

Breast adipose metabolites mediates the association of tetrabromobisphenol a with breast cancer: A case-control study in Chinese population - Ai Zhang; Rui Wang; Qianfeng Liu; Zhengjun Yang; Xiaohui Lin; Jing Pang; Xiaoyu Li; Dan Wang; Jiayu He; Jianping Li; Mingyue Zhang; Yue Yu; et al. (Environmental Pollution, 2023)

Combining a novel biofilm reactor with a constructed wetland for rural, decentralized wastewater treatment - Rui Zhang; Xianchang Liu; Lutian Wang; Pan Xu; Kai Li; Xiaoxiao Chen; Rong Meng; Yuewu Pu; Xuetong Yang; Diederik P.L. Rousseau; Stijn W.H. Van Hulle (Chemical Engineering Journal, 2023)

Robust emission in near-infrared II of lanthanide nanoprobes conjugated with Au (LNPs-Au) for temperature sensing and controlled photothermal therapy - Guofeng Liu; Zhenxing Wang; Wan Sun; Xiaohui Lin; Rui Wang; Chonghui Li; Li Zong; Zuoling Fu; Hanping Liu; Shicai Xu (Chemical Engineering Journal, 2023)

In-situ growth of bimetallic FeCo-MOF on magnetic biochar for enhanced clearance of tetracycline and fruit preservation - Yi-Cai Jiang; Meng-Fan Luo; Zi-Nuo Niu; Si-Yuan Xu; Yue Gao; Yuan Gao; Wen-Juan Gao; Jing-Jing Luo; Rui-Lin Liu (Chemical Engineering Journal, 2023)

Lattice doping of Zn boosts oxygen vacancies in Co3O4 Nanocages: Improving persulfate activation via forming Surface-Activated complex - Mei-Mei Wang; Li-Juan Liu; Jia-Rui Xi; Ying Ding; Peng-Xi Liu; Liang Mao; Bing-Jie Ni; Wei-Kang Wang; Juan Xu (Chemical Engineering Journal, 2023)

Positional cloning identified HvTUBULIN8 as the candidate gene for round lateral spikelet (RLS) in barley (Hordeum vulgare L.) - Dandan Qin; Gang Liu; Rui Liu; Chunchao Wang; Fuchao Xu; Qing Xu; Yu Ling; Guoqing Dong; Yanchun Peng; Shuangtao Ge; Ganggang Guo; Jing Dong; et al. (Theoretical and Applied Genetics, 2023)
Key message Map-based cloning, subcellular localization, virus-induced-gene-silencing and transcriptomic analysis reveal HvTUB8 as a candidate gene with pleiotropic effects on barley spike and leaf development via ethylene and chlorophyll metabolism. Abstract Barley lateral spikelet morphology and grain shape play key roles in grain physical quality and yield. Several genes and QTLs for these traits have been cloned or fine mapped previously. Here, we report the phenotypic and genotypic analysis of a barley mutant with round lateral spikelet (rls) from cv. Edamai 934. rls had round lateral spikelet, short but round grain, shortened awn, thick glume and dark green leaves. Histocytologic and ultrastructural analysis revealed that the difference of grain shape of rls was caused by change of cell arrangement in glume, and the dark leaf color resulted from enlarged chloroplast. HvTUBULIN8 ( HvTUB8 ) was identified as the candidate gene for rls by combination of RNA-Seq, map-based-cloning, virus-induced-gene-silencing (VIGS) and protein subcellular location. A single G-A substitution at the third exon of HvTUB8 resulted in change of Cysteine 354 to tyrosine. Furthermore, the mutant isoform Hvtub8 could be detected in both nucleus and cytoplasm, whereas the wild-type protein was only in cytoplasm and granular organelles of wheat protoplasts. Being consistent with the rare phenotype, the “A” allele of HvTUB8 was only detected in rls , but not in a worldwide barley germplasm panel with 400 accessions. VIGS confirmed that HvTUB8 was essential to maintain spike integrity. RNA-Seq results suggested that HvTUB8 may control spike morphogenesis via ethylene homeostasis and signaling, and control leaf color through chlorophyll metabolism. Collectively, our results support HvTUB8 as a candidate gene for barley spike and leaf morphology and provide insight of a novel mechanism of it in barley development.

LncRNA as potential biomarker and therapeutic target in glioma - Xun Xu; Yuan Liang; Ilgiz Gareev; Yanchao Liang; Rui Liu; Ning Wang; Guang Yang (Molecular Biology Reports, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Establishment and comprehensive analysis of a new human cell line (NK-NJ) with NK-cell characteristics established from extranodal natural killer cell lymphoma/leukemia - Jin-Hua Liang; Wei-Ting Wang; Kai-Xin Du; Tong-Yao Xing; Yan Wang; Hui Wang; Lu Liu; Rui Guo; Yang Shao; Junheng Liang; Yue Li; Hao-Rui Shen; et al. (Human Cell, 2022)

Site-directed RNA editing by harnessing ADARs: advances and challenges - Ming Li; Cheng Yan; Yue Jiao; Yuqin Xu; Chen Bai; Rui Miao; Jiying Jiang; Jiao Liu (Functional & Integrative Genomics, 2022)

Analysis of Cyclic Shear Stress–Displacement Mechanical Properties of Silt–Steel Interface in the Yellow River Delta - Peng Yu; Jie Dong; Haisong Liu; Rui Xu; Rujie Wang; Meijun Xu; Hongjun Liu (Journal of Marine Science and Engineering, 2022)
Pile foundations of offshore structures are often subjected to cyclic loads under storm loads, thus reducing their vertical bearing capacity. Therefore, studying the cyclic shear behavior of the soil–structure interface is important for maintaining the stability of offshore structures. A series of cyclic shear tests of the silt–steel interface were carried out using a large interface shear apparatus. The effects of various factors (i.e., normal stress, shear displacement amplitude, roughness, and water content) on the shear stress characteristics of the silt–steel interface were investigated. The stress–displacement model of the cyclic shear silt–steel interface was deduced. The results showed that the shear stress at the silt–steel interface was softened, and the type of bulk deformation was shear shrinkage under cyclic shear. With the increase in shear amplitude, the hysteresis curve gradually developed from “parallelogram” to “shuttle” and “hysteresis cake”. With the increase in normal stress and roughness and the decrease in water content, the interfacial shear strength, volume displacements growth rate, and growth rate increased. The stress–displacement mathematical model of the silt–steel interface based on the modified hyperbolic model was in good agreement with the test data.

Modification of alternative splicing in bovine somatic cell nuclear transfer embryos using engineered CRISPR-Cas13d - Rui Cheng; Xiaoman Zheng; Yingmei Wang; Xing Ma; Xin Liu; Wenjun Xu; Mengyun Wang; Yuanpeng Gao; Xupeng Xing; Chuan Zhou; Hongzheng Sun; Zekun Guo; et al. (Science China Life Sciences, 2022)

Characterization of thermal conductivity of seasonally frozen turfy soil from Northeastern China - Yuanyuan He; Yan Xu; Yan Lv; Lei Nie; Xiaoting Feng; Tingting Liu; Tao Zhang; Yuzheng Wang; Chao Du; Xiangjian Rui; Fansheng Kong (Bulletin of Engineering Geology and the Environment, 2022)

Two new triterpenoid glycosides from leaves of Cyclocarya paliurus - Huihui Sun; Hui Zhu; Jianping Wu; Yuyan Wang; Guihua Li; Yiqian Liu; Xiwen Chang; Saiyu Ou; Wenwen Zha; Huiyun Chen; Rui Gui; Xiaoai He; et al. (Natural Product Research, 2022)

Effect of winter feeding frequency on growth performance, biochemical blood parameters, oxidative stress, and appetite-related genes in Takifugu rubripes - Xiaoqiang Gao; Xinyi Wang; Xi Wang; Hongxu Li; Liang Xu; Yingying Fang; Shuquan Cao; Bin Huang; Haibin Chen; Rui Xing; Baoliang Liu (Fish Physiology and Biochemistry, 2022)

Integration of ABC curve, three dimensions of alpha diversity indices, and spatial patterns of fish assemblages into the health assessment of the Chishui River basin, China - Fandong Yu; Fei Liu; Zhijun Xia; Chunsen Xu; Jianwei Wang; Rui Tang; Zujun Ai; Youzhao Zhang; Miaomiao Hou; Xinhua Zou (Environmental Science and Pollution Research, 2022)

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

A study on the infection status and transmission of avian leukosis virus subgroup J in Hy-line brown roosters - Fanfeng Meng; Qiuchen Li; Rui Han; Guanlong Xu; Xintao Gao; Fubing Luo; Guangnian Shen; Xiaodong Liu; Zhifang Zhang; Peng Zhao; Guozhong Zhang (Archives of Virology, 2022)

Combining gradual and abrupt analysis to detect variation of vegetation greenness on the loess areas of China - Panxing He; Zongjiu Sun; Dongxiang Xu; Huixia Liu; Rui Yao; Jun Ma (Frontiers of Earth Science, 2022)

Hippocampal Activated Microglia May Contribute to Blood–Brain Barrier Impairment and Cognitive Dysfunction in Post-Traumatic Stress Disorder-Like Rats - Kun Ni; Jixiang Zhu; Xuan Xu; Yue Liu; Shuai Yang; Yulin Huang; Rui Xu; Li Jiang; Juan Zhang; Wei Zhang; Zhengliang Ma (Journal of Molecular Neuroscience, 2022)

A novel microRNA regulates cooperation between symbiont and a laterally acquired gene in the regulation of pantothenate biosynthesis within Bemisia tabaci whiteflies - Xiang Sun; Bing‐Qi Liu; Chu‐Qiao Li; Zhan‐Bo Chen; Xiao‐Rui Xu; Jun‐Bo Luan (Molecular Ecology, 2022)
Horizontally transferred genes (HTGs) play a key role in animal symbiosis, and some horizontally transferred genes or proteins are highly expressed in specialized host cells (bacteriocytes). However, it is not clear how HTGs are regulated, but microRNAs (miRNAs) are prime candidates given their previously demonstrated roles in symbiosis and impacts on the expression of host genes. A horizontally acquired PanBC that is highly expressed in whitefly bacteriocytes can cooperate with an obligate symbiont Portiera for pantothenate production, facilitating whitefly performance and Portiera titre. Here, we found that a whitefly miRNA, novel‐m0780‐5p, was up‐regulated and its target panBC was down‐regulated in Portiera ‐eliminated whiteflies. This miRNA was located in the cytoplasmic region of whitefly bacteriocytes. Injection of novel‐m0780‐5p agomir reduced the expression of PanBC in whitefly bacteriocytes, while injection of novel‐m0780‐5p antagomir enhanced PanBC expression. Agomir injection also reduced the pantothenate level, Portiera titre and whitefly performance. Supplementation with pantothenate restored Portiera titre and the fitness of agomir‐injected whiteflies. Thus, we demonstrate that a whitefly miRNA regulates panBC ‐mediated host–symbiont collaboration required for pantothenate synthesis, benefiting the whitefly– Portiera symbiosis. Both panBC and novel‐m0780‐5p are present in the genomes of six Bemisia tabaci species. The expression of a novel miRNA in multiple B . tabaci species suggests that the miRNA evolved after panBC acquisition, and allowed this gene to be more tightly regulated. Our discovery provides the first account of a HTG being regulated by a miRNA from the host genome, and suggests key roles for interactions between miRNAs and HTGs in the functioning of symbiosis.

Correction to: Desiccation cracking in clay‑bottom ash mixtures: insights from crack image analysis and digital image correlation - Rui Liu; Mark Vail; Behrad Koohbor; Cheng Zhu; Chao‑Sheng Tang; Hao Xu; Xiang‑Chao Shi (Bulletin of Engineering Geology and the Environment, 2022)

Desiccation cracking in clay-bottom ash mixtures: insights from crack image analysis and digital image correlation - Rui Liu; Mark Vail; Behrad Koohbor; Cheng Zhu; Chao-Sheng Tang; Hao Xu; Xiang-Chao Shi (Bulletin of Engineering Geology and the Environment, 2022)

Two new sesquiterpenes from the rhizomes of Atractylodes macrocephala and their biological activities - Yi-Nan Zhao; Gai Gao; Jin-Lian Ma; Rui-Zhu Xu; Tao Guo; Li-Min Wu; Xin-Guang Liu; Zhi-Shen Xie; Jiang-Yan Xu; Zhen-Qiang Zhang; Pan Wang (Natural Product Research, 2022)

Cytotoxic α-pyrone derivatives from Cryptocarya yunnanensis - Qian He; Yue Fan; Yu Liu; Yun-Xia You; Li Rao; Yu Su; You-Kai Xu; Bin Lin; Chuan-Rui Zhang (Natural Product Research, 2022)

Aflatoxin B 1 and sterigmatocystin: method development and occurrence in tea - Yarong Zhao; Rui Zeng; Qiongshan Wang; Peirong Chen; Xiangxiang Liu; Xu Wang (Food Additives & Contaminants Part B-Surveillance, 2022)

Molecular cloning and functional characterization of two squalene synthase genes in Atractylodes lancea - Junxian Wu; Rui Xu; Jimei Lu; Weiwei Liu; Hanwen Yu; Mengli Liu; Jing Li; Minzhen Yin; Huasheng Peng; Liangping Zha (Planta, 2022)

Deep convolutional neural network with random field model for lake ice mapping from Sentinel-1 imagery - Zhiguo Ma; Zihao Liu; Jiabin Pu; Linlin Xu; Kui Li; Linglong Wangqu; Rui Wu; Yiyi Ma; Ye Chen; Claude Duguay (International Journal of Remote Sensing, 2021)

Chronic Ethanol Exposure Induces Deleterious Changes in Cardiomyocytes Derived from Human Induced Pluripotent Stem Cells - Rui Liu; Fangxu Sun; Lawrence C. Armand; Ronghu Wu; Chunhui Xu (Stem Cell Reviews and Reports, 2021)

Simvastatin Blocks Reinstatement of Cocaine-induced Conditioned Place Preference in Male Mice with Brain Lipidome Remodeling - Wei Xu; Yuman He; Jiamei Zhang; Hongchun Li; Xuemei Wan; Menglu Li; Yonghai Wang; Rui Xu; Haoluo Zhang; Yanping Dai; Haxiaoyu Liu; Linhong Jiang; et al. (Neuroscience Bulletin, 2021)

Fast and efficient correction for population stratification in multi-locus genome-wide association studies - Rui Liu; Min Yuan; Xu Steven Xu; Yaning Yang (Genetica, 2021)

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

The TCP transcription factor PeTCP10 modulates salt tolerance in transgenic Arabidopsis - Yuzeng Xu; Huanlong Liu; Yameng Gao; Rui Xiong; Min Wu; Kaimei Zhang; Yan Xiang (Plant Cell Reports, 2021)

High-throughput sequencing reveals the spatial distribution variability of microbial community in coastal waters in Shenzhen - Rui Zhang; Yu Liu; Xianfeng Zhao; Zhihui Zhao; Honglian Zhang; Xiaoping Huang; Weiqing Xu; Yuchun Shen; Wensheng Lan (Ecotoxicology, 2021)

TREM-1 Exacerbates Neuroinflammatory Injury via NLRP3 Inflammasome-Mediated Pyroptosis in Experimental Subarachnoid Hemorrhage - Pengfei Xu; Ye Hong; Yi Xie; Kang Yuan; Juanji Li; Rui Sun; Xiaohao Zhang; Xiaolei Shi; Rongrong Li; Jiaonan Wu; Xinfeng Liu; Wei Hu; et al. (Translational Stroke Research, 2021)

The mTOR/NF-κB Pathway Mediates Neuroinflammation and Synaptic Plasticity in Diabetic Encephalopathy - Ting Xu; Jiao Liu; Xin-rui Li; Yinghua Yu; Xuan Luo; Xian Zheng; Yuan Cheng; Pei-quan Yu; Yi Liu (Molecular Neurobiology, 2021)

Temperature and Moisture Modulate the Contribution of Soil Fauna to Litter Decomposition via Different Pathways - Bo Tan; Rui Yin; Jian Zhang; Zhenfeng Xu; Yang Liu; Shuqin He; Li Zhang; Han Li; Lixia Wang; Sining Liu; Chengming You; Changhui Peng (Ecosystems, 2021)

Seasonal variations of water quality response to land use metrics at multi-spatial scales in the Yangtze River basin - Jiahui Xu; Rui Liu; Maofei Ni; Jing Zhang; Qin Ji; Zuolin Xiao (Environmental Science and Pollution Research, 2021)

A New Approach to Embed Complex Fracture Network in Tight Oil Reservoir and Well Productivity Analysis - Jiaxiang Xu; Lifeng Yang; Zhe Liu; Yunhong Ding; Rui Gao; Zhen Wang; Shaoyuan Mo (Natural Resources Research, 2021)

Effects of Diversified Cropping Sequences and Tillage Practices on Soil Organic Carbon, Nitrogen, and Associated Fractions in the North China Plain - Ahmad Latif Virk; Wen-Sheng Liu; Jia-Rui Niu; Cheng-Tang Xu; Qiu-Yue Liu; Zheng-Rong Kan; Xin Zhao; Hai-Lin Zhang (Journal of Soil Science and Plant Nutrition, 2021)

Water Qualities and Products Generated in Dechlorination Process Using Ultra-high Lime with Aluminum Method - Jiali Xu; Peng Chen; Chen Dou; Di Yin; GuangYuan Meng; Rui Cheng; Haifeng Liu; Lehua Zhang (Water, Air, & Soil Pollution, 2021)

A functional chromogen gene C from wild rice is involved in a different anthocyanin biosynthesis pathway in indica and japonica - Weihua Qiao; Yanyan Wang; Rui Xu; Ziyi Yang; Yan Sun; Long Su; Lizhen Zhang; Junrui Wang; Jingfen Huang; Xiaoming Zheng; Shijia Liu; Yunlu Tian; et al. (Theoretical and Applied Genetics, 2021)

Microbiological profiles and antimicrobial resistance patterns of pediatric bloodstream pathogens in China, 2016–2018 - Yue Qiu; Junwen Yang; Yiping Chen; Jinhong Yang; Qingxiong Zhu; Chunhui Zhu; Shuangjie Li; Jing Liu; Chaomin Wan; Yu Zhu; Minxia Chen; Yi Xu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Polymorphisms in the DC-SIGN gene and their association with the severity of hand, foot, and mouth disease caused by enterovirus 71 - Ya-Ping Li; Mu-Qi Wang; Chen-Rui Liu; Hui-Ling Deng; Yuan Wu; Shuang-Suo Dang; Li-Hong Xu (Archives of Virology, 2021)

New titanite U–Pb and molybdenite Re–Os ages for a hydrothermal vein-type Cu deposit in the Lanping Basin, Yunnan, SW China: constraints on regional metallogeny and implications for exploration - Juan Li; Lei-Luo Xu; Xian-Wu Bi; Yong-Yong Tang; Xiang-Yuan Sheng; Hai-Jun Yu; Gong Liu; Rui Ma (Mineralium Deposita, 2021)

Heteroaggregation of humic acid with montmorillonite in divalent electrolytes: effects of humic acid content and ionic concentration - Xiaodan Gao; Yingde Xu; Zhongyi Li; Song Li; Rui Tian; Hang Li; Rattan Lal; Lingzhi Liu; Muhammad Farhan Saeed; Jingkuan Wang (Journal of Soils and Sediments, 2021)

Small RNA Sequencing Analysis of Germinating Single-bud Seedcane Sett in Sugarcane - Kai-Chao Wu; Lin Xu; Zhi-Nian Deng; Tian Pang; Rong-Hua Zhang; Yi-Jie Li; Xiao-Yan Liu; Cheng-Feng Huang; Wen-Xian Qin; Jian-Feng Wei; Li-Ping Wei; Yang-Rui Li; et al. (Sugar Tech, 2021)

An insight into shallow gas hydrates in the Dongsha area, South China Sea - Bin Liu; Jiangxin Chen; Luis M. Pinheiro; Li Yang; Shengxuan Liu; Yongxian Guan; Haibin Song; Nengyou Wu; Huaning Xu; Rui Yang (Acta Oceanologica Sinica, 2021)

Vertical influence of temperature and precipitation on snow cover variability in the Yarlung Zangbo River basin, China - Chunguang Ban; Zongxue Xu; Depeng Zuo; Xiaowan Liu; Rui Zhang; Jing Wang (International Journal of Climatology, 2021)
Seasonal snow cover in mountainous areas is a key source of water for downstream regions. The snow cover area (SCA) in the Northern Hemisphere has significantly decreased during the past decades in response to global warming. Therefore, it is necessary to investigate the primary factors controlling the spatiotemporal variabilities in the SCA in high altitude regions. In this study, based on remote sensing data of SCA, temperature, and precipitation in the Yarlung Zangbo River basin, Pearson's correlation analysis was used to identify the relative importance of temperature and precipitation on the SCA variability with altitude. The results showed that temperature played a more dominant role for the SCA than precipitation at all elevation during the period 2001–2017; three threshold altitudes at high, moderate, and low elevation were identified, and these threshold altitudes are dynamic and vary with time; the threshold altitude at high elevation was 5,925 ± 125 m, below which temperature (precipitation) was negatively (positively) correlated and above which temperature (precipitation) was positively (negatively) correlated with the SCA; the threshold altitude at moderate elevation was 3,200 ± 300 m, below which temperature (precipitation) was positively (negatively) correlated and above which temperature (precipitation) was negatively (positively) correlated with the SCA; the threshold altitude in low elevation regions was 2,100 ± 200 m. This study sheds light on the dominant climatic control factors on the variability in SCA in high altitude regions. These results have major implications for SCA and water resources availability under future climate change.

The substrate‐dependent regulatory effects of the AfeI /R system in Acidithiobacillus ferrooxidans reveals the novel regulation strategy of quorum sensing in acidophiles - Xue‐Yan Gao; Chang‐Ai Fu; Likai Hao; Xiu‐Feng Gu; Rui Wang; Jian‐Qiang Lin; Xiang‐Mei Liu; Xin Pang; Cheng‐Jia Zhang; Jian‐Qun Lin; Lin‐Xu Chen (Environmental Microbiology, 2021)
Summary A LuxI/R‐like quorum sensing (QS) system (AfeI/R) has been reported in the acidophilic and chemoautotrophic Acidithiobacillus spp. However, the function of AfeI/R remains unclear because of the difficulties in the genetic manipulation of these bacteria. Here, we constructed different afeI mutants of the sulfur‐ and iron‐oxidizer A . ferrooxidans , identified the N‐acyl homoserine lactones (acyl‐HSLs) synthesized by AfeI, and determined the regulatory effects of AfeI/R on genes expression, extracellular polymeric substance synthesis, energy metabolism, cell growth and population density of A . ferrooxidans in different energy substrates. Acyl‐HSLs‐mediated distinct regulation strategies were employed to influence bacterial metabolism and cell growth of A . ferrooxidans cultivated in either sulfur or ferrous iron. Based on these findings, an energy‐substrate‐dependent regulation mode of AfeI/R in A . ferrooxidans was illuminated that AfeI/R could produce different types of acyl‐HSLs and employ specific acyl‐HSLs to regulate specific genes in response to different energy substrates. The discovery of the AfeI/R‐mediated substrate‐dependent regulatory mode expands our knowledge on the function of QS system in the chemoautotrophic sulfur‐ and ferrous iron‐oxidizing bacteria, and provides new insights in understanding energy metabolism modulation, population control, bacteria‐driven bioleaching process, and the coevolution between the acidophiles and their acidic habitats.

Elevated atmospheric CO 2 reduces yield‐scaled N 2 O fluxes from subtropical rice systems: Six site‐years field experiments - Zhisheng Yao; Rui Wang; Xunhua Zheng; Baoling Mei; Zaixing Zhou; Baohua Xie; Haibo Dong; Chunyan Liu; Shenghui Han; Zhongjun Xu; Klaus Butterbach‐Bahl; Jianguo Zhu (Global Change Biology, 2021)
Increasing levels of atmospheric CO 2 are expected to enhance crop yields and alter soil greenhouse gas fluxes from rice paddies. While elevated CO 2 ( ) effects on CH 4 emissions from rice paddies have been studied in some detail, little is known how might affect N 2 O fluxes or yield‐scaled emissions. Here, we report on a multi‐site, multi‐year in‐situ FACE (free‐air CO 2 enrichment) study, aiming to determine N 2 O fluxes and crop yields from Chinese subtropical rice systems as affected by . In this study, we tested various N fertilization and residue addition treatments, with rice being grown under either (+200 μmol/mol) or ambient control. Across the six site‐years, rice straw and grain yields under were increased by 9%–40% for treatments fertilized with ≥150 kg N/ha, while seasonal N 2 O emissions were decreased by 23%–73%. Consequently, yield‐scaled N 2 O emissions were significantly lower under . For treatments receiving insufficient fertilization (≤125 kg N/ha), however, no significant effects on N 2 O emissions were observed. The mitigating effect of upon N 2 O emissions is closely associated with plant N uptake and a reduction of soil N availability. Nevertheless, increases in yield‐scaled N 2 O emissions with increasing N surplus suggests that N surplus is a useful indicator for assessing N 2 O emissions from rice paddies. Our findings indicate that with rising atmospheric CO 2 soil N 2 O emissions from rice paddies will decrease, given that the farmers’ N fertilization is usually sufficient for crop growth. The expected decrease in N 2 O emissions was calculated to compensate 24% of the simultaneously observed increase in CH 4 emissions under . This shows that for an agronomic and environmental assessment of effects on rice systems, not only CH 4 emissions, but also N 2 O fluxes and yield‐scaled emissions need to be considered for identifying most climate‐friendly and economically viable options for future rice production.

Three new andrastin derivatives from the endophytic fungus Penicillium vulpinum - Yu-Yue Qin; Xi-Shan Huang; Xiao-Bo Liu; Tu-Xiang Mo; Zhao-Long Xu; Ben-Chao Li; Xiao-Ya Qin; Jun Li; Till F. Schӓberle; Rui-Yun Yang (Natural Product Research, 2020)

Elevated plasma phage load as a marker for intestinal permeability in leukemic patients - Xue-rui Yin; Ping Liu; Xi Xu; Ying Xia; Kai-zhao Huang; Qiong-dan Wang; Mei-mei Lai; Qi-gui Yu; Xiao-qun Zheng (Medical Microbiology and Immunology, 2020)

MHC-DRB1 exon 2 polymorphism and its association with mycoplasma ovipneumonia resistance or susceptibility genotypes in sheep - Kaisheng Wang; Xianxia Liu; Qiongqiong Li; Kexing Wan; Rui Gao; Guohua Han; Chaochen Li; Mengsi Xu; Bin Jia; Xiaoyun Shen (Journal of Genetics, 2020)

Utilizing borehole electrical image and conventional logs to characterize petrology of mixed volcanic and sedimentary rocks in Jiamuhe Formation at JL2 Wellfield, Zhongguai Uplift, Junggar Basin, NW China - Rui Yuan; Lei Zhang; Qinghai Xu; Youlun Feng; Zhiyuan An; Jun Wu; Kang Zhao; Shuai Liu; Peng Huang (Arabian Journal of Geosciences, 2020)

Two new anthraquinone derivatives and one new triarylbenzophenone analog from Selaginella tamariscina - Rui Liu; Hui Zou; Zhen-Xing Zou; Fei Cheng; Xia Yu; Ping-Sheng Xu; Xiao-Min Li; Dai Li; Kang-Ping Xu; Gui-Shan Tan (Natural Product Research, 2020)

Evaluating Spatial Heterogeneity of Land Surface Hydrothermal Conditions in the Heihe River Basin - Yuan Zhang; Shaomin Liu; Xiao Hu; Jianghao Wang; Xiang Li; Ziwei Xu; Yanfei Ma; Rui Liu; Tongren Xu; Xiaofan Yang (Chinese Geographical Science, 2020)

Enhancement of the activity of Cu/TiO2 catalyst by Eu modification for selective catalytic reduction of NOx with NH3 - Yuan-zhen Liu; Qi-yan Xu; Rui-tang Guo; Chao-peng Duan; Gui-lin Wu; Yu-fang Miao; Jing-wen Gu (Environmental Science and Pollution Research, 2020)

Analysis of pituitary transcriptomics indicates that lncRNAs are involved in the regulation of sheep estrus - Xiaoyue Li; Cunyuan Li; Yueren Xu; Rui Yao; Huixiang Li; Wei Ni; Renzhe Quan; Mengdan Zhang; Li Liu; Shuting Yu; Yaseen Ullah; Ruirui Hu; et al. (Functional & Integrative Genomics, 2020)

Effects of different NO3−:NH4+ ratios on the photosynthesis and ultrastructure of lettuce seedlings - Xu Zhu; Rui Yang; Yingyan Han; Jinghong Hao; Chaojie Liu; Shuangxi Fan (Horticulture, Environment, and Biotechnology, 2020)

Clinical strategies for differentiating IgG4-related cholecystitis from gallbladder carcinoma to avoid unnecessary surgical resection - Rui Zhang; Hao-Ming Lin; Zhao-Xi Cai; Su-Juan Du; Hong Zeng; Lei-Bo Xu; Jie Wang; Chao Liu (Science China Life Sciences, 2020)

PDB-1 from Potentilla discolor Bunge suppresses lung cancer cell migration and invasion via FAK/Src and MAPK signaling pathways - Na-na Meng; Rui-rui Zhang; Chao Liu; Qing Wang; Xin-kun Wang; Xu Guo; Ping-ping Wang; Jin-yue Sun (Medicinal Chemistry Research, 2020)

Spent mushroom substrate combined with alkaline amendment passivates cadmium and improves soil property - Zonghui Jin; Meng Zhang; Rui Li; Xu Zhang; Guoliang Wang; Xuesheng Liu; Juanjuan Qu; Yu Jin (Environmental Science and Pollution Research, 2020)

Long-term fertilization and intensive cropping enhance carbon and nitrogen accumulated in soil clay-sized particles of red soil in South China - Hu Xu; Kailou Liu; Wenju Zhang; Yichao Rui; Jingye Zhang; Lei Wu; Gilles Colinet; Qinghai Huang; Xianni Chen; Minggang Xu (Journal of Soils and Sediments, 2020)

Tracing solute sources and carbon dynamics under various hydrological conditions in a karst river in southwestern China - Jing Liu; Bo Chen; Zhu-Yan Xu; Yuan Wei; Zhi-Hua Su; Rui Yang; Yong-Xue Ji; Xiao-Dan Wang; Li-Li Zhang; Ning An; Fei Yang (Environmental Science and Pollution Research, 2020)

MiR-125a-5p Regulates Vitamin D Receptor Expression in a Mouse Model of Experimental Autoimmune Encephalomyelitis - Han-Chun Long; Rui Wu; Chun-Feng Liu; Fei-Long Xiong; Zu Xu; Dian He; Yi-Fan Zhang; Bing Shao; Ping-An Zhang; Guang-Yin Xu; Lan Chu (Neuroscience Bulletin, 2020)

Application of metagenomic next-generation sequencing for bronchoalveolar lavage diagnostics in critically ill patients - Ying Li; Bing Sun; Xiao Tang; Ya-lan Liu; Hang-yong He; Xu-yan Li; Rui Wang; Fei Guo; Zhao-hui Tong (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Risk factors and clinical characteristics of tacrolimus-induced acute nephrotoxicity in children with nephrotic syndrome: a retrospective case-control study - Ping Gao; Xin-Lei Guan; Rui Huang; Xiao-Fang Shang-guan; Jiang-Wei Luan; Mao-Chang Liu; Hua Xu; Xiao-Wen Wang (European Journal of Clinical Pharmacology, 2020)

Forest gaps retard carbon and nutrient release from twig litter in alpine forest ecosystems - Bo Tan; Jian Zhang; Wanqin Yang; Rui Yin; Zhenfeng Xu; Yang Liu; Li Zhang; Han Li; Chengming You (European Journal of Forest Research, 2020)

Genetic variants in circTUBB interacting with smoking can enhance colorectal cancer risk - Ke Zhang; Shuwei Li; Dongying Gu; Kaili Xu; Rui Zheng; Junyi Xin; Yixuan Meng; Shuai Ben; Haiyan Chu; Zhengdong Zhang; Yongqian Shu; Mulong Du; et al. (Archives of Toxicology, 2020)

Quality control of marine big data—a case study of real-time observation station data in Qingdao - Chengcheng Qian; Aichao Liu; Rui Huang; Qingrong Liu; Wenkun Xu; Shan Zhong; Le Yu (Journal of Oceanology and Limnology, 2019)

Digestive characteristics and blood chemistry profile of triploid rainbow trout Oncorhynchus mykiss: influence of body size and seasonal variation - Yuqiong Meng; Buying Han; Changzhong Li; Kangkang Qian; Xiaohong Liu; Xuemin Hu; Xu Yang; Haining Tian; Rui Ma (Fisheries Science, 2019)

Effects of climate change on lake area and vegetation cover over the past 55 years in Northeast Inner Mongolia grassland, China - Yanfei Zhang; Wentao Liang; Zilong Liao; Zhenhua Han; Xiaomin Xu; Rui Jiao; Hualin Liu (Theoretical and Applied Climatology, 2019)

Decreased miR-325-5p Contributes to Visceral Hypersensitivity Through Post-transcriptional Upregulation of CCL2 in Rat Dorsal Root Ganglia - Rui Wu; Ping-An Zhang; Xuelian Liu; Yuan Zhou; Meijie Xu; Xinghong Jiang; Jun Yan; Guang-Yin Xu (Neuroscience Bulletin, 2019)

Effect of genotype and environment on agronomical characters of common vetch (Vicia sativa L.) - Rui Dong; Shu H. Shen; Mohamed Z. Z. Jahufer; De K. Dong; Dong Luo; Qiang Zhou; Xu T. Chai; Kai Luo; Zhi B. Nan; Yan R. Wang; Zhi P. Liu (Genetic Resources and Crop Evolution, 2019)

Effects of Exogenous Application of Melatonin on Quality and Sugar Metabolism in ‘Zaosu’ Pear Fruit - Jianlong Liu; Rongrong Yue; Min Si; Meng Wu; Liu Cong; Rui Zhai; Chengquan Yang; Zhigang Wang; Fengwang Ma; Lingfei Xu (Journal of Plant Growth Regulation, 2019)

Aspergilolide, a steroid lactone produced by an endophytic fungus Aspergillus sp . MBL1612 isolated from Paeonia ostii - Pei-Liang Zhang; Gang Wang; Feng-Qing Xu; Jin-Song Liu; Ju-Tao Wang; Rui Zhang; Hai-Tao Liu; Jiang-Miao Hu; Guo-Kai Wang; Pei-Yun Wu (Natural Product Research, 2019)

Effects of exogenous putrescine on the ultrastructure of and calcium ion flow rate in lettuce leaf epidermal cells under drought stress - Xu Zhu; Lin Wang; Rui Yang; Yingyan Han; Jinghong Hao; Chaojie Liu; Shuangxi Fan (Horticulture, Environment, and Biotechnology, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Optimizing cold storage of the ectoparasitic mite Pyemotes zhonghuajia (Acari: Pyemotidae), an efficient biological control agent of stem borers - Limin He; Litao Li; Lichen Yu; Xiong Z. He; Rui Jiao; Changxin Xu; Linlin Zhang; Jinli Liu (Experimental and Applied Acarology, 2019)

Effects of different substrates on nitrogen and phosphorus removal in horizontal subsurface flow constructed wetlands - Rui Xu; Yong Zhang; Rong Liu; Yun Cao; Guoxiang Wang; Lingchen Ji; Yifan Xu (Environmental Science and Pollution Research, 2019)

Contributions to species of Xylariales in China-1. Durotheca species - Qing De Long; Li Li Liu; Xu Zhang; Ting Chi Wen; Ji Chuan Kang; Kevin David Hyde; Xiang Chun Shen; Qi Rui Li (Mycological Progress, 2019)

Chromosome level comparative analysis of Brassica genomes - Wenliang Wang; Rui Guan; Xing Liu; Haorui Zhang; Bo Song; Qiwu Xu; Guangyi Fan; Wenbin Chen; Xiaoming Wu; Xin Liu; Jianbo Wang (Plant Molecular Biology, 2019)

Multipotential Toxic Metals Accumulated in Urban Soil and Street Dust from Xining City, NW China: Spatial Occurrences, Sources, and Health Risks - Meng Zhang; Xiaoping Li; Rui Yang; Jiwen Wang; Yuwei Ai; Yu Gao; Yuchao Zhang; Xu Zhang; Xiangyang Yan; Bin Liu; Hongtao Yu (Archives of Environmental Contamination and Toxicology, 2019)

Postprandial change in glucose metabolism at the molecular level in the adipose tissue of omnivorous GIFT Oreochromis niloticus - Jing-Yun Feng; Qin-Qin Liu; Hang-Zhong Xu; Rui-Hong Chen; Li Luo; Shi-Mei Lin; Yong-Jun Chen; De-Shou Wang (Fisheries Science, 2019)

Improved ARAIM fault modes determination scheme based on feedback structure with probability accumulation - Qian Meng; Jianye Liu; Qinghua Zeng; Shaojun Feng; Rui Xu (GPS Solutions, 2019)

Investigation of early Bronze Age civilizations in Yunnan: a scientific analysis of metallurgical relics found at the Guangfentou ruins in Jiangchuan - Guisen Zou; Jianfeng Cui; Xu Liu; Xiaorui Li; Rui Min (Archaeological and Anthropological Sciences, 2019)

Eighty Years of Mycopathologia: A Retrospective Analysis of Progress Made in Understanding Human and Animal Fungal Pathogens - Vishnu Chaturvedi; Jean-Philippe Bouchara; Ferry Hagen; Ana Alastruey-Izquierdo; Hamid Badali; Anamelia Lorenzetti Bocca; Jose F. Cano-Lira; Cunwei Cao; Sudha Chaturvedi; Sanjay H. Chotirmall; Anne D. van Diepeningen; Jean-Pierre Gangneux; et al. (Mycopathologia, 2018)

Assessing spectral indices to estimate the fraction of photosynthetically active radiation absorbed by the vegetation canopy - Dailiang Peng; Helin Zhang; Le Yu; Mingquan Wu; Fumin Wang; Wenjiang Huang; Liangyun Liu; Rui Sun; Cunjun Li; Dacheng Wang; Fubao Xu (International Journal of Remote Sensing, 2018)

High-Order Statistics of Temperature Fluctuations in an Unstable Atmospheric Surface Layer over Grassland - Rui Lyu; Fei Hu; Lei Liu; Jingjing Xu; Xueling Cheng (Advances in Atmospheric Sciences, 2018)

Use of cationic microbubbles targeted to P-selectin to improve ultrasound-mediated gene transfection of hVEGF165 to the ischemic myocardium - Wei-hui Shentu; Cao-xin Yan; Chun-mei Liu; Rui-xiang Qi; Yao Wang; Zhao-xu Huang; Li-ming Zhou; Xiang-dong You (Journal of Zhejiang University-SCIENCE B, 2018)

Structural Strength Analysis of a Tri-Floater Floating Foundation for Offshore VAWT - Liqin Liu; Haixiang Zhao; Wanhai Xu; Rui Yuan; Ying Guo (Journal of Ocean University of China, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

Composition and antimicrobial activity of the essential oil from the branches of Jacaranda cuspidifolia Mart. growing in Sichuan, China - Juanjuan Yuan; Tian Gan; Yingtian Liu; Hui Gao; Weifeng Xu; Tao Zhang; Rui Tan; Zhenghong Cai; Hezhong Jiang (Natural Product Research, 2018)

Probing the toxic mechanism of bisphenol A with acid phosphatase at the molecular level - Mengchen Xu; Rui Zhang; Wei Song; Wansong Zong; Rutao Liu (Environmental Science and Pollution Research, 2018)

Expression of BpIAA10 from Betula platyphylla (birch) is differentially regulated by different hormones and light intensities - Wendi Xu; Rui Han; Sijia Xu; Jing Jiang; Guifeng Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Up-regulation of FOS-like antigen 1 contributes to neuronal apoptosis in the cortex of rat following traumatic brain injury - Xide Xu; Rui Jiang; Peipei Gong; Qianqian Liu; Yinan Chen; Shiqiang Hou; Debin Yuan; Jiansheng Shi; Qing Lan (Metabolic Brain Disease, 2018)

TQ-B3203, a potent proliferation inhibitor derived from camptothecin - Xiquan Zhang; Meng Cao; Jing Xing; Fei Liu; Ping Dong; Xin Tian; Hongjiang Xu; Laifang Zhang; Hongmei Gu; Ling Yang; Rui Li; Ming Zheng; et al. (Medicinal Chemistry Research, 2017)

Phenylpropanoids from the fruits of Nicandra physaloides and their anti-inflammatory activities - Bing You Yang; Yan Liu; Hai Bing Jiang; Zhen Peng Xu; Rui Guo; Rui Wang; Xiao Mao Li; Hai Xue Kuang (Natural Product Research, 2017)

Protective effect of Ganoderma lucidum polysaccharide against carbon tetrachloride-induced hepatic damage in precision-cut carp liver slices - Yingjuan Liu; Chunyun Zhang; Jinliang Du; Rui Jia; Liping Cao; Galina Jeney; Hiroki Teraoka; Pao Xu; Guojun Yin (Fish Physiology and Biochemistry, 2017)

Improved GNSS-based indoor positioning algorithm for mobile devices - Rui Xu; Wu Chen; Ying Xu; Shengyue Ji; Jianye Liu (GPS Solutions, 2017)

Genetic and transcriptomic analyses of lignin- and lodging-related traits in Brassica napus - Lijuan Wei; Hongju Jian; Kun Lu; Nengwen Yin; Jia Wang; Xiujian Duan; Wei Li; Liezhao Liu; Xinfu Xu; Rui Wang; Andrew H. Paterson; Jiana Li (Theoretical and Applied Genetics, 2017)

Land use legacies and nitrogen fertilization affect methane emissions in the early years of rice field development - Rui Shao; Ming Xu; Renqiang Li; Xiaoqin Dai; Lixiang Liu; Ye Yuan; Huimin Wang; Fengting Yang (Nutrient Cycling in Agroecosystems, 2017)

Adenovirus-mediated shRNA interference against HSV-1 replication in vitro - Bo Song; Xinjing Liu; Qingzhi Wang; Rui Zhang; Ting Yang; Zhiqiang Han; Yuming Xu (Journal of NeuroVirology, 2016)

Neuroprotective Effects of a PSD-95 Inhibitor in Neonatal Hypoxic-Ischemic Brain Injury - Baofeng Xu; Ai-Jiao Xiao; Wenliang Chen; Ekaterina Turlova; Rui Liu; Andrew Barszczyk; Christopher L. F. Sun; Ling Liu; Michael Tymianski; Zhong-Ping Feng; Hong-Shuo Sun (Molecular Neurobiology, 2016)

TRI6 and TRI10 play different roles in the regulation of deoxynivalenol (DON) production by cAMP signalling in Fusarium graminearum - Cong Jiang; Chengkang Zhang; Chunlan Wu; Panpan Sun; Rui Hou; Huiquan Liu; Chenfang Wang; Jin‐Rong Xu (Environmental Microbiology, 2016)
Summary The biosynthesis of mycotoxin deoxynivalenol (DON) in Fusarium graminearum is regulated by two pathway‐specific transcription factors Tri6 and Tri10 and affected by various host and environmental factors. In this study, we showed that cyclic adenosine monophosphate (cAMP) treatment induced DON production by stimulating TRI gene expression and DON‐associated cellular differentiation in F. graminearum . Interestingly, exogenous cAMP had no effects on the tri6 mutant but partially recovered the defect of tri10 mutant in DON biosynthesis. Although the two cAMP phosphodiesterase genes PDE1 and PDE2 had overlapping functions in vegetative growth, conidiation, sexual reproduction and plant infection, deletion of PDE2 but not PDE1 activated intracellular PKA activities and increased DON production. Whereas the tri6 pde2 mutant failed to produce DON, the tri10 pde2 double mutant produced a significantly higher level of DON than the tri10 mutant. Cellular differentiation associated with DON production was stimulated by exogenous cAMP or deletion of PDE2 in both tri10 and tri6 mutants. These data indicate that TRI6 is essential for the regulation of DON biosynthesis by cAMP signalling but elevated PKA activities could partially bypass the requirement of TRI10 for TRI gene‐expression and DON production, and Pde2 is the major cAMP phosphodiesterase to negatively regulate DON biosynthesis in F. graminearum .

Expression Profile of MiR-128 in the Astrocytoma Patients and Cell Lines - Jingjing Xu; Yuqiong Liu; Si Guo; Shengli Ma; Lin Xiao; Na Wei; Rui Xue (Molecular Neurobiology, 2016)

Genomewide analysis of the lateral organ boundaries domain gene family in Vitis vinifera - HUI CAO; CAI-YUN LIU; CHUN-XIANG LIU; YUE-LING ZHAO; RUI-RUI XU (Journal of Genetics, 2016)

Assessing spatial likelihood of flooding hazard using naïve Bayes and GIS: a case study in Bowen Basin, Australia - Rui Liu; Yun Chen; Jianping Wu; Lei Gao; Damian Barrett; Tingbao Xu; Linyi Li; Chang Huang; Jia Yu (Stochastic Environmental Research and Risk Assessment, 2016)

Prehistoric agriculture development in the Yunnan-Guizhou Plateau, southwest China: Archaeobotanical evidence - HaiMing Li; XinXin Zuo; LiHong Kang; LeLe Ren; FengWen Liu; HongGao Liu; NaiMeng Zhang; Rui Min; Xu Liu; GuangHui Dong (Science China Earth Sciences, 2016)

Transcriptome analysis reveals translational regulation in barley microspore-derived embryogenic callus under salt stress - Cheng-hong Liu; Rui-ju Lu; Gui-mei Guo; Ting He; Ying-bo Li; Hong-wei Xu; Run-hong Gao; Zhi-wei Chen; Jian-hua Huang (Plant Cell Reports, 2016)

Cloning and characterizing of the murine IRF-3 gene promoter region - Hua-Guo Xu; Lifei Liu; Shan Gao; Rui Jin; Wei Ren; Guo-Ping Zhou (Immunologic Research, 2016)

Tigecycline: Alone or in combination? - Yun Cai; Nan Bai; Xu Liu; Beibei Liang; Jin Wang; Rui Wang (Infectious Diseases, 2016)

Cognitive-enhancing effects of hydrolysate of polygalasaponin in SAMP8 mice - Pan Xu; Shu-ping Xu; Ke-zhu Wang; Cong Lu; Hong-xia Zhang; Rui-le Pan; Chang Qi; Yan-yan Yang; Ying-hui Li; Xin-min Liu (Journal of Zhejiang University-SCIENCE B, 2016)

Dynamics of Dissolved Oxygen and the Affecting Factors in Sediment of Polluted Urban Rivers under Aeration Treatment - Bo Liu; Wen-lin Wang; Rui-ming Han; Ming Sheng; Lin-lin Ye; Xu Du; Xin-ting Wu; Guo-xiang Wang (Water, Air, & Soil Pollution, 2016)

The role of exogenous electron donors for accelerating 2,4,6-trichlorophenol biotransformation and mineralization - Ning Yan; Rongjie Li; Hua Xu; Ling Li; Lihui Yang; Yongming Zhang; Rui Liu; Bruce E. Rittmann (Biodegradation, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Plasma miR-221/222 Family as Novel Descriptive and Prognostic Biomarkers for Glioma - Rui Zhang; Bo Pang; Tao Xin; Hua Guo; Yi Xing; Shangchen Xu; Bin Feng; Bin Liu; Qi Pang (Molecular Neurobiology, 2016)

CXCL16 upregulates RANKL expression in rheumatoid arthritis synovial fibroblasts through the JAK2/STAT3 and p38/MAPK signaling pathway - Chang-hong Li; Lin-lin Xu; Jin-xia Zhao; Lin Sun; Zhong-qiang Yao; Xiao-li Deng; Rui Liu; Lin Yang; Rui Xing; Xiang-yuan Liu (Inflammation Research, 2016)

Protective action of the phyllanthin against carbon tetrachloride-induced hepatocyte damage in Cyprinus carpio - Rui Jia; Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Pao Xu; Guo-Jun Yin (In Vitro Cellular & Developmental Biology - Animal, 2016)

The Prevention Effect of Selenium on Prevalence of Children Kaschin-Beck Disease in Active Endemic Areas in Qinghai Plateau - Qiang Li; Zhi-jun Zhao; Pei-zhen Yang; Xiao-qing Xu; Yu-fang Liu; Hui-zhen Yu; Xiao Ma; Rui Du; Lei Zhu (Biological Trace Element Research, 2016)

Effect of irrigation on the soil respiration of constructed grasslands in Inner Mongolia, China - Ji–Rui Gong; Sha Xu; Yihui Wang; Qinpu Luo; Min Liu; Wei Zhang (Plant and Soil, 2015)

Estimation of Permeability from NMR Logs Based on Formation Classification Method in Tight Gas Sands - Deng-Feng Wei; Xiao-Peng Liu; Xiao-Xin Hu; Rui Xu; Ling-Ling Zhu (Acta Geophysica, 2015)

Thermosensation and longevity - Rui Xiao; Jianfeng Liu; X. Z. Shawn Xu (Journal of Comparative Physiology A, 2015)

Baicalein inhibits prostate cancer cell growth and metastasis via the caveolin-1/AKT/mTOR pathway - Zhaoxin Guo; Xiaolin Hu; Zhaoquan Xing; Rui Xing; Renguang Lv; Xiangyu Cheng; Jing Su; Zunlin Zhou; Zhonghua Xu; Sten Nilsson; Zhaoxu Liu (Molecular and Cellular Biochemistry, 2015)

Hepatoprotective and antioxidant effects of phyllanthin against carbon tetrachloride-induced liver injury in Cyprinus carpio - Rui Jia; Jin-Liang Du; Li-Ping Cao; Ying-Juan Liu; Pao Xu; Guo-Jun Yin (Aquaculture International, 2015)

All-trans retinoic acid up-regulates the human CD2AP gene expression through Sp1/Sp3 binding sites - Hua-Guo Xu; Rui Jin; Shan Gao; Wei Ren; Li Zou; Lifei Liu; Guo-Ping Zhou (Immunologic Research, 2015)

Higenamine regulates Nrf2-HO-1-Hmgb1 axis and attenuates intestinal ischemia–reperfusion injury in mice - Chao Liu; Chenyu Zhu; Guangsheng Wang; Rui Xu; Yaoming Zhu (Inflammation Research, 2015)

Decreased expression of microRNA-125a-3p upregulates interleukin-23 receptor in patients with Hashimoto’s thyroiditis - Huiyong Peng; Yingzhao Liu; Jie Tian; Jie Ma; Xinyi Tang; Jun Yang; Ke Rui; Yue Zhang; Chaoming Mao; Liwei Lu; Huaxi Xu; Shengjun Wang (Immunologic Research, 2015)

Ribosomal Protein L3 Mutations are Associated with cfr-Mediated Linezolid Resistance in Clinical Isolates of Staphylococcus cohnii - Hongtao Xu; Rui Tian; Yanming Li; Dongke Chen; Yalin Liu; Yunjian Hu; Fei Xiao (Current Microbiology, 2015)

A novel method for rapid in vivo induction of homogeneous polyploids via calluses in a woody fruit tree (Ziziphus jujuba Mill.) - Qing-Hua Shi; Ping Liu; Meng-Jun Liu; Jiu-Rui Wang; Juan Xu (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Improved FLL-assisted PLL with in-phase pre-filtering to mitigate amplitude scintillation effects - Rui Xu; Zhizhao Liu; Wu Chen (GPS Solutions, 2015)

Effect of grazing on the abundance of functional genes associated with N cycling in three types of grassland in Inner Mongolia - K. Ding; L. Zhong; X. P. Xin; Z. H. Xu; X. M. Kang; W. J. Liu; Y. C. Rui; L. L. Jiang; L. Tang; Y. F. Wang (Journal of Soils and Sediments, 2015)

Assessment of growth rate, chlorophyll a fluorescence, lipid peroxidation and antioxidant enzyme activity in Aphanizomenon flos-aquae, Pediastrum simplex and Synedra acus exposed to cadmium - Xiaofei Ran; Rui Liu; Sha Xu; Fang Bai; Jinzhu Xu; Yanjun Yang; Junqiong Shi; Zhongxing Wu (Ecotoxicology, 2015)

Expression and prognostic role of SGTA in human breast carcinoma correlates with tumor cell proliferation - Ting Zhu; Zhengxiang Ji; Caixia Xu; Zhiyang Peng; Liang Gu; Rui Zhang; Yangchen Liu (Journal of Molecular Histology, 2014)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Association of microRNA-3144 variant with the susceptibility to hepatocellular carcinoma - Jun Zhang; Rui Wang; Min Cai; Shunji Yu; Yanyun Ma; Weihong Xu; Chunfang Gao; Jiucun Wang; Lifang Hou; Yi Liu; Jie Liu (Genes & Genomics, 2014)

Rheological Characteristics of Weak Rock Mass and Effects on the Long-Term Stability of Slopes - Tianhong Yang; Tao Xu; Hongyuan Liu; Chunming Zhang; Shanyong Wang; Yongqin Rui; Li Shen (Rock Mechanics and Rock Engineering, 2014)

Impact of diurnal temperature range on human health: a systematic review - Jian Cheng; Zhiwei Xu; Rui Zhu; Xu Wang; Liu Jin; Jian Song; Hong Su (International Journal of Biometeorology, 2014)

ORF005L from infectious spleen and kidney necrosis virus is located in the inner mitochondrial membrane and induces apoptosis - Rui Wang; Yang Yi; Lihong Liu; Yanghong Lu; Shaoping Weng; Jianguo He; Xiaopeng Xu (Virus Genes, 2014)

Internal loop photo-biodegradation reactor used for accelerated quinoline degradation and mineralization - Ling Chang; Yongming Zhang; Lu Gan; Hua Xu; Ning Yan; Rui Liu; Bruce E. Rittmann (Biodegradation, 2014)

The association between the Lys751Gln polymorphism in the XPD gene and the risk of bladder cancer - Tianyuan Xiong; Jiqiao Yang; Haichuan Wang; Fanyi Wu; Yang Liu; Rui Xu; Zi Lv; Pei Xue; Wen Cao; Yonggang Zhang (Molecular Biology Reports, 2014)

Selection and Characterization of a Peptide Specifically Targeting to Gastric Cancer Cell Line SGC-7901 Using Phage Display - Han Wang; Rui Li; Caixia Ma; Shaoying Lu; Dan Zhang; Yonge Guo; ChunYan Li; Jinling Wu; Qixuan Wang; Jinhui Xu; Yanyan Hu; Yuen Liu; et al. (International Journal of Peptide Research and Therapeutics, 2014)

New isoflavones with cytotoxic activity from the rhizomes of Iris germanica L. - Guo-Yong Xie; Xiao-Ying Qin; Rui Liu; Qi Wang; Bin-Bin Lin; Guo-Kai Wang; Guang-Kai Xu; Rui Wen; Min-Jian Qin (Natural Product Research, 2013)

Characterization of OsMIK in a rice mutant with reduced phytate content reveals an insertion of a rearranged retrotransposon - Hai-Jun Zhao; Hai-Rui Cui; Xiu-Hong Xu; Yuan-Yuan Tan; Jun-Jie Fu; Guo-Zhen Liu; Yves Poirier; Qing-Yao Shu (Theoretical and Applied Genetics, 2013)

Microbial Treatment for Prevention and Removal of Paraffin Deposition on the Walls of Crude Pipelines - Jiang Hong Liu; Yun Peng Jia; Yi Tong Chen; Rui Dan Xu (Indian Journal of Microbiology, 2013)

The Effect of Energy Substrates on PHB Accumulation of Acidiphilium cryptum DX1-1 - Ai-ling Xu; Jin-lan Xia; Zhi-wen Song; Peng Jiang; Yan Xia; Min-xi Wan; Rui-yong Zhang; Yi Yang; Ke-ke Liu (Current Microbiology, 2013)

Pelagibacterium nitratireducens sp.nov., A Marine Alphaproteobacterium Isolated from the East China Sea - Qipei Li; Yongle Xu; Keshao Liu; Lanlan Cai; Yingnan Fu; Jia Sun; Rui Zhang (Current Microbiology, 2013)

Upregulation of CBLL1 in rat brain cortex after lipopolysaccharide treated - Maohong Cao; Heyi Zheng; Xiang Tan; Wei Xu; Ying Rui; Lei Li; Xiaofei Liu; Guangfei Xu; Gang Cui; Jian Xu; Jianhua Cao; Kaifu Ke; et al. (Journal of Molecular Histology, 2013)

WHAMM is required for meiotic spindle migration and asymmetric cytokinesis in mouse oocytes - Xin Huang; Lu Ding; Rui Pan; Peng-Fei Ma; Pan-Pan Cheng; Chun-Hui Zhang; Yu-Ting Shen; Lin Xu; Yu Liu; Xiao-Qin He; Zhong-Quan Qi; Hai-Long Wang (Histochemistry and Cell Biology, 2013)

Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

Postconditioning with vagal stimulation attenuates local and systemic inflammatory responses to myocardial ischemia reperfusion injury in rats - Qiang Wang; Yi Cheng; Fu-Shan Xue; Yu-Jing Yuan; Jun Xiong; Rui-Ping Li; Xu Liao; Jian-Hua Liu (Inflammation Research, 2012)

Synthesis of 2-R1-2-(4-(2-fluoroethoxy)benzamido)acetate as potential PET imaging agents - Yong He; Jingli Xu; Hang Liu; Man Feng; Xiao Wang; Rui Ding; Chuanmin Qi; Yurong Chen; Fang Li; Zhao-Hui Zhu; Yong-Hong Dang; Ming Wang; et al. (Medicinal Chemistry Research, 2012)

Erbin inhibits TGF-β1-induced EMT in renal tubular epithelial cells through an ERK-dependent pathway - Qiaodan Zhou; Rui Zeng; Chuou Xu; Lili Liu; Lin Chen; Pei Kou; Guangchang Pei; Shoujun Bai; Yamin Zhang; Caixia Li; Song Rong; Min Han; et al. (Journal of Molecular Medicine, 2012)

Preparation and bioevaluation of 99mTc nitrido radiopharmaceuticals with pyrazolo[1,5-a]pyrimidine as tumor imaging agents - Rui Ding; Yong He; Jingli Xu; Hang Liu; Xiao Wang; Man Feng; Chuanmin Qi; Junbo Zhang; Cheng Peng (Medicinal Chemistry Research, 2012)

Oceaniovalibus guishaninsula gen. nov., sp. nov., A Marine Bacterium of the Family Rhodobacteraceae - Keshao Liu; Rui Zong; Qipei Li; Yingnan Fu; Yongle Xu; Yanan Wang; Nianzhi Jiao (Current Microbiology, 2012)

Natural Heritage value of Xinjiang Tianshan and global comparative analysis - Xiaoliang Xu; Zhaoping Yang; Adayi Saiken; Shao Rui; Xinyu Liu (Journal of Mountain Science, 2012)

A New Piezochromic Fluorescence and Aggregation-Induced Emission Compound Containing Tetraphenylethylene and Triphenylamine Moieties with Morphology-alterable Property - Xie Zhou; Hai-yin Li; Zhen-guo Chi; Bing-jia Xu; Xi-qi Zhang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2012)

The Mechanism of the Molecular Interaction between Cerium (III) and Ribulose-1,5-Bisphosphate Carboxylase/Oxygenase (Rubisco) - Chao Liu; Fa-shui Hong; Ye Tao; Tao Liu; Ya-ning Xie; Jian-hua Xu; Zhong-rui Li (Biological Trace Element Research, 2011)

Synthesis and Characterization of Triphenylethylene Derivatives with Aggregation-Induced Emission Characteristics - Xiao-Fang Li; Zhen-Guo Chi; Bing-Jia Xu; Hai-Yin Li; Xi-Qi Zhang; Wei Zhou; Yi Zhang; Si-Wei Liu; Jia-Rui Xu (Journal of Fluorescence, 2011)

Expression of a novel gene FAM43B repressing cell proliferation is regulated by DNA methylation in hepatocellular carcinoma cell lines - Xiao Xu; Rui-Fang Liu; Bing-Bing Wan; Wen-Ming Xing; Jian Huang; Ze-Guang Han (Molecular and Cellular Biochemistry, 2011)

Symbiotic nitrogen fixation and soil N availability under legume crops in an arid environment - Xiaoqi Zhou; Xian Liu; Yichao Rui; Chengrong Chen; Hanwen Wu; Zhihong Xu (Journal of Soils and Sediments, 2011)

Multiple amino acid variations in the nonstructural proteins of swine Japanese encephalitis virus alter its virulence in mice - Rui Wu; Yongxiang Tian; Junhua Deng; Keli Yang; Wangwang Liang; Rui Guo; Zhengying Duan; Zewen Liu; Danna Zhou; Diping Xu (Archives of Virology, 2011)

Synthesis and Properties of Diphenylcarbazole Triphenylethylene Derivatives with Aggregation-Induced Emission, Blue Light Emission and High Thermal Stability - Bing-jia Xu; Zhen-guo Chi; Xiao-fang Li; Hai-yin Li; Wei Zhou; Xi-qi Zhang; Cheng-cheng Wang; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Comparison of Responsive Behaviors of Two Cinnamic Acid Derivatives Containing Carbazolyl Triphenylethylene - Xi-qi Zhang; Zhen-guo Chi; Bing-jia Xu; Hai-yin Li; Wei Zhou; Xiao-fang Li; Yi Zhang; Si-wei Liu; Jia-rui Xu (Journal of Fluorescence, 2011)

Isolation and Analysis of Rice Rf1-Orthologus PPR Genes Co-segregating with Rf3 in Maize - Xiang-Bo Xu; Zhan-Xian Liu; Deng-Feng Zhang; Ying Liu; Wei-Bin Song; Jian-Sheng Li; Jing-Rui Dai (Plant Molecular Biology Reporter, 2009)

The Influence of Cosolvent on the Complexation of HP-β-cyclodextrins with Oleanolic Acid and Ursolic Acid - Rui Li; Peng Quan; Dong-Fei Liu; Fang-Di Wei; Qing Zhang; Qun-Wei Xu (AAPS PharmSciTech, 2009)

Deglycosylation altered the gating properties of rNav1.3: glycosylation/deglycosylation homeostasis probably complicates the functional regulation of voltage-gated sodium channel - Qing Xu; Hui-Wen Cheng; Hui-Qiong He; Zhi-Rui Liu; Ming He; Hong-Tian Yang; Zhi-Lei Zhou; Yong-Hua Ji (Neuroscience Bulletin, 2008)

Vesicular stomatitis virus matrix protein gene enhances the antitumor effects of radiation via induction of apoptosis - Xiao-Bo Du; Jin-Yi Lang; Jian-Rong XU; You Lu; Yan-Jun Wen; Ju-Mei Zhao; Peng Diao; Zhi-Ping Yuan; Bin Yao; Ling-Yu Fan; Guo-Qing Wang; Li Liu; et al. (Apoptosis, 2008)

Isolation and molecular characterization of the Triticum aestivum L. ethylene-responsive factor 1 (TaERF1) that increases multiple stress tolerance - Zhao-Shi Xu; Lan-Qin Xia; Ming Chen; Xian-Guo Cheng; Rui-Yue Zhang; Lian-Cheng Li; Yun-Xiang Zhao; Yan Lu; Zhi-Yong Ni; Li Liu; Zhi-Gang Qiu; You-Zhi Ma (Plant Molecular Biology, 2007)

Prohibitin suppresses renal interstitial fibroblasts proliferation and phenotypic change induced by transforming growth factor-β1 - Wei Guo; Hong Xu; Jing Chen; Yong Yang; Jia Wei Jin; Rui Fu; Hai Mei Liu; Xi Liang Zha; Zhi Gang Zhang; Wen Yan Huang (Molecular and Cellular Biochemistry, 2007)

Inhibition of Japanese Encephalitis Virus NS1 Protein Expression in Cell by Small Interfering RNAs - Xueqin Liu; Shengbo Cao; Rui Zhou; Gaoyuan Xu; Shaobo Xiao; Ying Yang; Minxuan Sun; Yaoming Li; Huanchun Chen (Virus Genes, 2006)

Biophysical studies of a ruthenium(II) polypyridyl complex binding to DNA and RNA prove that nucleic acid structure has significant effects on binding behaviors - Hong Xu; Yi Liang; Peng Zhang; Fen Du; Bing-Rui Zhou; Jun Wu; Jian-Hong Liu; Zhi-Gang Liu; Liang-Nian Ji (JBIC Journal of Biological Inorganic Chemistry, 2005)